Polyester Polymer Nanocomposite

JP2024500790A5Pending Publication Date: 2025-01-08KINTRA FIBERS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023537232
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-12-23
Filing Date
2021-12-23
Publication Date
2025-01-08

Smart Images

  • Figure 00000082_0000
    Figure 00000082_0000
  • Figure 00000082_0001
    Figure 00000082_0001
  • Figure 00000082_0002
    Figure 00000082_0002
Patent Text Reader

Abstract

Aspects of the present disclosure include compositions of polymer-polysaccharide nanocomposite resins and methods for producing polymer-polysaccharide nanocomposite resins, comprising polymerizing alkanediol monomers and alkanediol monomers in a mixture containing dispersed polysaccharide nanocrystals, a catalyst, and one or more optional additives under conditions sufficient to produce a polymer-polysaccharide nanocomposite resin. Aspects of the present disclosure further include compositions of polybutylene succinate nanocomposites and methods for producing polybutylene succinate nanocomposites, comprising dispersing cellulose nanocrystals in 1,4 butanediol (BDO) to form a cellulose-BDO dispersion and esterifying the cellulose-BDO dispersion with succinic anhydride to form a plurality of polybutylene succinate oligomers. The polybutylene succinate oligomers are condensed to form a polybutylene succinate nanocomposite.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims the benefit of U.S. Provisional Application No. 63 / 130,020, filed December 23, 2020, which is incorporated by reference in its entirety. [Background technology]

[0002] (introduction) Aliphatic polyester polymers can have many interesting properties, such as biodegradability, melt processability, and heat and chemical resistance. Polybutylene succinate (PBS) is a promising polymer that exhibits high processability for various potential applications, since it can be processed into melt-blown, multifilament, monofilament, flat, and split yarns in the textile field, and into injection molded articles in the plastic field.

[0003] PBS is typically synthesized by esterification reaction between 1,4 butanediol and succinic acid, followed by condensation of the intermediate oligomeric products produced to form the PBS polymer. A common method for increasing the molecular weight of the PBS polymer by such methods is by adding a chain extender, such as a carbonate or diisocyanate, during preparation.

[0004] Conventional processes can be accompanied by undesirable and toxic by-products and reactants. One by-product of PBS production is tetrahydrofuran (THF), a hazardous waste product formed when 1,4 butanediol monomer cyclizes. Diisocyanate chain extenders are a non-renewable resource, are potentially toxic, and require additional processing steps for use.

[0005] Linear aliphatic polyesters such as PBS are more susceptible to thermal and hydrolytic degradation than higher melting polyesters such as polyethylene terephthalate (PET), polytrimethylene terephthalate (PTT), or polybutylene terephthalate (PBT). The physical performance of these polymers becomes extremely sensitive to formulation and subsequent physical processing.

[0006] Polymers used in textile applications must survive numerous processing steps, such as compounding, melt spinning, drawing, weaving / knitting, dyeing / finishing, and washing. For example, synthetic fibers can be produced by the melt spinning process. In this process, molten polymer is extruded through a die (also called a spinneret) to create a cylindrical jet of viscous polymer, i.e., a fiber. The fiber, wound on a drum from the spinneret, is pulled away at a given winding speed. The winding speed is typically much higher than the extrusion speed in industrial processes, e.g., the winding speed can be about 50 m / s and the extrusion speed can be about 10 m / s. The ratio between the winding speed (vL) and the extrusion speed (v0) is called the draw ratio d. Thus, the filament length is significantly stretched, and thus the diameter is reduced. The ambient atmosphere temperature is lower than the polymer solidification temperature so that the polymer cools and solidifies before winding. In industrial processes, entire bundles of hundreds of single filaments can be extruded and spun in parallel. Summary of the Invention [Problem to be solved by the invention]

[0007] There remains a need for methods for producing polymer-polysaccharide nanocomposite resins that utilize renewable feedstocks and provide polymer products with improved properties and processability while reducing the amount of waste produced. [Means for solving the problem]

[0008] Aspects of the present disclosure include compositions of polyester polymer-polysaccharide nanocomposite resins and methods for producing polyester polymer-polysaccharide nanocomposite resins. The methods of the present disclosure may include polymerizing alkanediol monomers and alkanediol monomers in a mixture containing dispersed polysaccharide nanocrystals, a catalyst, and one or more optional additives under conditions sufficient to produce a polymer-polysaccharide nanocomposite resin. The catalyst can be added to the mixture before or during polymerization. The polymerization can be carried out in a one-pot reaction. The polymerization can be carried out as a single step or as two separate steps having different reaction conditions. Aspects of the present disclosure further include compositions of polybutylene succinate nanocomposites and methods for producing polybutylene succinate nanocomposites, the methods including dispersing cellulose nanocrystals in 1,4 butanediol (BDO) to form a cellulose-BDO dispersion and esterifying the cellulose-BDO dispersion and succinate anhydride to form a plurality of polybutylene succinate oligomers. The polybutylene succinate oligomers are condensed to form a polybutylene succinate nanocomposite.

[0009] In another embodiment, the method includes adding cellulose nanocrystals to 1,4 butanediol to form a cellulose-BDO mixture, and then sonicating the cellulose-BDO mixture to disperse the cellulose nanocrystals in the 1,4 butanediol to form a cellulose-BDO dispersion. A succinate derivative is esterified in the cellulose-BDO dispersion to form a plurality of polybutylene succinate oligomers. The polybutylene succinate oligomers are condensed to form a polybutylene succinate nanocomposite.

[0010] Another embodiment of the method includes adding cellulose nanocrystals to 1,4 butanediol to form a cellulose-BDO mixture and sonicating the cellulose-BDO mixture to disperse the cellulose nanocrystals in the 1,4 butanediol to form a cellulose-BDO dispersion. The cellulose-BDO dispersion and succinate anhydride are esterified to form a plurality of polybutylene succinate oligomers, which are then condensed to form a polybutylene succinate nanocomposite. [Brief description of the drawings]

[0011] [Figure 1] Figure 1 shows a plot of dynamic viscosity versus temperature for polybutylene succinate nanocomposite synthesized from cellulose nanocrystals dispersed in 1,4 butanediol using a homogenizer and esterified with epoxidized linseed oil. [Diagram 2] 1 shows a particle size distribution plot of polymer fiber containing material prepared as shown in Example 13. [Figure 3A] FIG. 1 shows particle size distribution plots of various cellulose nanocrystals dispersed in 1,4 butanediol at 60, 80 or 100% sonication amplitude, respectively. FIG. 1 shows particle size distribution plots of various cellulose nanocrystals dispersed in 1,4 butanediol at 60%, 80 or 100% sonication amplitude, respectively. [Figure 3B] FIG. 1 shows particle size distribution plots of various cellulose nanocrystals dispersed in 1,4 butanediol at 60, 80 or 100% sonication amplitude, respectively. ... [Figure 3C] FIG. 1 shows particle size distribution plots of various cellulose nanocrystals dispersed in 1,4 butanediol at 60, 80 or 100% sonication amplitude, respectively. FIG. 100% sonication amplitude. [Figure 4A] 1 shows particle size distribution plots of cellulose nanocrystals dispersed in 1,4 butanediol at homogenizer speeds of 10,000 rpm, 13,333 rpm, or 16,666 rpm for 1 minute, respectively; 10,000 rpm for 1 minute. [Figure 4B]1 shows particle size distribution plots of cellulose nanocrystals dispersed in 1,4 butanediol at homogenizer speeds of 10,000 rpm, 13,333 rpm, or 16,666 rpm for 1 minute, respectively. [Figure 4C] 1 shows particle size distribution plots of cellulose nanocrystals dispersed in 1,4 butanediol at homogenizer speeds of 10,000 rpm, 13,333 rpm, or 16,666 rpm for 1 minute, respectively. [Diagram 5] 1 shows a plot of intrinsic viscosity versus maximum fiber length for conventional commercial grade PBS polymer resin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The foregoing and other aspects of the present invention will be described in more detail below with reference to the descriptions and methodologies provided herein. It is understood that the present invention may be embodied in different forms and should not be construed as being limited to the embodiments set forth herein. Rather, these embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the invention to those skilled in the art.

[0013] The terms used in the description of the present specification are intended to describe specific embodiments only and are not intended to limit the present invention. When used in the description of the embodiments of the present invention and the appended claims, the singular forms "a", "an" and "the" are intended to include the plural forms unless the context clearly indicates otherwise. Also, as used herein, "and / or" refers to and includes any and all possible combinations of one or more of the associated listed items.

[0014] The term "about" as used herein when referring to measurable values ​​such as the amount of a compound, dosage, time, temperature, etc. is meant to encompass variations of 20%, 10%, 5%, 1%, 0.5%, and even 0.1% of the specified amount. Unless otherwise defined, all terms, including technical and scientific terms, used in the description have the same meaning as commonly understood by those skilled in the art to which this invention belongs.

[0015] The terms "comprise," "comprises," "comprising," "include," "includes," and "including" specify the presence of stated features, integers, steps, operations, elements, and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or groups thereof.

[0016] The term "consisting essentially of" (and grammatical variations thereof) as applied to the compositions and methods of the present invention means that the composition / method may contain additional components so long as the additional components do not substantially alter the composition / method. The term "substantially alter" as applied to a composition / method refers to an increase or decrease in the effectiveness of the composition / method by at least about 20% or more.

[0017] All patents, patent applications, and publications referenced herein are incorporated by reference in their entirety. In the event of a conflict of terminology, the present specification will control.

[0018] Aspects of the present disclosure include compositions of polymer-polysaccharide nanocomposite resins and methods for producing the polymer-polysaccharide nanocomposite resins, comprising preparing a mixture (e.g., a dispersion) comprising polysaccharide nanocrystals, alkanediol monomers, alkanedioic acid monomers, and a catalyst, and polymerizing the alkanediol monomers and alkanedioic acid monomers in the dispersion to produce the polymer-polysaccharide nanocomposite resin. In some embodiments, the polysaccharide nanocrystals and / or catalyst are added in situ to the mixture after polymerization has been initiated. Aspects of the present disclosure further include compositions of polybutylene succinate nanocomposites and methods for producing the polybutylene succinate nanocomposite, comprising dispersing cellulose nanocrystals in 1,4 butanediol (BDO) to form a cellulose-BDO dispersion, and esterifying the cellulose-BDO dispersion and succinate anhydride to form a plurality of polybutylene succinate oligomers. The polybutylene succinate oligomers are condensed to form a polybutylene succinate nanocomposite.

[0019] Polyester polymer-polysaccharide nanocomposite resin An embodiment of the present disclosure includes a polyester polymer-polysaccharide nanocomposite resin composition.

[0020] A nanocomposite, as used herein in its conventional sense, generally consists of multiple nanoscale materials or nanoscale materials incorporated into a bulk material. A nanocomposite can be a multiphase solid material in which one of the phases has one, two, or three dimensions or a structure with repeating nanoscale distances between the different phases that make up the material. Thus, a nanocomposite can include nanoparticles entrained in a polymer matrix.

[0021] In some embodiments, the polyester polymer-polysaccharide nanocomposite resin comprises an increased modulus and strength due to the addition of the nanocomposite to provide reinforcing fibers, compared to the modulus and strength of the polyester polymer-polysaccharide without the addition of the nanocomposite.

[0022] In some embodiments, the polyester polymer-polysaccharide nanocomposite resin may act to toughen the base polymer resin, thereby enhancing one or more mechanical properties of the base resin. Non-limiting properties that may be improved by incorporating polysaccharide nanoparticles into the base polyester polymer resin may be selected from at least one of modulus of elasticity, tensile yield stress, strength, toughness, hoop stress rating, flexural modulus, UV resistance, and reduced gas or moisture permeability, flame retardant mechanism, antimicrobial properties. Thus, the present disclosure allows for measurable enhancement of performance to be achieved without significant loss of other desirable properties such as tensile strength, ultimate elongation, melt index, thermal stability, flame retardant properties, antimicrobial properties, reduced gas and / or moisture permeability, impact strength, slow crack growth resistance, and rapid crack propagation resistance.

[0023] In some embodiments, the polyester polymer-polysaccharide nanocomposite resin provides an improved yield stress of at least 1%, at least 2%, at least 3%, at least 4%, at least 5%, at least 6%, at least 7%, at least 8%, at least 9%, or at least 10% compared to the base polymer alone, i.e., a composition lacking polysaccharide nanoparticles. In some embodiments, the polyester polymer-polysaccharide nanocomposite resin provides an improved yield stress of at least 10%, at least 20%, at least 30%, at least 40%, at least 50%, at least 60%, at least 70%, at least 80%, or at least 90% compared to the base polymer alone. In some embodiments, the polyester polymer-polysaccharide nanocomposite resin provides an improved yield stress of up to 200%, e.g., up to 100%, compared to the base polymer alone. In some embodiments, the polyester polymer-polysaccharide nanocomposite resin provides improved yield stress in the range of 10% to 15%, 15% to 20%, 20% to 25%, 25% to 30%, 30% to 35%, 35% to 40%, 40% to 45%, or 45% to 50% compared to the base polymer alone.

[0024] In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has a tensile strength in the range of about 10 MPa to about 60 MPa. In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has a tensile strength in the range of about 10 MPa to about 15 MPa, about 15 MPa to about 20 MPa, about 20 MPa to about 25 MPa, about 25 MPa to about 30 MPa, about 30 MPa to about 35 MPa, about 35 MPa to about 40 MPa, about 40 MPa to about 45 MPa, about 45 MPa to about 50 MPa, about 50 MPa to about 55 MPa, about 55 MPa to about 60 MPa, about 60 MPa to about 65 MPa, or about 65 MPa to about 70 MPa. In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has a tensile strength of about 10 MPa or more, about 15 MPa or more, about 15 MPa or more, about 20 MPa or more, about 20 MPa or more, about 25 MPa or more, about 25 MPa or more, about 30 MPa or more, about 30 MPa to about 35 MPa or more, about 35 MPa or more, 40 MPa or more, about 45 MPa or more, about 45 MPa or more, about 50 MPa or more, about 50 MPa or more, about 55 MPa or more, about 55 MPa or more, about 60 MPa or more, about 65 MPa or more, or about 70 MPa or more. In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has a tensile strength in the range of about 20 MPa to about 35 MPa. In some embodiments, the polymer-polysaccharide nanocomposite resin has a tensile strength in the range of about 20 MPa to about 40 MPa. In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has a tensile strength in the range of about 20 MPa to about 60 MPa. In some embodiments, the polymer-polysaccharide nanocomposite resin has a tensile strength in the range of about 20 MPa to about 70 MPa. In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has a tensile strength in the range of about 10 MPa to about 70 MPa.

[0025] In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has a stiffness modulus in the range of 250 MPa to about 450 MPa. In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has a modulus or stiffness in the range of 300 MPa to 400 MPa. In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has a modulus or stiffness of 300 MPa or more, 305 MPa or more, 310 MPa or more, 315 MPa or more, 320 MPa or more, 330 MPa or more, 340 MPa or more, 350 MPa or more, 360 MPa or more, 370 MPa or more, 380 MPa or more, 390 MPa or more, or 400 MPa or more.

[0026] In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has an elastic modulus in the range of 0.10 GPa to about 1.0 GPa. In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has an elastic modulus in the range of 0.20 GPa to about 0.5 GPa. In some embodiments, the polymer-polysaccharide nanocomposite resin has an elastic modulus in the range of 0.20 GPa to about 0.4 GPa. In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has an elastic modulus of 0.10 GPa or more, 0.15 GPa or more, 0.20 GPa or more, 0.25 GPa or more, 0.30 GPa or more, 0.35 GPa or more, 0.40 GPa or more, 0.45 GPa or more, or 0.50 GPa or more.

[0027] In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has a tensile strain (εu) percentage ranging from 10% to about 300%. In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has a tensile strain (εu) percentage ranging from 20% to 200%. The polyester polymer-polysaccharide nanocomposite resin may have a tensile strain (εu) percentage of 10% or more, 20% or more, 30% or more, 40% or more, 50% or more, 60% or more, 70% or more, 80% or more, 90% or more, 100% or more, 110% or more, 120% or more, 130% or more, 140% or more, 150% or more, 160% or more, 170% or more, 180% or more, 190% or more, 200% or more, 210% or more, 220% or more, 230% or more, 240% or more, 250% or more, 260% or more, 270% or more, 280% or more, 290% or more, or 300% or more.

[0028] In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has an intrinsic viscosity in the range of about 0.1 to about 1.5 dL / g. In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has an intrinsic viscosity in the range of about 0.2 to about 0.8 dL / g, such as about 0.2 to about 0.5 dL / g. Intrinsic viscosity, as used herein and in its conventional sense, is a measure of the contribution of a solute to the viscosity of a solution. In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has a viscosity of about 0.10 dL / g or more, 0.15 dL / g or more, 0.20 dL / g or more, 0.25 dL / g or more, 0.30 dL / g or more, 0.35 dL / g or more, 0.40 dL / g or more, 0.45 dL / g or more, 0.50 dL / g or more, 0.55 dL / g or more, 0.60 dL / g or more, 0.65 dL / g or more, 0.70 dL / g or more or greater, 0.75 dL / g or greater, 0.80 dL / g or greater, 0.85 dL / g or greater, 0.90 dL / g or greater, 0.95 dL / g or greater, 1.0 dL / g or greater, 1.10 dL / g or greater, 1.15 dL / g or greater, 1.20 dL / g or greater, 1.25 dL / g or greater, 1.30 dL / g or greater, 1.35 dL / g or greater, 1.40 dL / g or greater, 1.45 dL / g or greater, or 1.50 dL / g or greater. In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has an intrinsic viscosity of about 0.8 dL / g or greater. In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has an intrinsic viscosity of about 0.9 dL / g or greater. In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has an intrinsic viscosity in the range of about 0.8 to about 1.5 dL / g. In some embodiments, the polyester polymer-polysaccharide nanocomposite resins have an intrinsic viscosity in the range of about 0.9 to about 1.5 dL / g. The intrinsic viscosity of the polyester polymer-polysaccharide nanocomposite resins of the present disclosure can be determined by standard methods using a capillary-based viscometer under standard conditions and a temperature of 20° C., for example, as described herein, or according to the ASTM D445 and D2515 test methods.

[0029] In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has a relative viscosity in the range of about 3 to about 150. Relative viscosity, as used herein and in its conventional sense, refers to the ratio of the viscosity of the polymer solution to the viscosity of the solvent used. In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has a relative viscosity in the range of about 3 to about 5, about 5 to about 7, about 7 to about 10, about 10 to about 15, about 15 to about 20, about 20 to about 25, about 25 to about 30, about 30 to about 35, about 35 to about 40, about 40 to about 45, about 45 to about 50, about 50 to about 55, about 55 to about 60, about 60 to about 65, about 65 to about 70, about 70 to about 75, about 75 to about 80, about 80 to about 85, about 85 to about 90, about 90 to about 95, about 95 to about 100, about 100 to about 105, about 105 to about 110, about 110 to about 115, about 115 to about 120, about 120 to about 125, about 125 to about 130, about 130 to about 135, about 135 to about 140, about 140 to about 145, or about 145 to about 150.

[0030] In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has a melt viscosity in the range of about 500 to about 15,000 cP. In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has a melt viscosity in the range of about 500 to about 10,000 cP. In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has a melt viscosity in the range of about 500 to about 1,000 cP. In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has a melt viscosity in the range of about 800 to about 10,000 cP. In some embodiments, the polyester polymer-polysaccharide nanocomposite resin has a melt viscosity in the range of about 500 to about 1,000 cP, about 1,000 cP to about 1,500 cP, about 1,500 cP to about 2,000 cP, about 2,000 cP to about 2,500 cP, about 2,500 cP, to about 3,000 cP, about 3,000 cP to about 3,500 cP, about 4,000 cP, about 4,000 cP to about 4,500 cP, about 4,500 cP to about 5,000 cP, about 5,000 cP to about 7,000 cP, about 7,000 cP to about 10,000 cP, or about 10,000 cP to about 15,000 cP. In some cases, the melt temperature at which the melt viscosity is measured is from about 115°C to about 230°C.

[0031] Polysaccharide Nanoparticles An embodiment of the present disclosure includes a polyester polymer-polysaccharide nanocomposite resin that includes polysaccharide nanoparticles.

[0032] Polysaccharides are composed of multiple sugar units linked together by glycosidic linkages and have several unique characteristics that distinguish them from other biopolymer families. The polysaccharide materials used in the subject nanocomposites can be nanoparticles, i.e., nanostructured forms of the polysaccharide of interest. In some cases, the nanoparticles are crystalline and can be referred to as nanocrystals.

[0033] The polyester polymer-polysaccharide resin may be derived from polysaccharide nanoparticles. In some embodiments, the polyester polymer-polysaccharide resin is derived from polysaccharide nanocrystals and one or more monomers. In some embodiments, the one or more monomers include alkanediol monomers and alkanediacid monomers.

[0034] In some embodiments, the polysaccharide nanocrystals are derived from heparin, chitosan, chitin, hyaluronan, starch, cellulose, alginate, pectin, guar, starch / chitosan, chitosan / heparin, chitosan / hyaluronan, hyaluronan / heparin, or cellulose, as well as chitin whiskers and platelet starch, hi some embodiments, the polysaccharide nanocrystals are derived from cellulose, starch, or chitin.

[0035] In some embodiments, the polysaccharide nanocrystals are derived from cellulose. In some embodiments, the polysaccharide nanocrystals are derived from starch. In some embodiments, the polysaccharide nanocrystals are derived from chitin.

[0036] In some embodiments, the polysaccharide nanocrystals can be spheres, rods, disks, or any other shape. In some embodiments, the nanocrystals used in the compositions of the present disclosure have a low particle size distribution. In some embodiments, low particle size distribution refers to nanocrystals or nanoparticles with a polydispersity index (PDI) of 0.5 or less. In some embodiments, the nanocrystals can be polydisperse and have a high size distribution. In some embodiments, high particle size distribution refers to nanocrystals or nanoparticles with a polydispersity index (PDI) of 0.6 or more, for example 1.0 or more.

[0037] In some embodiments, the polysaccharide nanocrystals contain, or are modified to contain, sulfonic acid groups and may be present as a sulfonate salt, such as the sodium salt.

[0038] Cellulose Nanoparticles The polysaccharide nanoparticles used in the nanocomposites of the present disclosure may be composed of or derived from cellulose. In some embodiments, the polysaccharide nanocrystals are derived from cellulose. The terms cellulose nanoparticles and nanocellulose are used interchangeably herein. Nanocellulose refers to nanostructured cellulose, which may include nanofibers or non-fibrils, nanocrystals, or other nano-sized structures. Cellulose is a polysaccharide (e.g., of the formula (C6Hi0O5)) composed of linear chains of P(1→4) linked D-glucose units. n (e.g., n is 100 to 100,000, e.g., 500 to 10,000). In some embodiments, the polysaccharide nanocrystal is a cellulose nanocrystal. The terms cellulose nanocrystal and nanocellulose crystal (NCC) are used interchangeably herein. An exemplary formula for unmodified cellulose is shown below:

[0039] [ka]

[0040] In some embodiments, cellulose nanocrystals, as a subset of cellulose nanoparticles, are highly ordered nanoscale crystals that remain after treatment to remove disordered amorphous regions from nanofibrils (the next member of the cellulose hierarchy).

[0041] In some embodiments, cellulose nanocrystals are crystals derived by subjecting cellulose fibers to a chemical treatment such as acid hydrolysis. In some embodiments, cellulose nanocrystals are derived from acid hydrolyzed cellulose from cellulosic biomass via an acid hydrolysis technique similar to that first described by Roanby, BG (Ranby, BG (1951) Descation Faraday Society, 11, 158-164). Nanocellulose crystals (NCC) produced via sulfuric acid treatment and neutralized with base (in this case NaOH) contain a large amount of sulfate and / or sulfonate substituents that affect dispersibility in hydrophilic media.

[0042] It is understood that the NCC used in the subject nanocomposites may be unmodified or modified, for example, by incorporating one or more substituents to replace or derivatize one or more of the three hydroxyl groups of one or more of the glucopyranose repeat units. In some cases, the NCC is sulfated (-OSOH). During sulfuric acid hydrolysis of cellulose, starch, or chitin, sulfate groups cover the surface of the nanocrystals. If hydrochloric acid is used instead, sulfate groups (or other substituents) can be attached to the nanocrystal surface later by esterification reaction with sulfuric acid. After HCl or HBr hydrolysis, the NCC may be unmodified. Further modification steps may be performed to add substituents, for example, amine-containing groups to provide surface cationization. After HPO hydrolysis, the NCC may be modified with phosphate (-OPOH). In some cases, after HCl / HBr hydrolysis and subsequent TEMPO-oxidation, the -CHOH hydroxyl may be converted to a carboxylic acid. In some embodiments, the NCC contains, or is modified to contain, a sulfonic acid substituent or a salt thereof (eg, a sulfonate salt).

[0043] Exemplary modifying units that can be incorporated into the glucopyranose repeat units at the surface of the NCC are shown below, where R is any convenient substituent, such as alkyl or substituted alkyl, alkanoyl or substituted alkanoyl, and the like.

[0044] [ka]

[0045] In some embodiments, the cellulose nanocrystals are derived from acid hydrolyzed cellulose from source wood, cotton, bacteria, or algae. In some cases, sulfuric acid is used for the acid treatment of the cellulose. NCCs of interest for use in the subject methods and compositions include those described by George et al. ("Cellulose nanocrystals: synthesis, functional properties, and applications", Nanotechnol Appl 2015;8:45-54), the disclosure of which is incorporated by reference.

[0046] In some embodiments, the incorporation of NCC toughens the resulting polybutylene succinate polymer composition (e.g., by making the product more fracture-resistant). In some embodiments, additives such as epoxy derivatives or epoxidized oils incorporated into the preparation process (e.g., as described herein) can toughen or reinforce the resulting polybutylene succinate (PBS) polymer composition, but can also simultaneously impart flexibility or desirable elasticity to the PBS polymer composition. In some embodiments, the use of a combination of NCC and epoxidized oil toughens the material, but makes it slightly softer or more elastic, for example, compared to a composition lacking epoxidized oil (e.g., as described herein).

[0047] In some embodiments, the acid hydrolyzed cellulose is obtained from naturally occurring cellulose fibers. In some embodiments, the acid hydrolyzed cellulose is obtained, for example, from plant biomass, vascular plants, cotton plants, wood pulp, jute, hemp, corn, frass, rice, wheat straw, or sisal. In some embodiments, the cellulose is obtained from plant biomass, including, but not limited to, trees, grasses, cotton, sisal, bamboo, and ramie.

[0048] In some embodiments, cellulose nanocrystals can be found as structural components in urochordates (sea creatures similar to sea cucumbers) and are produced naturally by the bacterium Acetobacter xylinum.

[0049] In some embodiments, the cellulose nanocrystals have an average dimension of about 1-80 nm in width and about 25-1000 nm in length. In some embodiments, the cellulose nanocrystals have an average dimension of about 1-100 nm in width and about 25-3000 nm in length. In some embodiments, the cellulose nanocrystals have an average dimension of about 10 nm or more, 15 nm or more, 20 nm or more, 25 nm or more, 30 nm or more, 35 nm or more, 40 nm or more, 45 nm or more, 50 nm or more, 55 nm or more, 60 nm or more, 65 nm or more, 70 nm or more, 75 nm or more, 80 nm or more, 85 nm or more, 90 nm or more, 95 nm or more, or 100 nm or more in width and 25 nm or more, 50 nm or more, 100 nm or more in length. m or more, 150 nm or more, 200 nm or more, 250 nm or more, 300 nm or more, 350 nm or more, 400 nm or more, 500 nm or more, 550 nm or more, 600 nm or more, 650 nm or more, 700 nm or more, 800 nm or more, 850 nm or more, 900 nm or more, 950 nm or more, 1000 nm or more, 1500 nm or more, 2000 nm or more, 2500 nm or more, or 3000 nm or more.

[0050] In some embodiments, the cellulose nanocrystals have average dimensions of about 3-50 nm width and about 100-1000 nm length.

[0051] In some embodiments, the cellulose nanocrystals have an average aspect ratio (length / diameter) that is 10 or more, e.g., 20 or more, 30 or more, 40 or more, 50 or more, 60 or more, 70 or more, 80 or more, 90 or more, 100 or more, 150 or more, 200 or more, or even more. In some embodiments, the cellulose nanocrystals have an average aspect ratio (length / diameter) that is 10-200, e.g., 20-200, 50-200, or 100-200.

[0052] In some embodiments, the nanocrystals in the dispersion have a particle size distribution in the range of about 1 d.nm to about 400 d.nm. In some embodiments, the nanocrystals in the dispersion have a particle size distribution in the range of about 1 d.nm to about 50 d.nm, about 50 d.nm to about 100 d.nm, about 100 d.nm to about 150 d.nm, about 150 d.nm to about 200 d.nm, 200 d.nm to about 250 d.nm, 250 d.nm to about 300 d.nm, 300 d.nm to about 350 d.nm, 350 d.nm to about 400 d.nm. In some embodiments, the nanocrystals in the dispersion have a particle size distribution in the range of about 1 d.nm to about 20 d.nm. In some embodiments, the nanocrystals in the dispersion have a particle size distribution in the range of about 10 d.nm to about 100 d.nm. In some embodiments, the nanocrystals in the dispersion have a particle size distribution in the range of about 10 d.nm to about 30 d.nm. In some embodiments, the nanocrystals in the dispersion have a particle size distribution in the range of about 100 d.nm to about 200 d.nm. In some embodiments, the nanocrystals in the dispersion have a particle size distribution in the range of about 1 d.nm to about 200 d.nm. In some embodiments, the nanocrystals in the dispersion have a particle size distribution in the range of about 1 d.nm or more, 2 d.nm or more, 4 d.nm or more, 6 d.nm or more, 8 d.nm or more, 10 d.nm or more, 12 d.nm or more, 14 d.nm or more, 16 d.nm or more, 18 d.nm or more, 20 d.nm or more, 22 d.nm or more, 24 d.nm or more, 26 d.nm or more, 28 d.nm or more, 30 d.nm or more, 32 d.nm or more, 34 d.nm or more, 36 d.nm or more, 38 d.nm or more, 40 d.nm or more, 42 d.nm or more, 44 d.nm or more, 46 d.nm or more, 48 d.nm or more, 50 d.nm or more, 52 d.nm or more, 54 d.nm or more, 56 d.nm or more, 5 ...0 d.nm or more, 50 d.nm or more The particle size distribution is 0 d.nm or more, 52 d.nm or more, 54 d.nm or more, 56 d.nm or more, 58 d.nm or more, 60 d.nm or more, 62 d.nm or more, 64 d.nm or more, 66 d.nm or more, 68 d.nm or more, 70 d.nm or more, 72 d.nm or more, 74 d.nm or more, 76 d.nm or more, 78 d.nm or more, 80 d.nm or more, 82 d.nm or more, 84 d.nm or more, 86 d.nm or more, 88 d.nm or more, 90 d.nm or more, 92 d.nm or more, 94 d.nm or more, 96 d.nm or more, 98 d.nm or more, or 100 d.nm or more.In some embodiments, the nanocrystals in the dispersion have a diameter of 100 d.nm or more, 125 d.nm or more, 150 d.nm or more, 175 d.nm or more, 200 d.nm or more, 225 d.nm or more, 250 d.nm or more, 275 d.nm or more, 300 d.nm or more, 325 d.nm or more, 350 d.nm or more, 400 d.nm or more, 425 d.nm or more, 500 d.nm or more, 525 d.nm or more, 550 d.nm or more, 575 d.nm or more, .nm or more, 600d.nm or more, 625d.nm or more, 650d.nm or more, 675d.nm or more, 700d.nm or more, 725d.nm or more, 750d.nm or more, 775d.nm or more, 800d.nm or more, 825d.nm or more, 850d.nm or more, 875d.nm or more, 900d.nm or more, 925d.nm or more, 950d.nm or more, 975d.nm or more, or 1000d.nm or more.

[0053] In some embodiments, increasing the length of the cellulose nanocrystals increases the load distribution potential throughout the polymer compared to shorter length cellulose nanocrystals, hi some embodiments, the relative orientation of the cellulose nanocrystals within the polymer can provide desirable alignment and interfacial contact between adjacent cellulose nanocrystals in an axial orientation, providing the ultimate tensile strength of the resulting composition that can be increased compared to compositions lacking such aligned nanocrystals.

[0054] The morphology (e.g., length, aspect ratio, length, polydispersity) and surface charge of cellulose nanocrystals vary greatly based on synthesis conditions. In some embodiments, acid hydrolysis is used to break down cellulose microfibrils by digesting the amorphous regions that connect the cellulose nanocrystals. In some embodiments, processing typically requires heating, agitation, rinsing, filtration, dialysis, and ultrasonication, with the parameters of each step having a direct effect on the morphology and / or surface chemistry of the cellulose nanocrystals. In some embodiments, the end result of cellulose nanocrystal processing includes a suspension of liquid crystalline cellulose nanocrystals that are produced, forming either a nematic or chiral nematic mesophase (mesophase) (e.g., depending on the length, aspect ratio, length, polydispersity, surface charge, nanocrystalline cellulose (NCC) concentration, and electrolyte concentration of the cellulose nanocrystals).

[0055] In some embodiments, cellulose nanocrystals enhance one or more mechanical properties of the polymer base resin. Non-limiting properties that may be improved by incorporating cellulose nanoparticles into the base polymer resin may be selected from at least one of the following: modulus of elasticity, tensile yield stress, hoop stress rating, flexural modulus, UV resistance, and reduced gas permeability. Thus, the present disclosure allows for measurable enhancement of performance to be achieved without significant loss of other desirable properties such as tensile strength, ultimate elongation, melt index, thermal stability, impact strength, slow crack growth resistance, and rapid crack propagation resistance.

[0056] Aspects of the subject disclosure include the preparation of nanocomposites in which polymer chains can be grafted to polysaccharide nanoparticles, such as cellulose nanocrystals, for example, via ester linkages to hydroxyl groups of the polysaccharide.

[0057] Chitosan Nanoparticles The polysaccharide nanoparticles used in the nanocomposites of the present disclosure may be composed of or derived from chitosan. Chitosan, a deacetylated derivative of chitin, is a natural biodegradable polysaccharide polymer that is a non-toxic, sustainable, natural antimicrobial agent. The use of chitosan nanoparticles can impart several desirable properties to the resulting composition, such as flame retardancy, antimicrobial properties, and enhanced biodegradability.

[0058] In some embodiments, the polysaccharide nanocrystals are derived from chitosan, a polysaccharide (e.g., of the formula (CH)) composed of randomly distributed β-(1→4) linked D-glucosamine (deacetylated unit) and N-acetyl-D-glucosamine (acetylated unit). 11 No. 4) n ) In some embodiments, the polysaccharide nanocrystals are chitosan nanocrystals. An exemplary formula for unmodified chitosan containing free amine groups is shown below: It is understood that depending on the degree of deacetylation present, a few percent of the amine groups may be N-acetylated.

[0059] [ka]

[0060] The primary alcohol and / or amine groups of chitosan may participate in branching reactions with carboxylic acid groups and / or epoxides during the polymerization and / or capping process of the present disclosure.

[0061] In some embodiments, chitosan is derived from marine crustaceans, such as, but not limited to, shrimp shells. Commercially, chitosan is produced by deacetylation of chitin, which is the structural element in the exoskeleton of crustaceans.

[0062] In some embodiments, mixtures of two or more types of polysaccharide nanoparticles may be utilized in the subject compositions and methods.

[0063] In some embodiments, chitosan nanoparticles are the only type of polysaccharide nanoparticle utilized. In some embodiments, chitosan nanoparticles are utilized in a mixture with nanocrystalline cellulose (NCC) as the polysaccharide nanoparticle of the subject compositions and methods. In some examples, the polysaccharide nanoparticle mixture is 50:50 weight percent chitosan to NCC. In some embodiments, chitosan nanoparticles are greater than 50 weight percent of the polysaccharide nanoparticle mixture. In some embodiments, NCC is greater than 50 weight percent of the polysaccharide nanoparticle mixture.

[0064] Polyester Polymer The nanocomposites of the present disclosure are based on polyester polymers. The term polyester polymer refers to a polymer that includes multiple repeat units linked via ester linkages. In some embodiments, the ester linkages are formed between an aliphatic diol comonomer and an aliphatic diacid comonomer. The polyester polymers of the nanocomposites of interest can be biodegradable. The exact components of the polyester polymer can be selected to provide the desired properties for the resulting nanocomposite.

[0065] The term "unit" refers to a structural subunit of a polymer. The term unit is meant to include monomers, comonomers, coblocks, segments, repeat units, and the like. A "repeat unit" is a subunit of a polymer defined by the minimum number of distinct structural features required for the unit to be considered a monomer, such that when the unit is repeated n times, the resulting structure represents a polymer or a block thereof. In some cases, a polymer may include two or more different repeat units, e.g., if the polymer is a multiblock polymer, each block may define a distinct repeat unit. In some cases, the repeat unit of a polymer includes a single monomer group. In certain instances, the repeat unit of a polymer includes two or more monomer groups, i.e., two, three, four or more comonomer groups, and the like.

[0066] The term "comonomer" or "comonomer group" refers to a structural unit of a polymer that may itself be part of a repeat unit of the polymer. In some embodiments, the polyester polymer comprises a block copolymer composed of blocks of polymerized monomers. In such cases, the block copolymer may be described as having separate repeat units, each corresponding to a separate coblock of the polymer. In some cases, the polymer is a diblock copolymer, containing two different coblocks. In such cases, the polymer may be described as comprising coblocks, and each coblock may be composed of one, two, three or more comonomers, etc.

[0067] In some embodiments, the nanocomposite comprises a polyester polymer comprising a repeat unit of formula (I):

[0068] [ka]

[0069] During the ceremony, L 1 and L 2 are each independently a linking group 2 to 12 atoms in length; p is 1 to 100,000; each * independently represent H, OH, alkyl, alkoxy, alkanoyl, aroyl, heteroaroyl, aryloxy, heteroaryloxy, capping group, copolymer segment, repeat unit, comonomer, grafted polysaccharide nanoparticle, linker, crosslinker, or epoxidized oil, epoxy derivative, or fatty acid.

[0070] L 1 and L 2can be any convenient divalent linking group having a chain length of 2 to 12 atoms, e.g., 2, 3, 4, 5, 6, 8, 10, or 12 carbon atoms, and the linker can be linear, branched, or cyclic. In certain cases, 1, 2, 3, 4, or 5 or more carbon atoms in the linking group backbone can be optionally substituted with sulfur, nitrogen, or oxygen heteroatoms. The bonds between the backbone atoms can be saturated or unsaturated (e.g., alkenyl), and in some cases, one, two, or up to three unsaturated bonds are present in the linker backbone. The linker can include one or more substituents, e.g., with alkyl, aryl, or alkenyl groups. Linkers can include, but are not limited to, polyethylene glycol; ether, thioether, tertiary amine, alkenyl, alkyl (which may be linear or branched, e.g., methyl, ethyl, n-propyl, 1-methylethyl (isopropyl), n-butyl, n-pentyl, 1,1-dimethylethyl (t-butyl), and the like. In some embodiments of Formula (I), L 1 and L 2 are each independently selected from alkyl, substituted alkyl, alkenyl, and substituted alkenyl.

[0071] "Alkylene" refers to a divalent aliphatic hydrocarbyl group (e.g., alkyl or alkenyl), preferably having 2 to 12, more preferably 2 to 6 carbon atoms, either straight chain or branched, and optionally interrupted with one or more groups selected from -O-, -NR10-, NRC(O)-, -C(O)NR10-, and the like. This term includes, by way of example, methylene (CH2), ethylene (CH2CH2), n-propylene (CH2CH2CH2), iso-propylene (CH2CH(CH3)), (C(CH3)2CH2CH2), (C(CH3)2CH2C(O)), (C(CH3)2CH2C(O)NH), (CH(CH3)CH2-), and the like. "Substituted alkylene" refers to an alkylene group having one to three hydrogens replaced with a substituent.

[0072] In some embodiments of Formula (I), p is 2 to 100,000. In some embodiments of Formula (I), p is 5 to 100,000. In some embodiments of Formula (I), p is 10 to 100,000. In some embodiments of Formula (I), p is 100 to 100,000. In some embodiments of Formula (I), p is 1000 to 100,000.

[0073] In some embodiments of formula (I), p is 2 to 10,000. In some embodiments of formula (I), p is 5 to 10,000. In some embodiments of formula (I), p is 10 to 10,000. In some embodiments of formula (I), p is 100 to 10,000. In some embodiments of formula (I), p is 1000 to 10,000. In some embodiments of formula (I), p is 2 to 1,000. In some embodiments of formula (II), p is 5 to 1,000. In some embodiments of formula (I), p is 10 to 1,000. In some embodiments of formula (I), p is 100 to 1000.

[0074] Any convenient polymer, and / or monomer precursor thereof, may be adapted for incorporation into the subject preparation methods to provide nanocomposite compositions having desirable physical properties (e.g., as described herein, such as tensile strength). Polymers of interest and monomer precursors thereof that may be adapted for use in the subject preparation methods and nanocomposite compositions include, but are not limited to, the polymers and monomers described in Zheng et al. (Ind. Eng. Chem. Res. 2013, 52, 6147-6155), Tserki et al. (Polymer Degradation and Stability, Volume 91, Issue 2, February 2006, 367-376), U.S. Patent Application Publication No. 20190194400, and U.S. Patent No. 9,796,849, the disclosures of which are incorporated herein by reference in their entireties.

[0075] In some embodiments, the polyester polymer-polysaccharide nanocomposite resin is derived from a mixture comprising polysaccharide nanocrystals, alkanediol monomers, and alkanedioic acid monomers. Aspects of the subject disclosure include the preparation of nanocomposites via polymerization reactions in which polysaccharide nanoparticles, such as cellulose nanocrystals, are present during polymerization to allow for the grafting of polymer chains to the polysaccharide, for example, via ester linkages to hydroxyl groups of the polysaccharide.

[0076] In some embodiments, the polysaccharide nanocrystals, alkanediol monomers, and alkanedioic acid agent monomers are polymerized (eg, esterified and polycondensed) in the dispersion to produce a polyester polymer-polysaccharide nanocomposite resin.

[0077] In some embodiments, the polyester polymer of the polymer-polysaccharide nanocomposite resin is an aliphatic polyester polymer. In some cases, the polyester polymer is biodegradable. In some embodiments, the polymer comprises a polybutylene succinate homopolymer or copolymer. In some embodiments, the polymer comprises poly(butylene succinate-co-butylene adipate).

[0078] The polyester polymer may include one or more additional comonomers incorporated into the polymer to provide certain desired properties.

[0079] In some embodiments, the aliphatic polyester polymer may comprise segments of specific aliphatic polyester polymers selected from, but not limited to, polylactide (PLA) (e.g., poly(lactic acid)), polyglycolide (PGA) (e.g., polyglycolic acid), poly(ε-caprolactone) (PCL), poly(γ-valerolactone) (PVL), and copolymer poly(lactic-co-glycolic acid) (PLGA).

[0080] PLA is a biodegradable, hydrophobic polymer synthesized from lactic acid.

[0081] PCL is a semi-crystalline polyester, typically with a melting temperature of about 55-60°C.

[0082] PGA is a highly crystalline polymer, typically with a melting point above 200°C and a glass transition temperature of about 35-40°C.

[0083] PLGA can be fabricated with different ratios of its monomers, lactide and glycolide, allowing for tunable degradation and release rates.

[0084] In some embodiments, the nanocomposite comprises a polyester polymer comprising a repeat unit of formula (II):

[0085] [ka]

[0086] During the ceremony, n is 1 to 11; m is 1 to 11; p is 1 to 100,000; each * independently represent H, OH, alkyl, alkoxy, alkanoyl, aroyl, heteroaroyl, aryloxy, heteroaryloxy, capping group, copolymer segment, repeat unit, comonomer, grafted polysaccharide nanoparticle, linker, crosslinker, or epoxidized oil, epoxy derivative, or fatty acid.

[0087] In some embodiments of Formula (II), n is 1-5 and m is 1-5.

[0088] In some embodiments of Formula (II), n is 1. In some embodiments of Formula (II), n is 2. In some embodiments of Formula (II), n is 3. In some embodiments of Formula (II), n is 4. In some embodiments of Formula (II), n is 5.

[0089] In some embodiments of Formula (II), m is 2 to 5. In some embodiments of Formula (II), m is 2. In some embodiments of Formula (II), m is 3. In some embodiments of Formula (II), m is 4. In some embodiments of Formula (II), m is 5.

[0090] In some embodiments of Formula (II), n is 1 and m is 3.

[0091] In some embodiments of Formula (II), p is 2 to 100,000. In some embodiments of Formula (II), p is 5 to 100,000. In some embodiments of Formula (II), p is 10 to 100,000. In some embodiments of Formula (II), p is 100 to 100,000. In some embodiments of Formula (II), p is 1000 to 100,000.

[0092] In some embodiments of Formula (II), p is 2 to 10,000. In some embodiments of Formula (II), p is 5 to 10,000. In some embodiments of Formula (II), p is 10 to 10,000. In some embodiments of Formula (II), p is 100 to 10,000. In some embodiments of Formula (II), p is 1000 to 10,000.

[0093] In some embodiments of Formula (II), p is 2 to 1,000. In some embodiments of Formula (II), p is 5 to 1,000. In some embodiments of Formula (II), p is 10 to 1,000. In some embodiments of Formula (II), p is 100 to 1000.

[0094] In some embodiments of formula (I)-(II), at least one * represents a grafted polysaccharide nanoparticle. In some embodiments of formulas (I)-(II), at least one * represents a grafted cellulose nanoparticle. In some embodiments of formulas (I)-(II), at least one* represents the grafted cellulose nanocrystals.

[0095] In some embodiments of formula (I)-(II), at least one * represents a capping group. A capping group is a group that contains a compatible functional group suitable for attachment to a hydroxy or carboxylic acid terminus of a polymer segment. Exemplary capping groups include alkanoyl groups that form an ester linkage to the hydroxy terminus and alkoxy groups that form an ester linkage to the carboxylic acid terminus. A variety of chemical linkages and capping groups can be utilized. In some embodiments of formulas (I)-(II), at least one * represents a link to an epoxidized oil, an epoxy derivative, or a fatty acid. The epoxidized oil may have one or more epoxide groups suitable for coupling to a reactive group of a polyester polymer, for example, an end group such as a carboxylic acid to form an ester linkage to the epoxidized oil, or an end group such as a hydroxyl to form an ether linkage. When the epoxidized oil has two or more epoxide reactive groups, it may provide crosslinking between two or more polyester polymers. In some cases, a fatty acid may be used to cap the polyester polymer via an ester linkage to a hydroxyl end group.

[0096] In some embodiments of formula (I)-(II), at least one * represents a comonomer, copolymer segment, or repeat unit (e.g., as described herein), such that the polyester polymer is a copolymer (e.g., as described herein). It is understood that such a copolymer may be a random copolymer or a block copolymer.

[0097] In some embodiments, the polyester polymer-polysaccharide nanocomposite resin comprises a diol monomer HO-L 2 The polymer comprises repeat units based on —OH, wherein L 2 is as defined in formula (I). 2is alkyl or substituted alkyl. 2 is alkenyl or substituted alkenyl.

[0098] Alkanediol Monomers In some aspects, the polyester polymer-polysaccharide nanocomposite resin comprises polymer repeat units based on alkanediol monomers. Alkanediol monomers refer to linear or branched alkyl groups (e.g., HO-alkyl-OH) having terminal hydroxyl groups. The alkanediol monomers can have a C2-C12 chain connecting the terminal hydroxyl groups. The alkanediol monomers can be unsubstituted or substituted with one or more substituents. In some embodiments, the alkyl group comprises 1-10 carbon atoms. In certain embodiments, the alkyl group comprises 1-6 carbon atoms, e.g., 1-4 carbon atoms. This term includes, by way of example, straight chain and branched hydrocarbyl groups such as ethyl (CH3CH2), n-propyl (CH3CH2CH2-), isopropyl ((CH3)2CH-), n-butyl (CH3CH2CH2CH2), isobutyl ((CH3)2CHCH2), sec-butyl ((CH3)(CH3CH2)CH-), t-butyl ((CH3)3C-), n-pentyl (CH3CH2CH2CH2CH2-), and neopentyl ((CH3)3CCH2-).

[0099] The term "substituted alkyl" refers to an alkyl group, as defined herein, wherein one or more carbon atoms in the alkyl chain are optionally replaced with a heteroatom, such as O-, N-, S-, -S(O)n- (where n is 0-2), -NR- (where R is hydrogen or alkyl), and includes alkoxy, substituted alkoxy, cycloalkyl, substituted cycloalkyl, cycloalkenyl, substituted cycloalkenyl, acyl, acylamino, acyloxy, amino, aminoacyl, aminoacyloxy, oxyaminoacyl, azido, cyano, halogen, hydroxyl, oxo, thioketo, carboxyl, carboxylalkyl, thioaryloxy, thioheteroaryloxy, thio ... and -NRaRb, wherein Ra and Rb may be the same or different and are selected from hydrogen, optionally substituted alkyl, cycloalkyl, alkenyl, cycloalkenyl, alkynyl, aryl, heteroaryl, and heterocyclic.

[0100] In some embodiments, the alkanediol monomers are selected from 1,4-butanediol monomers, 1,2-ethanediol monomers, 1,3-propanediol monomers, 1,5-pentanediol monomers, or 1,6-hexanediol monomers.

[0101] In some embodiments, the alkanediol monomer includes one or more diols to form a polyester composite.Non-limiting examples of other suitable diols include, but are not limited to, ethylene glycol, 1,3-propylene glycol, neopentyl glycol, 1,6-hexamethylene glycol, 1,4-cyclohexanedimethanol, hydroquinone, 1.5-dihydroxynaphthalene, 4,4'-dihydroxydiphenyl, bis(p-hydroxyphenyl)methane, bis(p-hydroxyphenyl)-2.2-propane, and combinations thereof.

[0102] In some embodiments, the alkanediol monomer 1,4-butanediol.

[0103] In some embodiments, the alkanediol monomer is 1,2-ethanediol.

[0104] In some embodiments, the alkanediol monomer is 1,3-propanediol.

[0105] In some embodiments, one or more additional components may be added along with one or more other diols or substituted for 1,4-butanediol to form a polyester composite.

[0106] Other non-limiting examples of suitable diols include, but are not limited to, ethylene glycol, 1,3-propylene glycol, neopentyl glycol, 1,6-hexamethylene glycol, 1,4-cyclohexanedimethanol, hydroquinone, 1.5-dihydroxynaphthalene, 4,4'-dihydroxydiphenyl, bis(p-hydroxyphenyl)methane, bis(p-hydroxyphenyl)-2.2-propane, and combinations thereof.

[0107] In some embodiments, polyethers having hydroxyl end groups can be used in combination with the diols of the present disclosure. In some embodiments, the polyethers having hydroxyl end groups have a carbon number of typically 4 or more, with a lower limit of 10 or more, and typically 1,000 or less, 200 or less, or even 100 or less. Non-limiting examples of polyethers having hydroxyl end groups include, but are not limited to, diethylene glycol, triethylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, poly-1,6-hexamethylene glycol, and the like. Also, copolymer polyethers of polyethylene glycol and polypropylene glycol, and the like, can be used.

[0108] Alkanedioic acid monomer The polyester polymer-polysaccharide nanocomposite includes a polymer repeat unit based on a diacid monomer (e.g., of the formula HO2C-L 1 -CO2, or a derivative or equivalent thereof, wherein L 1 is as defined in formula (I). The polyester polymer-polysaccharide nanocomposite comprises polymer repeat units based on alkanedioic acid monomers. Alkanedioic acid monomers refer to linear or branched alkyl groups having terminal hydroxyl groups. Alkanedioic acid monomers can have C2-C12 alkyl chains linking terminal carboxylic acid or ester groups, or equivalent functional groups. Alkanedioic acid monomers can be unsubstituted or substituted with one or more substituents. In some embodiments, the alkyl group comprises 1-10 carbon atoms. In certain embodiments, the alkyl group comprises 1-6 carbon atoms, such as 1-4 carbon atoms. It is understood that the diacid group of the monomers is typically provided in a derivative form suitable for polymerization with hydroxyl-containing comonomers. In some embodiments, when the alkanedioic acid monomers are provided in the form of esters or cyclic anhydrides, the monomers are capable of transesterification with hydroxyl-containing monomers, for example, alkanediol monomers.

[0109] In some embodiments, the alkanedioic acid agent monomer is selected from succinic acid, monoalkyl succinates, dialkyl succinates (e.g., dimethyl adipate or diethyl adipate), succinic anhydride, adipic acid, monoalkyl adipates, dialkyl adipates (e.g., dimethyl adipate or diethyl adipate), and adipic anhydride.

[0110] In some embodiments, the alkanedioic acid monomer is selected from oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, suberic acid, sebacic acid, cyclohexanedicarboxylic acid, and their cyclic anhydride equivalents. In certain embodiments, the succinate derivative is replaced or added with one or more additional components. In some embodiments, these one or more additional components include one or more dicarboxylic acids or dicarboxylic anhydrides. Non-limiting examples include, but are not limited to, fumaric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, suberic acid, sebacic acid, cyclohexanedicarboxylic acid, and their cyclic anhydride equivalents.

[0111] In some embodiments, the polyester polymer comprises repeat units based on an aliphatic diacid comonomer (e.g., as described herein). In certain embodiments, the aliphatic diacid comonomer is fumaric acid.

[0112] Polybutylene succinate or fumarate polymers and copolymers In some embodiments, the polyester polymer-polysaccharide nanocomposite resin comprises polysaccharide nanocrystals, alkanediol monomers, and diacid agent monomers.

[0113] In some embodiments, the alkane diol monomer is a 1,4-butane diol monomer. In some embodiments, the alkane diacid agent monomer is a succinic acid agent monomer. In some embodiments, the alkane diacid agent monomer is succinic anhydride.

[0114] Aliphatic homopolyesters and copolyesters can be prepared from 1,4 butanediol and succinic acid agent monomers (e.g., succinic anhydride or dimethyl ester of succinic acid), and optionally one or more other comonomers (e.g., as described herein), by polymerization processes of esterification, transesterification, and / or polycondensation. In some embodiments, the process is carried out as two separate steps, e.g., using different reaction conditions, e.g., specific conditions of temperature and / or pressure. In some embodiments, the process is carried out as a single step. The process can be carried out in a single reaction vessel. Similarly, an alkenyl diacid monomer, such as a fumaric acid monomer, e.g., maleic anhydride, can be utilized with a 1,4-butanediol monomer to produce a polybutylene fumarate (PBF) homopolymer or copolymer for use in the subject nanocomposites.

[0115] In some embodiments, a mixture comprising polysaccharide nanocrystals, 1,4-butanediol monomers, and succinic acid agent monomers (optionally in the presence of one or more additional comonomers) is polymerized (e.g., esterified and / or polycondensed) to produce a polymer-polysaccharide nanocomposite resin.

[0116] In some embodiments, the polysaccharide nanocrystals, alkanediol monomers, and alkanedioic acid agent monomers are polymerized in a single step to produce a first resin material. The first resin material can then be pelletized and dried under conditions sufficient to increase the MW of the polymer in the first resin material to produce a polyester polymer-polysaccharide nanocomposite resin. In some embodiments, pelletizing and / or drying the polymerization product of the polysaccharide nanocrystals, alkanediol monomers, and alkanedioic acid agent monomers removes moisture from the mixture and increases the molecular weight of the polymer in the mixture or resin.

[0117] In some embodiments, the polymer of the polymer-polysaccharide nanocomposite resin is a polybutylene succinate (PBS) homopolymer or a polybutylene succinate copolymer.

[0118] In some embodiments, the polymer of the polymer-polysaccharide nanocomposite resin is a polybutylene succinate copolymer.

[0119] In some embodiments, the polybutylene succinate copolymer is butylene fumarate or a polymer blend of PBS and polybutylene fumarate (PBF). In some embodiments, the polybutylene succinate copolymer is represented by formula (III):

[0120] [ka]

[0121] In the formula, p, q, and r are independently 1 to 100,000; * independently represent H, OH, alkyl, alkoxy, alkanoyl, aroyl, heteroaroyl, aryloxy, heteroaryloxy, capping group, copolymer segment, repeat unit, comonomer, grafted polysaccharide nanoparticle, linker, crosslinker, or epoxidized oil, epoxy derivative, or fatty acid.

[0122] In some embodiments of Formula (III), p and q are independently 2 to 100,000. In some embodiments of Formula (III), p and q are independently 5 to 100,000. In some embodiments of Formula (III), p and q are independently 10 to 100,000. In some embodiments of Formula (III), p and q are independently 100 to 100,000. In some embodiments of Formula (III), p and q are independently 1000 to 100,000.

[0123] In some embodiments of formula (III), p and q are independently 2 to 10,000. In some embodiments of formula (III), p and q are independently 5 to 10,000. In some embodiments of formula (III), p and q are independently 10 to 10,000. In some embodiments of formula (III), p and q are independently 100 to 10,000. In some embodiments of formula (III), p and q are independently 1000 to 10,000. In some embodiments of formula (III), p and q are independently 2 to 1,000. In some embodiments of formula (III), p and q are independently 5 to 1,000. In some embodiments of formula (III), p and q are independently 10 to 1,000. In some embodiments of formula (III), p and q are independently 100 to 1000.

[0124] In some embodiments of Formula (III), r is 1 to 10,000. In some embodiments of Formula (III), r is 1 to 1,000. In some embodiments of Formula (III), r is 1 to 100. In some embodiments of Formula (III), r is 1 to 10.

[0125] It is understood that the polybutylene succinate copolymer can include any convenient arrangement of comonomers, such as a coblock or random arrangement. In some embodiments, the polybutylene succinate copolymer is represented by formula (IV):

[0126] [ka]

[0127] where x, y, and z represent the mol % of the comonomer in the polymer.

[0128] In some embodiments, x, y, and z are each independently 1-50 mol%. In some cases, y is x+z. In some embodiments, x>z. In some embodiments, z>x.

[0129] In some embodiments, the polybutylene succinate copolymer has an average MW of from 10 kDa to 100 kDa, for example from 10 kDa to 50 kDa or from 20 kDa to 40 kDa.

[0130] In some embodiments, adding a fumarate moiety extends the crystalline melt temperature of PBS by up to 10° C.-15° C. For example, PBS has a melt temperature of about 115° C., which can hinder processability in the melt in yarn / fabric production as well as yarn / fabric applications. Pure PBF has a melt temperature of about 139° C. In some embodiments, PBF acts as a polymer nucleating agent when blended with succinate-derived polyesters, enhancing the crystallization rate.

[0131] In some embodiments, the polybutylene succinate copolymer is diethylene glycol succinate. In some embodiments, diethylene glycol (DEG) can be replaced with triethylene glycol, 1,3 propanediol, sorbitol, or xylitol. In some embodiments, the introduction of a hydrophilic backbone creates a better substrate for certain bacteria and fungi to attach to, allowing aerobic / anaerobic degradation processes to occur. In some embodiments, the introduction of an asymmetric backbone reduces crystallinity and improves biodegradability. PBS is hydrophobic and highly crystalline, limiting the ease of degradation in certain aquatic and terrestrial environments.

[0132] In some embodiments, the polybutylene succinate copolymer is polypropylene oxide succinate. The introduction of poly(1,3 propylene oxide) polyol allows for the formation of phase-separated soft segments in the copolymer to create a thermoplastic polyester elastomer (TPPE). The molecular weight of the polyol can range from 500 to 2700 g / mol. In some embodiments, polytetramethylene oxide (PTMO) or polyethylene glycol (PEG) polyols of similar molecular weight can also be used. In some embodiments, fumaric acid can be included in the copolymer. In some embodiments, fumaric acid can be introduced to increase crystallinity and induce better phase separation of the hard (PBS) and soft (PPOS) segments.

[0133] In some embodiments, polybutylene succinate copolymer is phenyl ethylene succinate. In some embodiments, tyrosol can be replaced with homovanillyl alcohol, coniferyl alcohol, or vanillyl alcohol. For example, the introduction of naturally occurring aryl hydroxy acid increases the strength and durability of polybutylene succinate.

[0134] In some embodiments, the polybutylene succinate copolymer is butylene coumarate. In some embodiments, p-coumaric acid is replaced with ferulic acid, phloretic acid, syringic acid, sinapic acid, or caffeic acid. For example, the introduction of hydroxycinnamic acid derivatives increases the strength and melting point of PBS.

[0135] Succinic Acid Monomer In some embodiments, the alkanedioic acid agent monomer is a succinic acid agent monomer or a derivative thereof. In some embodiments, the alkanedioic acid agent monomer is a succinic acid agent monomer. In some embodiments, the succinic acid agent is succinic anhydride.

[0136] In some embodiments, succinic acid agent monomers include, but are not limited to, succinic acid agents selected from succinic acid, monoalkyl succinates, dialkyl succinates (e.g., dimethyl succinate or diethyl succinate), or succinic anhydride.

[0137] In some embodiments, the succinic acid agent is a succinate derivative. In some embodiments, the succinate derivative is succinate anhydride. In some embodiments, succinic anhydride enhances the rate of esterification with 1,4 butanediol and also reduces the amount of harmful THF generated during the esterification process compared to polymer-polysaccharide nanocomposite resins that do not contain succinic anhydride. However, other suitable non-limiting examples of succinate derivatives may include succinic acid or succinate esters.

[0138] Additives Various additives can be included during polymerization of the monomeric agents to impart desirable physical properties or characteristics to the resulting polymer-polysaccharide nanocomposite resin. The additives can be comonomers, capping agents, epoxy derivatives, oils (e.g., epoxidized oils), pigments, crosslinking agents, and the like. Thus, in some embodiments, the polymer-polysaccharide nanocomposite resin includes one or more additional comonomers, additive components, and / or capping agents. The additives added to the reaction mixture can be covalently or non-covalently incorporated into the resulting polymer-polysaccharide nanocomposite resin. In some examples, the additives can form covalent bonds with chemical groups on the growing polymer, such as terminal hydroxy or carboxylic acid type groups, or compatible linking groups of the crosslinking agent. In other examples, the additives are non-covalently incorporated into the resin composition to impart desirable physical properties (e.g., as described herein).

[0139] In some embodiments, the polymer-polysaccharide nanocomposite comprises one or more additional monomers or components, such as, but not limited to, comonomers, capping groups, epoxy derivatives, oils, pigments, crosslinkers, and the like.

[0140] In some embodiments, the one or more additional monomers include an additional alkanediol monomer and / or an additional diacid monomer.

[0141] In some embodiments, the additional alkanediol monomers include, but are not limited to, 1,4-butanediol monomers, 1,2-ethanediol monomers, 1,3-propanediol monomers, 1,5-pentanediol monomers, or 1,6-hexanediol monomers.

[0142] In some embodiments, additional diacid agent monomers include, but are not limited to, succinic acid, monoalkyl succinates, dialkyl succinates (e.g., dimethyl adipate or diethyl adipate), succinic anhydride, adipic acid, monoalkyl adipates, dialkyl adipates (e.g., dimethyl adipate or diethyl adipate), and adipic anhydride.

[0143] In some embodiments, the additional alkanedioic acid agent monomer comprises adipic anhydride.

[0144] In some embodiments, the one or more additional components may include a hydrophobic agent. In some embodiments, the hydrophobic agent is an oil. In some embodiments, the hydrophobic agent is an elastomeric material. In some embodiments, the hydrophobic agent is epoxidized soybean oil or an elastomeric material.

[0145] In some embodiments, the one or more additional components include, but are not limited to, agents to provide additional water and may include oxygen barrier properties. Non-limiting exemplary water and oxygen barrier agents include candelilla wax, beeswax, and other waxes. In some embodiments, such barrier agents are derived from renewable resources.

[0146] In some embodiments, one or more additional components are non-covalent plasticizers. Plasticizers are additives used to impart flexibility to polymer blends and improve their processability. Any known non-covalent plasticizer can be included as one or more additional components.

[0147] In some embodiments, the one or more additional components include a polishing agent that provides an aesthetically pleasing shine to the finished product. Non-limiting exemplary polishing agents include shea butter and nut oils such as Brazil nut oil. In some embodiments, the polishing agent is derived from a renewable resource.

[0148] In some embodiments, the one or more additional components include, but are not limited to, impact modifiers, antioxidants, antibacterial agents, antifungal agents, antistatic agents, fillers, heat stabilizers, UV stabilizers, dyes, fillers, crystallization enhancers, and coupling agents.

[0149] Non-limiting examples of antioxidants include hindered phenol antioxidants such as p-tert-butylhydroxytoluene and p-tert-butylhydroxyanisole, sulfur antioxidants such as distearyl thiodipropionate and dilauryl thiodipropionate, etc. Heat stabilizers include triphenyl phosphite, trilauryl phosphite, trisnonylphenyl phosphite, etc. UV stabilizers include p-tert-butylphenyl salicylate, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxy-2'-carboxybenzophenone, 2,4,5-trihydroxybutyrophenone, etc. Lubricants include calcium stearate, zinc stearate, barium stearate, sodium palmitate, etc. Antistatic agents include N,N-bis(hydroxyethyl)alkylamines, alkylamines, alkylarylsulfonates, alkylsulfonates, etc. Flame retardants include hexabromocyclododecane, tris-(2,3-dichloropropyl)phosphate, pentabromophenyl allyl ether, etc. Antiblocking agents include inorganic fillers such as silica and combinations of oleamide, etc. Inorganic fillers or nucleating agents include calcium carbonate, silica, titanium oxide, talc, mica, barium sulfate, alumina, a mixture of NaHCO3 and citric acid, etc. Crystallization accelerators include polyethylene terephthalate, poly-transcyclohexane dimethanol terephthalate, etc. Organic fillers include wood flour, rice husks, waste paper such as newspapers, starch (including modified materials such as alpha starch), cellulose, etc.

[0150] In some embodiments, polyethers having hydroxyl end groups can be used in combination with the diols disclosed in the present disclosure. For polyethers having hydroxyl end groups, the carbon number has a lower limit of usually 4 or more, preferably 10 or more, and an upper limit of usually 1,000 or less, preferably 200 or less, more preferably 100 or less. Non-limiting examples of polyethers having hydroxyl end groups include, but are not limited to, diethylene glycol, triethylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, poly-1,6-hexamethylene glycol, and the like. Also, copolymer polyethers of polyethylene glycol and polypropylene glycol, and the like, can be used.

[0151] In some embodiments, the one or more additional monomers include one or more dicarboxylic acids or dicarboxylic anhydrides. Non-limiting examples may include, but are not limited to, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, suberic acid, sebacic acid, cyclohexanedicarboxylic acid, and their cyclic anhydride equivalents.

[0152] Epoxidized lipid additives In some embodiments, the additive is an epoxidized lipid. Any convenient lipid can be adapted for use in the compositions and methods of the present disclosure. In general terms, lipids that are unsaturated or polyunsaturated can be epoxidized to provide additive materials for use in the compositions and methods of the present disclosure. In some embodiments, the term "epoxidized derivative" or "epoxy derivative" refers to a derivative of a lipid moiety that has been epoxidized (e.g., using a peroxide or peracid reagent).

[0153] In some embodiments, the additive may include an epoxidized oil, an epoxidized derivative of a fatty acid, a triglyceride, a terpene or other lipid, or an epoxidized polymer. In some embodiments, the epoxidized oil, epoxidized fatty acid ester, epoxidized triglyceride, epoxidized terpene, epoxidized polymer, epoxy derivative or other fatty acid (ester) additive may react with the monomers, oligomers or polymers of the polymerization reaction mixture.

[0154] In some embodiments, the additive is an epoxidized triglyceride. Triglycerides with different degrees of unsaturation can be epoxidized to add reactive functional groups. In some cases, the functional groups are up to 6 epoxide groups per molecule. Linseed oil and soybean oil are triglycerides that can be epoxidized for use in the methods and compositions of the present disclosure.

[0155] In some examples, the additives can be esterified. In some examples, the additives include epoxide functional groups that can form covalent bonds with hydroxy and / or carboxylic acid groups of the growing oligomer or polymer. In some embodiments, the epoxy derivative or epoxidized oil or other additives are added to the reaction mixture or dispersion at the beginning of the polymerization reaction. In some embodiments, the epoxy derivative or epoxidized oil or other additives are added to the reaction mixture during the polymerization reaction, for example, after oligomers of a desired length have been formed. In some embodiments, the epoxy derivative or epoxidized oil or other additives are added at the end of the polymerization reaction. For example, in some embodiments, the epoxy derivative or epoxidized product can be added after repressurizing the vessel just before cooling and discharging the polymer. In some embodiments, the NCC, epoxy derivative, and / or epoxidized oil can be added up front with the alkanediol monomer and / or alkanediol monomer. For example, in some embodiments, the NCC can be added in the form of a dispersion at the beginning of the reaction. In some embodiments, the epoxy derivative or epoxidized oil is added at the end of the esterification process just before the catalyst is added and polycondensation is performed. In some instances, the epoxy derivative or epoxidized oil is allowed to react for 5 minutes before the catalyst is added. The high shear disperser method follows the same process as the ultrasonication method in terms of time and power consumption, but instead uses the equipment described at https: / / www(dot)mixers(dot)com / products / high-speed-dispersers / .

[0156] In some embodiments, one or more additional monomers are epoxidized oils.In some embodiments, one or more additional monomers are, for example, epoxidized derivatives of fatty acids or fatty acid esters.In some embodiments, epoxidized oils or epoxy derivatives include, but are not limited to, epoxidized linseed oil, epoxidized soybean oil, lard, beef tallow, fish oil, coffee oil, soybean oil, safflower oil, tung oil, tall oil, calendula, rapeseed oil, peanut oil, sesame oil, grape seed oil, olive oil, jojoba oil, dehydrated castor oil, tallow oil, sunflower oil, cottonseed oil, corn oil, canola oil, orange oil, and mixtures thereof.

[0157] In some embodiments, the epoxidized oil is derived from one or more fatty acids selected from linolenic acid, oleic acid, linoleic acid, palmitic acid, and stearic acid. In some cases, the epoxidized oil is derived from a fatty acid derivative (e.g., a triglyceride). In some embodiments, the epoxidized oil is epoxidized linseed oil. In some embodiments, the epoxidized oil is epoxidized soybean oil. The epoxidized linseed oil or epoxidized fatty acid derivative can act as a non-volatile plasticizer during resin preparation to stabilize the resin product and help provide desirable intrinsic viscosity and / or physical properties of the resin.

[0158] Epoxidized oils can impart many benefits and desirable properties to the disclosed method and resin composition. Epoxidized oils can act as acid scavengers, where the epoxide groups preferentially react with any COOH groups present in the prepolymer mixture. We have demonstrated that the addition of epoxidized oils such as ELO improves the color and thermal stability of the resulting resin mixture. Epoxidized oils act as chain extenders, whereby high reactivity and functionality can induce greater branching in the prepolymer mixture. We have demonstrated that the addition of epoxidized oils such as ELO improves the melt strength and intrinsic viscosity of the polymer resin product. In addition, the addition of epoxidized oils can enhance the process, where the epoxide groups can react with any residual solvent (e.g., BDO or water) present in the prepolymer mixture. We have demonstrated that the addition of epoxidized oils such as ELO increases processing speed and decreases reaction time.

[0159] In some embodiments, one or more additives are added in situ to the reaction mixture. In some embodiments, the one or more additives include a heat stabilizer. In some embodiments, the one or more additives include a color remover. In some embodiments, the one or more additives are flame retardants. In certain embodiments, the one or more additives are phytic acid. In certain embodiments, phytic acid is added in situ to the reaction to provide heat stabilization and color remover for the nanocomposite resin.

[0160] catalyst The polymerization reaction to form the polymer-polysaccharide nanocomposite resin can be carried out in the presence of a catalyst. A catalyst can be used during the polymerization process to activate and accelerate the process, for example, the esterification reaction between the alkanediol monomer and the alkanedioic acid monomer and / or their oligomers. In some embodiments, the reaction mixture (e.g., dispersion) containing one or more additional monomers can further include a catalyst. In some embodiments, the catalyst is added to the reaction mixture during the esterification and / or polycondensation process after the polymerization has already been initiated.

[0161] The catalyst may be a Lewis acid catalyst.

[0162] The catalyst may be a metal-based Lewis acid catalyst.

[0163] In some embodiments, the catalyst utilized in preparing the resin composition of the present disclosure is a metal oxide catalyst. In some embodiments, the catalyst is a mixed metal oxide catalyst, such as those described in Carneiro et al. "Embracing the Complexity of Catalytic Structures: A Viewpoint on the Synthesis of Nonstoichiometric Mixed Metal Oxides for Catalysis." ACS Catalysis 2020 10(1), 516-527, the disclosure of which is incorporated herein by reference.

[0164] In some embodiments, the metal oxide catalyst is a mixed metal oxide that includes two or more different metal oxides, i.e., metal oxides derived from different metals. In some embodiments, the mixed metal oxide catalyst includes an alkali or alkaline earth metal oxide and a transition metal oxide. In some embodiments, the mixed metal oxide catalyst includes an alkaline earth metal oxide and a transition metal oxide.

[0165] Transition metal oxides of interest that can be utilized in the catalyst compositions of the present disclosure include, but are not limited to, metal oxides containing aluminum, tin, titanium, zirconium, iron, copper, zinc, hafnium, and molybdenum.

[0166] Alkaline earth metal oxides of interest that may be utilized in the catalyst compositions of the present disclosure include, but are not limited to, metal oxides containing calcium, magnesium, or strontium.

[0167] In some embodiments, the mixed metal oxide catalyst comprises a titanium or zirconium metal catalyst and an alkaline earth metal catalyst containing calcium, magnesium, or strontium.

[0168] Generally, compounds containing at least one member of metal elements belonging to Groups 1 to 14 of the periodic table can be used as esterification reaction catalysts. Specific examples of metal elements include scandium, yttrium, samarium, titanium, zirconium, vanadium, chromium, molybdenum, tungsten, tin, antimony, cerium, germanium, zinc, cobalt, manganese, iron, aluminum, magnesium, calcium, strontium, sodium, and potassium. Among these, scandium, yttrium, titanium, zirconium, vanadium, molybdenum, tungsten, zinc, iron, and germanium are preferred, and titanium, zirconium, tungsten, iron, and germanium are particularly preferred. In addition, in order to reduce the concentration of polyester ends that affect the thermal stability of polyesters, metal elements belonging to Groups 3 to 6 of the periodic table and exhibiting Lewis acidity are particularly preferred among the above-mentioned metals. Specific examples thereof include scandium, titanium, zirconium, vanadium, molybdenum, and tungsten. In particular, titanium and zirconium are preferred from the viewpoint of availability, and titanium is more preferred from the viewpoint of reaction activity. In an alternative embodiment, the catalyst is not a titanium-containing catalyst.

[0169] In some embodiments, the catalyst is a metal-based Lewis acid catalyst that includes aluminum, tin, titanium, zirconium, iron, copper, zinc, hafnium, or molybdenum, hi some embodiments, the catalyst includes a titanium or zirconium compound, such as titanium lactate or zirconium butoxide.

[0170] In some embodiments, the catalyst is a hafnium-containing catalyst. In some embodiments, the catalyst comprises a hafnium salt, such as a hafnium alkoxide. Hafnium salts of interest that can be utilized as catalysts in the subject method include, but are not limited to, hafnium acetate, hafnium acetylacetonate, hafnium ethoxide, hafnium propoxide, hafnium butoxide, hafnium tert-butoxide, hafnium chloride, hafnium oxychloride hydrate, hafnium tetrachloride, hafnium tetrakis(ethylmethylamido) and hafnium-tannic acid (Hf-TA) catalysts.

[0171] In some embodiments, the catalyst is a molybdenum-containing catalyst. Molybdenum (VI) complexes have high Lewis acidity and can attack alcohol O-H bonds to generate transient species with high nucleophilic properties. Sodium molybdate is a heterogeneous catalyst used in the methanolysis of different types of renewable lipid sources derived from soybean oil. The transesterification reaction can occur under relatively mild conditions requiring low temperature, short time, and atmospheric pressure. See, for example, Nakagaki et al. "Use of anhydrous sodium molybdate as an efficient heterogeneous catalyst for soybean oil methanolysis", Applied Catalysis A: General 351 (2008) 267-274, the disclosure of which is incorporated herein by reference. In some embodiments, the catalyst comprises a molybdate or molybdate complex, such as sodium molybdate (Na2MoO4), potassium molybdate, or zinc molybdate (ZnMoO4).

[0172] In some embodiments, the catalyst is not a titanium-containing catalyst. It is understood that in some cases, the catalyst can impart a particular color to the resulting resin, and thus, the catalyst can be selected to provide the desired color or colorless properties.

[0173] In some embodiments, the catalyst is a titanium compound. In some embodiments, the titanium compound is a tetraalkyl titanate and its hydrolyzates. Non-limiting examples include, but are not limited to, tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, tetra-t-butyl titanate, tetraphenyl titanate, tetracyclohexyl titanate, tetrabenzyl titanate, and mixed titanates thereof, and their hydrolyzates.

[0174] In some embodiments, the catalyst includes titanium(oxy)acetylacetonate, titanium tetraacetylacetonate, titanium(diisopropoxide)acetylacetonate, titanium bis(ammonium lactate)dihydroxide, titanium bis(ethylacetoacetate)diisopropoxide, titanium(triethanolaminate)isopropoxide, polyhydroxytitanium stearate, titanium lactate, titanium triethanolaminate, butyl titanate dimer, etc. In some embodiments, the method further includes adding a liquid material obtained by mixing an alcohol, a Group 2 metal compound of the long form of the periodic table (IUPAC Recommendations for Nomenclature of Inorganic Chemistry 2005) (hereinafter sometimes referred to as "Group 2 metal compound of the long form of the periodic table"), a phosphate ester compound, and a titanium compound.

[0175] In some embodiments, the catalyst is selected from tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, titanium (oxy)acetylacetonate, titanium tetraacetylacetonate, titanium bis(ammonium lactate) dihydroxide, polyhydroxytitanium stearate, titanium lactate, or butyl titanate dimer, and a liquid material obtained by mixing an alcohol, a Group 2 metal compound of the long form periodic table, and a phosphate ester compound and adding a titanium compound is added.

[0176] In some embodiments, the catalyst is selected from tetra-n-butyl titanate, titanium (oxy)acetylacetonate, titanium tetraacetylacetonate, polyhydroxytitanium stearate, titanium lactate, or butyl titanate dimer, and a liquid material obtained by mixing an alcohol, a Group 2 metal compound of the long form periodic table, and a phosphate ester compound is added.

[0177] In some embodiments, the catalyst is selected from tetra-n-butyl titanate, polyhydroxy titanium stearate, titanium (oxy)acetylacetonate, titanium tetraacetylacetonate, and is added to a liquid material obtained by mixing an alcohol, a Group 2 metal compound of the long form periodic table, and a phosphate ester compound, and adding a titanium compound.

[0178] Non-limiting examples of zirconium compounds as catalysts include, but are not limited to, zirconium tetraacetate, zirconium acetate hydroxide, zirconium tris(butoxy)stearate, zirconyl diacetate, zirconium oxalate, zirconyl oxalate, potassium zirconium oxalate, polyhydroxyzirconium stearate, zirconium ethoxide, zirconium tetra-n-propoxide, zirconium tetraisopropoxide, zirconium tetra-n-butoxide, zirconium tetra-t-butoxide, zirconium tributoxyacetylacetonate, and mixtures thereof.

[0179] In some embodiments, the catalyst is selected from zirconyl diacetate, zirconium tris(butoxy)stearate, zirconium tetraacetate, zirconium acetate hydroxide, ammonium zirconium oxalate, potassium zirconium oxalate, polyhydroxyzirconium stearate, zirconium tetra-n-propoxide, zirconium tetraisopropoxide, zirconium tetra-n-butoxide, and zirconium tetra-t-butoxide (preferably zirconium tetra-t-butoxide), zirconyl diacetate, zirconium tetraacetate, zirconium acetate hydroxide, zirconium tris(butoxy)stearate, ammonium zirconium oxalate, zirconium tetra-n-propoxide, and zirconium tetra-n-butoxide. In some embodiments, the catalyst is selected from zirconium tris(butoxy)stearate. In some embodiments, colorless polyesters with a high degree of polymerization are readily obtained using zirconium tris(butoxy)stearate.

[0180] In some embodiments, the catalyst is a germanium compound.Non-limiting examples of germanium compounds include, but are not limited to, inorganic germanium compounds such as germanium oxide and germanium chloride; and organic germanium compounds such as tetraalkoxy germanium.From the viewpoint of cost and availability, germanium oxide, tetraethoxy germanium, tetrabutoxy germanium, etc. are preferred, and germanium oxide is particularly preferred.

[0181] In some embodiments, the catalyst is an inorganic chloride. Non-limiting examples of inorganic chlorides include, but are not limited to, ferric chloride, etc.; inorganic oxides, such as iron oxide; organic iron complexes, such as ferrocene; and the like. In some embodiments, the catalyst is an inorganic oxide.

[0182] In some embodiments, the catalyst is a metal-containing compound.Non-limiting examples of metal-containing compounds include, but are not limited to, scandium compounds such as scandium carbonate, scandium acetate, scandium chloride, and scandium acetylacetonate; yttrium compounds such as yttrium carbonate, yttrium chloride, yttrium acetate, and yttrium acetylacetonate; vanadium compounds such as vanadium chloride, vanadium trichloride oxide, vanadium acetylacetonate, and vanadium oxide acetylacetonate; molybdenum compounds such as molybdenum chloride and molybdenum acetate; tungsten compounds such as tungsten chloride, tungsten acetate, and tungstic acid; lanthanoid compounds such as cerium chloride, samarium chloride, and ytterbium chloride; etc.

[0183] Chelating Agents In some embodiments, the metal-based catalyst used in the preparation of the resin of the present disclosure further comprises a chelating agent.The nature and number of chelating agents used in the catalyst composition vary depending on the size and charge of the metal ions in the solution.When the size or charge of the metal ions of the catalysts involved in the polymerization are significantly different, it may be useful to use two or more chelating agents.

[0184] Any convenient chelating agent may be utilized. Chelating agents of interest include, but are not limited to, citric acid, kojic acid, urea, glycine, glycolic acid, propionic acid, acetic acid, furaneol, maltol, and combinations thereof.

[0185] In some embodiments, the chelating agent is of biological origin, for example, a compound or material of biological origin produced by a plant, fungus, or microorganism.

[0186] In some embodiments, the chelating agent is selected from kojic acid (5-hydroxy-2-(hydroxymethyl)-4-pyrone), furaneol (4-hydroxy-2,5-dimethyl-3-furanone), maltol (3-hydroxy-2-methyl-4H-pyran-4-one), and maple lactone (3-methylcyclopentane-1,2-dione).

[0187] In some embodiments, the catalyst is added to the mixture as a liquid catalyst composition comprising a mixed metal oxide catalyst and a chelating agent dissolved in a solvent, for example a glycol solvent such as ethylene glycol or propylene glycol. In some cases, the glycol solvent itself can act as a chelating or complexing agent with the metal ions in the catalyst composition.

[0188] In some embodiments, the catalyst composition used in the disclosed method is a metal oxide chelate or a mixed metal oxide chelate (e.g., a metal oxide catalyst containing a chelating agent). In some embodiments, the catalyst composition used in the disclosed method is a magnesium zirconate chelate. In some embodiments, the chelating agent used in the mixed metal oxide chelate (e.g., magnesium zirconate chelate) is selected from kojic acid (5-hydroxy-2-(hydroxymethyl)-4-pyrone), furaneol (4-hydroxy-2,5-dimethyl-3-furanone), maltol (3-hydroxy-2-methyl-4H-pyran-4-one), and maple lactone (3-methylcyclopentane-1,2-dione).

[0189] In some embodiments, the catalyst composition is premixed with dispersed polysaccharide nanocrystals, e.g., dispersed cellulose nanocrystals (e.g., as described herein), and activated. In such embodiments, the catalyst composition used in the methods of the present disclosure is referred to as a metal oxide nanoparticle chelate or mixed metal oxide nanoparticle chelate, e.g., magnesium zirconate nanoparticle chelate composition.

[0190] Other catalysts In some embodiments, the catalyst is not a metal-containing compound.

[0191] In certain embodiments, the catalyst is a mineral. In some embodiments, the catalyst comprises a naturally occurring mineral. In some embodiments, the catalyst is derived from an industrial product or by-product. The catalyst can be a clay mineral. In some embodiments, the catalyst is an aluminosilicate mineral. In some embodiments, the catalyst is a magnesium aluminum phyllosilicate clay. In some embodiments, the catalyst is selected from kaolin, kaolinite, zeolite, illite, attapulgite, palygorskite, and bentonite. In some embodiments, a fuller's earth clay material is used as the catalyst, which may be composed of palygorskite (attapulgite) and / or bentonite in some cases. In some embodiments, the catalyst is act-gel 208, a hydrous magnesium aluminosilicate material.

[0192] In some embodiments, the catalyst is kaolin. In some embodiments, the catalyst is kaolinite, such as low water content kaolinite. In some embodiments, the catalyst is metakaolinite, and in some cases, such catalysts can be thermally activated by calcination to remove any water present and increase the acidity of the catalyst material.

[0193] Non-limiting examples of catalysts include, but are not limited to, ash, fly ash, calcium carbonate, calcite, silicates, silica, quartz, oxides, metal oxides, insoluble or substantially insoluble metal salts, iron ore, talc, gypsum, magnesium carbonate, calcium and magnesium carbonate, limestone, dolomite, calcium hydroxide, magnesium hydroxide, calcium oxide, magnesium oxide, calcium bicarbonate, magnesium bicarbonate, calcium phosphate, hydroxyapatite, phyllosilicates, and any combination thereof.

[0194] In certain embodiments, a catalyst such as kaolinite is used during the esterification process to activate and complete the esterification process to produce a polymer with a suitable MW for use in the resin.

[0195] In some embodiments, the catalyst includes compounds containing organic groups, such as carboxylates, alkoxy salts, organic sulfonates, or p-diketonate salts, each of which contains such a metal element; as well as inorganic compounds such as oxides, halides, and the like of the above metals, as well as mixtures thereof.

[0196] In some embodiments, the catalyst is not a metal-containing catalyst. In some embodiments, the catalyst does not include a transition metal compound or salt. In certain embodiments, the method provides improved catalytic activity without a metal catalyst.

[0197] In some embodiments, the catalyst is a protic ionic salt. Protic ionic salt-containing catalysts of interest include sulfonic acid-containing compounds and materials, or salts thereof. In some embodiments, the catalyst is an organic catalyst that includes a protic ionic salt. In some embodiments, the organic catalyst includes organic sulfate and / or sulfonate groups. In some embodiments, modified cellulose or other polysaccharides can act as catalysts. Methanesulfonic acid is an organic catalyst used for polymer degradation and synthesis at high temperatures. In some embodiments, the protic ionic salt catalyst is utilized in conjunction with a non-nucleophilic base, such as triazabicyclodecene (TBD) or 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU).

[0198] In some embodiments, the polysaccharide nanocrystals utilized in the reaction mixture are selected to contain substituents that can act as Lewis acid catalysts. For example, nanocellulose crystals (NCC) produced via sulfuric acid treatment may contain sulfate and / or sulfonate groups. In some cases, the modified polysaccharide nanocrystals are selected to act as protonic ionic salt catalysts in the reaction mixture.

[0199] In some embodiments, the method includes a compound that is liquid or soluble in the ester oligomer or polyester during polymerization. In some embodiments, a compound that is liquid or soluble in the ester oligomer or polyester is added because the polymerization rate is higher when the catalyst is in a molten or dissolved state during polymerization.

[0200] method An aspect of the present disclosure includes a method for producing a polyester polymer-polysaccharide nanocomposite resin.

[0201] In some embodiments, the method includes preparing a dispersion or suspension including polysaccharide nanocrystals, alkanediol monomers, and alkanedioic acid agent monomers, and then initiating polymerization, which can be initiated, for example, by the addition of a catalyst and / or by application of reaction conditions (e.g., temperature, solvent, pressure, etc.) sufficient to initiate transesterification.

[0202] In some embodiments, the dispersion or suspension of the present method, including polysaccharide nanocrystals, alkanediol monomers, and alkanedioic acid agent monomers, is prepared in situ after the start of the reaction. Thus, in some cases, polysaccharide nanocrystals are added to a reaction mixture including alkanediol monomers and alkanedioic acid agent monomers, and, for example, oligomers composed thereof. In some embodiments, the in situ addition of polysaccharide nanocrystals (e.g., NCC) can provide one or more desired properties or characteristics in the resulting composition, such as desired strength, toughness, processing aid during melt spinning, cationic dyeable sites, gas / moisture permeability properties, nucleating agent, and / or improved biodegradability.

[0203] In some embodiments, the method further comprises polymerizing or polycondensing the alkanediol monomers and the alkanedioic acid monomers in the dispersion to produce a polymer-polysaccharide nanocomposite resin.

[0204] In an alternative embodiment, the method further comprises pelletizing and / or drying the polymer-polysaccharide nanocomposite resin after the initial polymerization reaction.

[0205] In some embodiments, the method further comprises pelletizing the polyester polymer-polysaccharide nanocomposite resin produced from the polymerization process. In some embodiments, drying the resin pellets is performed under conditions sufficient to remove moisture from the mixture and increase the molecular weight of the polymers in the resin mixture. In certain embodiments, pelletizing the mixture is performed prior to compounding (e.g., involving blending, remelting, and mixing) or melt spinning. In some embodiments, compounding comprises any one of in situ polymerization, melt mixing, and solution mixing.

[0206] In some embodiments, pelletizing comprises any conventionally known pelletizing process, non-limiting examples of which include, but are not limited to, melt pelletizing and strand pelletizing.

[0207] Preparation of reaction mixture or dispersion An embodiment of the method includes preparing a mixture or dispersion that includes polysaccharide nanocrystals, alkanediol monomers, and alkanedioic acid agent monomers.

[0208] In some embodiments, preparing the mixture or dispersion comprises dispersing polysaccharide nanocrystals in a solution comprising one or both of an alkanediol monomer and an alkanedioic acid monomer.

[0209] In some embodiments, dispersing comprises contacting with polysaccharide nanocrystals in a solution. In some embodiments, the solution comprises one or both of an alkanediol monomer and an alkanediol monomer. In some embodiments, the polysaccharide nanocrystals are added in situ. In certain embodiments, the in situ addition of the polysaccharide nanocrystals is configured to increase the tensile strength and Young's modulus of the nanocomposite resin. In certain embodiments, the in situ addition of the polysaccharide nanocrystals can increase the biodegradability of an article produced with the nanocomposite resin. In certain embodiments, the in situ addition of the polysaccharide nanocrystals reduces gas and / or moisture permeation through an article produced by forming the nanocomposite resin. In some embodiments, the polysaccharide nanocrystals are nucleating agents. In certain embodiments, the polysaccharide nanocrystals function as cationic dyeable sites in an article produced by producing the nanocomposite resin. In certain embodiments, the polysaccharide nanocrystals are compatibilizers for melt processing / spinning of the nanocomposite during yarn or fiber production.

[0210] In some embodiments, the solution comprises an alkanediol monomer and an alkanedioic acid agent monomer. In some embodiments, the solution consists of an alkanediol monomer and an alkanedioic acid agent monomer.

[0211] In some embodiments, the solution further comprises a non-aqueous solvent. In some embodiments, the solution further comprises a non-aqueous organic solvent.

[0212] In some embodiments, the solution further comprises water, hi some embodiments, the water is deionized water.

[0213] In some embodiments, dispersing the polysaccharide nanocrystals, alkanediol monomers, and alkanedioic acid agent monomers comprises contacting cellulose nanocrystals with a solution comprising polysaccharide nanocrystals, alkanediol monomers, and alkanedioic acid agent monomers to form a mixture, and sonicating the mixture to homogenously disperse the polysaccharide nanocrystals in the solution to form a dispersion.

[0214] For example, polysaccharide nanocrystals may be added to and dispersed in an alkanediol monomer and / or an alkanedioic acid agent.

[0215] In some embodiments, the method includes charging an alkanediol monomer and / or an alkane diacid agent to a reaction vessel to form a reactant mixture. In some embodiments, the method includes agitating the reactants with a nitrogen gas flow in the range of 100-250 rpm (e.g., 100 rpm or more, 150 rpm or more, 200 rpm or more, or 250 rpm or more) until a homogenous slurry is formed.

[0216] In some embodiments, the method further comprises contacting the polysaccharide nanocrystals with a homogenous slurry.

[0217] A catalyst (e.g., as described herein) may be added to the reaction mixture at any convenient time. In some embodiments, a catalyst solution is prepared as part of the initial reaction mixture. In some embodiments, the catalyst and polysaccharide nanocrystals are prepared as separate dispersions and then added to the reaction mixture at any convenient stage.

[0218] In some embodiments, the method further comprises increasing the temperature of the reaction mixture or slurry. In some embodiments, the temperature is increased to 100° C. or more, 125° C. or more, 150° C. or more, 175° C. or more, 200° C. or more, 225° C. or more, 250° C. or more, or 275° C. or more. In some embodiments, the temperature is increased for about 10 minutes or more, about 20 minutes or more, about 30 minutes or more, about 40 minutes or more, about 50 minutes or more, about 60 minutes or more, about 70 minutes or more, about 80 minutes or more, about 90 minutes or more, about 100 minutes or more, about 110 minutes or more, about 120 minutes or more, about 130 minutes or more, about 140 minutes or more, or about 150 minutes or more.

[0219] In some embodiments, increasing the temperature results in the formation of water and THF, hi some embodiments, the method further comprises removing the water and THF from the reactor via a distillation apparatus.

[0220] The polysaccharide nanocrystals can be dispersed in the pre-solution or reaction mixture and characterized using any convenient method, such as that described by Beck et al. ("Dispersibility in Water of Dried Nanocrystalline Cellulose." Biomacromolecules 2012, 13, 1486-1494).

[0221] In some embodiments, the polysaccharide nanocrystals are dispersed in the alkanediol monomer by sonicating the polysaccharide-alkanediol mixture. In some embodiments, dispersing the polysaccharide-alkanediol mixture includes sonicating the mixture as opposed to other mechanical means, such as stirring, to eliminate or substantially eliminate settling. In some embodiments, a polysaccharide-alkanediol mixture with a higher dispersion value (smaller polysaccharide nanocrystal particle size) compared to a larger polysaccharide nanocrystal particle size with a lower dispersion value ultimately produces a polysaccharide nanocomposite with more desirable properties, including increased transparency, processability, biodegradability, strength, and toughness. However, other embodiments of the method may include using mechanical means to disperse the polysaccharide nanocrystals, such as a homogenizer for high shear dispersion.

[0222] In some embodiments, the polysaccharide nanocrystals are dispersed in the alkanediol monomer using a homogenizer.

[0223] In some embodiments, the polysaccharide nanocrystals are dispersed prior to esterification. For example, a polysaccharide-alkanediol dispersion can be obtained by dispersing polysaccharide nanocrystals in an alkanediol monomer prior to esterification. Additionally, the quality of the dispersion can be verified before further production and the dispersion can be adjusted until it is at a desired level. The quality of the dispersion can be verified by measuring the quality of the dispersion before the reaction occurs. For example, in production, an aliquot of the BDO / NCC dispersion can be taken and verified to meet requirements. More data is collected regarding the level of dispersion prior to reaction (e.g., more than 50% of the material has dimensions <100 nm) to evaluate how it affects the properties of the final polymer, which can include the NCC gel size of the final polymer.

[0224] In some embodiments, the polysaccharide nanocrystals are dispersed in the alkanedioic acid agent by optionally sonicating the polysaccharide-alkanedioic acid agent mixture. In some embodiments, dispersing the polysaccharide-alkanedioic acid agent mixture includes optionally sonicating the mixture to eliminate or substantially eliminate settling, as opposed to other mechanical means such as stirring. In some embodiments, a polysaccharide-alkanedioic acid agent mixture with a higher dispersion value (smaller polysaccharide nanocrystal size) ultimately produces a polysaccharide nanocomposite with more desirable properties, including increased transparency, processability, and toughness. However, other embodiments of the method may include using mechanical means to disperse the polysaccharide nanocrystals, such as a homogenizer for high shear dispersion.

[0225] In some embodiments, the polysaccharide nanocrystals are dispersed in the -alkanedioic acid agent using a homogenizer.

[0226] In some embodiments, the polysaccharide nanocrystals are dispersed in the alkanedioic acid agent by optionally sonicating the polysaccharide-alkanedioic acid agent mixture. In some embodiments, dispersing the polysaccharide-alkanedioic acid agent mixture includes optionally sonicating the mixture to eliminate or substantially eliminate settling, as opposed to other mechanical means such as stirring. In some embodiments, a polysaccharide-alkanedioic acid agent mixture with a higher dispersion value (smaller polysaccharide nanocrystal size) ultimately produces a polysaccharide nanocomposite with more desirable properties, including increased transparency, processability, and toughness. However, other embodiments of the method may include using mechanical means to disperse the polysaccharide nanocrystals, such as a homogenizer for high shear dispersion.

[0227] In certain embodiments, the polysaccharide nanocrystals are dispersed in the alkanedioic acid agent by sonicating the polysaccharide-alkanedioic acid agent mixture.

[0228] In some embodiments, the polysaccharide nanocrystals are dispersed in the -alkanedioic acid agent using a homogenizer.

[0229] In some embodiments, the polysaccharide nanocrystals are dispersed using a high shear disperser.

[0230] In some embodiments, the method includes contacting the polysaccharide-alkanediol monomer dispersion with an alkanedioic acid agent monomer. In some embodiments, the polysaccharide-alkanediol monomer mixture is added to the alkanedioic acid agent monomer as a slurry.

[0231] In some embodiments, sonicating the mixture is carried out under conditions sufficient to produce a dispersion in which there is no visible settling.

[0232] In some embodiments, the method includes contacting the polysaccharide-alkanediol monomer dispersion with an alkanedioic acid agent monomer. In some embodiments, the polysaccharide-alkanediol monomer mixture is added to the alkanedioic acid agent monomer as a slurry.

[0233] In some embodiments, sonicating the mixture is carried out under conditions sufficient to produce a dispersion in which there is no visible settling.

[0234] In some embodiments, the polysaccharide nanocrystals are dispersed in the alkanediol monomer and the alkanediol agent by sonicating the polysaccharide-alkanediol-alkanediol agent mixture. In some embodiments, dispersing the polysaccharide-alkanediol-alkanediol agent mixture includes sonicating the mixture as opposed to other mechanical means, such as stirring, to eliminate or substantially eliminate settling. In some embodiments, a polysaccharide-alkanediol-alkanediol agent mixture with a higher dispersion value (smaller polysaccharide nanocrystal size) ultimately produces a polysaccharide nanocomposite with more desirable properties, including increased transparency, processability, and toughness. However, other embodiments of the method may include using mechanical means to disperse the polysaccharide nanocrystals, such as a homogenizer for high shear dispersion.

[0235] In some embodiments, the polysaccharide nanocrystals are dispersed in the alkanediol monomer-alkanedioic acid agent mixture using a homogenizer.

[0236] In some embodiments, the polysaccharide nanocrystals are dispersed prior to esterification. For example, a polysaccharide-alkanediol-alkanediacid agent dispersion can be obtained by dispersing polysaccharide nanocrystals in an alkanediol monomer-alkanediacid agent prior to esterification. Furthermore, the quality of the dispersion can be verified before further production and the dispersion can be adjusted until a desired level is achieved.

[0237] In some embodiments, sonicating the mixture comprises sonicating for a duration of about 5 minutes or more. In some embodiments, sonicating the mixture comprises sonicating for a duration of about 5 minutes or more (e.g., at at least 60% of the amplitude of the maximum output of the sonicator). In some embodiments, sonicating the mixture comprises sonicating for a duration of about 5 minutes or more (e.g., at at least 80% of the amplitude of the maximum output of the sonicator). In some embodiments, sonicating the mixture comprises sonicating for a duration of about 5 minutes or more (e.g., at at least 100% of the amplitude of the maximum output of the sonicator).

[0238] In some embodiments, sonicating the mixture comprises sonicating for a duration of about 6 minutes or more, 7 minutes or more, 8 minutes or more, 9 minutes or more, 10 minutes or more, 11 minutes or more, 12 minutes or more, 13 minutes or more, 14 minutes or more, or 15 minutes or more.

[0239] Dispersion components In some embodiments, the dispersion comprises polysaccharide nanocrystals and one or more monomers, hi some embodiments, the one or more monomers include alkanediol monomers and alkanedioic acid monomers.

[0240] In some embodiments, the polysaccharide nanocrystals are derived from heparin, chitosan, chitin, hyaluronan, starch, cellulose, alginate, pectin, guar, starch / chitosan, chitosan / heparin, chitosan / hyaluronan, hyaluronan / heparin, or cellulose, as well as chitin whiskers and platelet-like starch. In some embodiments, the polysaccharide nanocrystals are derived from cellulose, starch, or chitin. In some embodiments, the polysaccharide nanocrystals are derived from chitosan. In some embodiments, the polysaccharide nanocrystals are derived from chitosan and cellulose. In some embodiments, the polysaccharide nanocrystals in the nanocomposite resin derived from chitosan provide improved properties to articles manufactured from the nanocomposite resin. In some embodiments, the improved properties to the article include one or more of flame retardancy, increased antimicrobial properties, and enhanced biodegradability of the article. In some embodiments, the article is a yarn or fiber.

[0241] In some embodiments, the polysaccharide nanocrystals are derived from cellulose. In some embodiments, the polysaccharide nanocrystals are derived from starch. In some embodiments, the polysaccharide nanocrystals are derived from chitin.

[0242] In some embodiments, the polysaccharide nanocrystals can be spheres, rods, disks, or any other shape. In some embodiments, the nanocrystals can have a narrow size distribution. In some embodiments, the nanocrystals can have a broad size distribution.

[0243] In some embodiments, the polysaccharide nanocrystals are derived from cellulose, hi some embodiments, the polysaccharide nanocrystals are cellulose nanocrystals.

[0244] In some embodiments, cellulose nanocrystals are crystals derived by subjecting cellulose fibers to a chemical treatment such as acid hydrolysis. In some embodiments, cellulose nanocrystals are derived from acid hydrolyzed cellulose from cellulosic biomass via an acid hydrolysis technique similar to that first described by Ranby, BG (Ranby, BG (1951) Descation Faraday Society, 11, 158-164). NCC produced via sulfuric acid and neutralized with base (NaOH in this case) contains a large amount of sodium sulfate groups that affect dispersibility in hydrophilic media.

[0245] In some embodiments, the acid hydrolyzed cellulose is obtained from naturally occurring cellulose fibers. In some embodiments, the acid hydrolyzed cellulose is obtained, for example, from plant biomass, vascular plants, cotton plants, wood pulp, jute, hemp, corn, frass, rice, wheat straw, or sisal. In some embodiments, the cellulose is obtained from plant biomass, including, but not limited to, trees, grasses, cotton, sisal, bamboo, and ramie.

[0246] In some embodiments, cellulose nanocrystals can be found as structural components in urochordates (sea creatures similar to sea cucumbers) and are produced naturally by the bacterium Acetobacter xylinum.

[0247] In some embodiments, the cellulose nanocrystals have an average dimension of about 1-80 nm in width and about 25-1000 nm in length. In some embodiments, the cellulose nanocrystals have an average dimension of about 1-100 nm in width and about 25-3000 nm in length. In some embodiments, the cellulose nanocrystals have an average dimension of about 10 nm or more, 15 nm or more, 20 nm or more, 25 nm or more, 30 nm or more, 35 nm or more, 40 nm or more, 45 nm or more, 50 nm or more, 55 nm or more, 60 nm or more, 65 nm or more, 70 nm or more, 75 nm or more, 80 nm or more, 85 nm or more, 90 nm or more, 95 nm or more, or 100 nm or more in width and 25 nm or more, 50 nm or more, 100 nm or more in length. m or more, 150 nm or more, 200 nm or more, 250 nm or more, 300 nm or more, 350 nm or more, 400 nm or more, 500 nm or more, 550 nm or more, 600 nm or more, 650 nm or more, 700 nm or more, 800 nm or more, 850 nm or more, 900 nm or more, 950 nm or more, 1000 nm or more, 1500 nm or more, 2000 nm or more, 2500 nm or more, or 3000 nm or more.

[0248] In some embodiments, the nanocrystals in the dispersion have a particle size distribution in the range of about 1 d.nm to about 400 d.nm. In some embodiments, the nanocrystals in the dispersion have a particle size distribution in the range of about 1 d.nm to about 50 d.nm, about 50 d.nm to about 100 d.nm, about 100 d.nm to about 150 d.nm, about 150 d.nm to about 200 d.nm, 200 d.nm to about 250 d.nm, 250 d.nm to about 300 d.nm, 300 d.nm to about 350 d.nm, 350 d.nm to about 400 d.nm. In some embodiments, the nanocrystals in the dispersion have a particle size distribution in the range of about 1 d.nm to about 20 d.nm. In some embodiments, the nanocrystals in the dispersion have a particle size distribution in the range of about 10 d.nm to about 100 d.nm. In some embodiments, the nanocrystals in the dispersion have a particle size distribution in the range of about 10 d.nm to about 30 d.nm. In some embodiments, the nanocrystals in the dispersion have a particle size distribution in the range of about 100 d.nm to about 200 d.nm. In some embodiments, the nanocrystals in the dispersion have a particle size distribution in the range of about 1 d.nm to about 200 d.nm. In some embodiments, the nanocrystals in the dispersion have a particle size distribution in the range of about 1 d.nm or more, 2 d.nm or more, 4 d.nm or more, 6 d.nm or more, 8 d.nm or more, 10 d.nm or more, 12 d.nm or more, 14 d.nm or more, 16 d.nm or more, 18 d.nm or more, 20 d.nm or more, 22 d.nm or more, 24 d.nm or more, 26 d.nm or more, 28 d.nm or more, 30 d.nm or more, 32 d.nm or more, 34 d.nm or more, 36 d.nm or more, 38 d.nm or more, 40 d.nm or more, 42 d.nm or more, 44 d.nm or more, 46 d.nm or more, 48 d.nm or more, 50 d.nm or more, 52 d.nm or more, 54 d.nm or more, 56 d.nm or more, 5 ...0 d.nm or more, 50 d.nm or more The particle size distribution is 0 d.nm or more, 52 d.nm or more, 54 d.nm or more, 56 d.nm or more, 58 d.nm or more, 60 d.nm or more, 62 d.nm or more, 64 d.nm or more, 66 d.nm or more, 68 d.nm or more, 70 d.nm or more, 72 d.nm or more, 74 d.nm or more, 76 d.nm or more, 78 d.nm or more, 80 d.nm or more, 82 d.nm or more, 84 d.nm or more, 86 d.nm or more, 88 d.nm or more, 90 d.nm or more, 92 d.nm or more, 94 d.nm or more, 96 d.nm or more, 98 d.nm or more, or 100 d.nm or more.In some embodiments, the nanocrystals in the dispersion have a diameter of 100 d.nm or more, 125 d.nm or more, 150 d.nm or more, 175 d.nm or more, 200 d.nm or more, 225 d.nm or more, 250 d.nm or more, 275 d.nm or more, 300 d.nm or more, 325 d.nm or more, 350 d.nm or more, 400 d.nm or more, 425 d.nm or more, 500 d.nm or more, 525 d.nm or more, 550 d.nm or more, 575 d.nm or more, .nm or more, 600d.nm or more, 625d.nm or more, 650d.nm or more, 675d.nm or more, 700d.nm or more, 725d.nm or more, 750d.nm or more, 775d.nm or more, 800d.nm or more, 825d.nm or more, 850d.nm or more, 875d.nm or more, 900d.nm or more, 925d.nm or more, 950d.nm or more, 975d.nm or more, or 1000d.nm or more.

[0249] In some embodiments, increasing the length of the cellulose nanocrystals increases the potential load distribution throughout the polymer. In some embodiments, the orientation of the cellulose nanocrystals within the polymer increases the interfacial contact between adjacent cellulose nanocrystals in the axial orientation, which may increase the ultimate tensile strength. In some embodiments, in the transverse direction, The morphology (eg, length, aspect ratio, length, polydispersity) and surface charge of cellulose nanocrystals vary greatly based on synthesis conditions.

[0250] In some embodiments, acid hydrolysis is used to break down cellulose microfibrils by digesting the amorphous regions that connect the cellulose nanocrystals. In some embodiments, processing typically requires heating, agitation, rinsing, filtration, dialysis, and ultrasonication, with the parameters of each step having a direct effect on the morphology and / or surface chemistry of the cellulose nanocrystals. In some embodiments, the end result of cellulose nanocrystal processing includes a suspension of produced liquid crystalline cellulose nanocrystals, forming either a nematic or chiral nematic mesophase (e.g., depending on the length, aspect ratio, length, polydispersity, surface charge, cellulose nanocrystal concentration, and electrolyte concentration of the cellulose nanocrystals).

[0251] In some embodiments, the polymer of the polymer-polysaccharide nanocomposite resin comprises an aliphatic polyester polymer, which may include, but is not limited to, an aliphatic polyester polymer selected from polylactide (PLA) (e.g., poly(lactic acid)), polyglycolide (PGA) (e.g., polyglycolic acid), poly(ε-caprolactone) (PCL), poly(γ-valerolactone) (PVL), and the copolymer poly(lactic-co-glycolic acid) (PLGA).

[0252] In some embodiments, the polymer of the polymer-polysaccharide nanocomposite resin includes a polybutylene succinate homopolymer or a polybutylene succinate copolymer (eg, a polybutylene succinate adipate copolymer).

[0253] In some embodiments, the dispersion comprises an alkanediol monomer.

[0254] In some embodiments, alkanediol monomers include, but are not limited to, 1,4-butanediol monomers, 1,2-ethanediol monomers, 1,3-propanediol monomers, 1,5-pentanediol monomers, or 1,6-hexanediol monomers.

[0255] In some embodiments, the alkanediol monomer includes one or more diols to form a polyester composite.Non-limiting examples of other suitable diols include, but are not limited to, ethylene glycol, 1,3-propylene glycol, neopentyl glycol, 1,6-hexamethylene glycol, 1,4-cyclohexanedimethanol, hydroquinone, 1.5-dihydroxynaphthalene, 4,4'-dihydroxydiphenyl, bis(p-hydroxyphenyl)methane, bis(p-hydroxyphenyl)-2.2-propane, and combinations thereof.

[0256] In some embodiments, the alkanediol monomer 1,4-butanediol.

[0257] In some embodiments, the alkanediol monomer is 1,2-ethanediol.

[0258] In some embodiments, the alkanediol monomer is 1,3-propanediol.

[0259] In some embodiments, the dispersion comprises an alkanedioic acid agent monomer, including, but not limited to, an alkanedioic acid agent monomer selected from succinic acid, monoalkyl succinates, dialkyl succinates (e.g., dimethyl or diethyl succinate), succinic anhydride, adipic acid, monoalkyl adipates, dialkyl adipates (e.g., dimethyl or diethyl adipate), and adipic anhydride.

[0260] In some embodiments, the alkanedioic acid agent monomers are selected from oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, suberic acid, sebacic acid, cyclohexanedicarboxylic acid, and their cyclic anhydride equivalents.

[0261] In certain embodiments, the alkane diol monomer is a 1,4-butane diol monomer. In certain embodiments, the alkanedioic acid agent monomer is a succinic acid agent monomer. In certain embodiments, the alkanedioic acid agent monomer is succinic anhydride.

[0262] In some embodiments, the dispersing comprises contacting cellulose nanocrystals, 1,4-butanediol monomers, and succinic acid agent monomers to produce the cellulose mixture.

[0263] In some embodiments, the alkanedioic acid agent monomer is a succinic acid agent monomer or a derivative thereof. In some embodiments, the alkanedioic acid agent monomer is a succinic acid agent monomer. In some embodiments, the succinic acid agent is succinic anhydride.

[0264] In some embodiments, succinic acid agent monomers include, but are not limited to, succinic acid agents selected from succinic acid, monoalkyl succinates, dialkyl succinates (e.g., dimethyl succinate or diethyl succinate), or succinic anhydride.

[0265] In some embodiments, the succinic acid agent is a succinate derivative. In some embodiments, the succinate derivative is succinate anhydride. In some embodiments, succinate anhydride increases the rate of esterification with 1,4 butanediol and also reduces the amount of harmful THF produced during the esterification process. However, other suitable non-limiting examples of succinate derivatives may include succinic acid or succinate esters.

[0266] In some embodiments, the dispersion includes one or more additional monomers.

[0267] In some embodiments, the one or more additional monomers include, but are not limited to, comonomers, epoxy derivatives, oils, pigments, crosslinkers, and the like.

[0268] In some embodiments, the one or more additional monomers include an additional alkanediol monomer and / or an additional alkanedioic acid agent monomer.

[0269] In some embodiments, the additional alkanediol monomers include, but are not limited to, alkanediol monomers and / or additional alkanedioic acid monomers, including, but not limited to, 1,4-butanediol monomers, 1,2-ethanediol monomers, 1,3-propanediol monomers, 1,5-pentanediol monomers, or 1,6-hexanediol monomers.

[0270] In some embodiments, diacid agent monomers include, but are not limited to, alkanedioic acid agent monomers selected from succinic acid, monoalkyl succinates, dialkyl succinates (e.g., dimethyl or diethyl succinate), succinic anhydride, adipic acid, monoalkyl adipates, dialkyl adipates (e.g., dimethyl or diethyl adipate), and adipic anhydride.

[0271] In some embodiments, the additional alkanedioic acid agent monomer comprises adipic anhydride, hi some embodiments, the additional alkanedioic acid agent monomer comprises fumaric acid, or an ester or anhydride thereof.

[0272] In some embodiments, one or more additional components may include a hydrophobic agent. In some embodiments, the hydrophobic agent is an oil. In some embodiments, the hydrophobic agent is an elastomeric material. In some embodiments, the hydrophobic agent is an epoxidized soybean oil or an elastomeric material. The hydrophobic agent may be utilized as an end capping agent of the polyester polymer in the composition, for example, linked via an ether, ester, or carbamate linkage.

[0273] In some embodiments, the one or more additional components include, but are not limited to, agents to provide additional water and may include oxygen barrier properties. Non-limiting exemplary water and oxygen barrier agents include candelilla wax, beeswax, and other waxes. In some embodiments, such barrier agents are derived from renewable resources. In some embodiments, the one or more additional monomers include polishes that provide an aesthetically pleasing shine to the finished product. Non-limiting exemplary polishes include shea butter and nut oils such as Brazil nut oil. In some embodiments, the polishes are derived from renewable resources.

[0274] In some embodiments, the one or more additional monomers include, but are not limited to, impact modifiers, antioxidants, antibacterial agents, antifungal agents, antistatic agents, fillers, heat stabilizers, UV stabilizers, dyes, fillers, crystallization enhancers, and coupling agents.

[0275] Non-limiting examples of antioxidants include hindered phenol antioxidants such as p-tert-butylhydroxytoluene and p-tert-butylhydroxyanisole, sulfur antioxidants such as distearyl thiodipropionate and dilauryl thiodipropionate, etc. Heat stabilizers include triphenyl phosphite, trilauryl phosphite, trisnonylphenyl phosphite, etc. UV stabilizers include p-tert-butylphenyl salicylate, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxy-2'-carboxybenzophenone, 2,4,5-trihydroxybutyrophenone, etc. Lubricants include calcium stearate, zinc stearate, barium stearate, sodium palmitate, etc. Antistatic agents include N,N-bis(hydroxyethyl)alkylamines, alkylamines, alkylarylsulfonates, alkylsulfonates, etc. Flame retardants include hexabromocyclododecane, tris-(2,3-dichloropropyl)phosphate, pentabromophenyl allyl ether, etc. Antiblocking agents include combinations of inorganic fillers such as silica and oleamide. Inorganic fillers or nucleating agents include calcium carbonate, silica, titanium oxide, talc, mica, barium sulfate, alumina, a mixture of NaHCO3 and citric acid, etc. Crystallization promoters include polyethylene terephthalate, poly-transcyclohexanedimethanol terephthalate, etc. Organic fillers include wood flour, rice husks, waste paper such as newspapers, starch (including modified materials such as pregelatinized starch), cellulose, etc.

[0276] In some embodiments, polyethers having hydroxyl end groups can be used in combination with the diols disclosed in the present disclosure. For polyethers having hydroxyl end groups, the carbon number has a lower limit of usually 4 or more, preferably 10 or more, and an upper limit of usually 1,000 or less, preferably 200 or less, more preferably 100 or less. Non-limiting examples of polyethers having hydroxyl end groups include, but are not limited to, diethylene glycol, triethylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, poly-1,6-hexamethylene glycol, and the like. Also, copolymer polyethers of polyethylene glycol and polypropylene glycol, and the like, can be used.

[0277] In some embodiments, the one or more additional monomers include one or more dicarboxylic acids or dicarboxylic anhydrides. Non-limiting examples may include, but are not limited to, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, suberic acid, sebacic acid, cyclohexanedicarboxylic acid, and their cyclic anhydride equivalents.

[0278] In some embodiments, the one or more additional monomers include an epoxidized oil, an epoxy derivative, or a fatty acid. In some embodiments, the epoxidized oil, the epoxy derivative, or the fatty acid can be esterified.

[0279] In some embodiments, the one or more additional monomers include an epoxidized oil, an epoxy derivative, or a fatty acid. In some embodiments, the epoxidized oil, the epoxy derivative, or the fatty acid can be esterified. In some embodiments, the epoxy derivative or the epoxidized oil is added at the end of the reaction. In some embodiments, the epoxidized oil or the epoxy derivative is added in situ. For example, in some embodiments, the method includes adding the epoxy derivative or the epoxidized product after repressurizing the vessel just before cooling and discharging the polymer. In some embodiments, the method includes adding the NCC, the epoxy derivative, and / or the epoxidized oil, which may be added up front with the alkanediol monomer and / or the alkanediol monomer. For example, in some embodiments, the method includes adding the NCC in the form of a dispersion at the beginning of the reaction. In some embodiments, the method includes adding the epoxy derivative or the epoxidized oil at the end of the esterification process just before the catalyst is added and polycondensation is performed. In some examples, the catalyst is added after the epoxy derivative or the epoxidized oil is allowed to react for 5 minutes. The high shear disperser method follows the same process as the ultrasonication method in terms of time and power consumption, but instead uses the equipment described at https: / / www(dot)mixers(dot)com / products / high-speed-dispersers / .

[0280] In some embodiments, one or more additional monomers are epoxidized oils.In some embodiments, one or more additional monomers are epoxidized derivatives.In some embodiments, epoxidized oils or epoxy derivatives include, but are not limited to, epoxidized linseed oil, linseed oil as epoxidized, lard, beef tallow, fish oil, coffee oil, soybean oil, safflower oil, tung oil, tall oil, calendula, rapeseed oil, peanut oil, sesame oil, grapeseed oil, olive oil, jojoba oil, dehydrated castor oil, tallow oil, sunflower oil, cottonseed oil, corn oil, canola oil, orange oil, and mixtures thereof.

[0281] In some embodiments, the one or more additional monomers comprise a catalyst.

[0282] Non-limiting exemplary catalysts include titanium or zirconium compounds, such as, but not limited to, titanium lactate or zirconium butoxide. Generally, compounds containing at least one member of the metal elements belonging to Groups 1 to 14 of the periodic table can be used as esterification reaction catalysts. Specifically, examples of metal elements include scandium, yttrium, samarium, titanium, zirconium, vanadium, chromium, molybdenum, tungsten, tin, antimony, cerium, germanium, zinc, cobalt, manganese, iron, aluminum, magnesium, calcium, strontium, sodium, potassium, and the like. Among these, scandium, yttrium, titanium, zirconium, vanadium, molybdenum, tungsten, zinc, iron, and germanium are preferred, and titanium, zirconium, tungsten, iron, and germanium are particularly preferred. In addition, in order to reduce the concentration of polyester ends that affect the thermal stability of polyesters, metal elements belonging to Groups 3 to 6 of the periodic table and exhibiting Lewis acidity are particularly preferred among the above-mentioned metals. Specific examples of such elements include scandium, titanium, zirconium, vanadium, molybdenum, and tungsten. In particular, titanium and zirconium are preferred from the viewpoint of availability, and titanium is more preferred from the viewpoint of reaction activity.

[0283] In some embodiments, the catalyst includes compounds containing organic groups, such as carboxylates, alkoxy salts, organic sulfonates, or β-diketonate salts, each of which contains such a metal element; as well as inorganic compounds such as oxides, halides, and the like of the above metals, as well as mixtures thereof.

[0284] In some embodiments, the method includes a compound that is liquid or soluble in the ester oligomer or polyester during polymerization. In some embodiments, a compound that is liquid or soluble in the ester oligomer or polyester is added because the polymerization rate is higher when the catalyst is in a molten or dissolved state during polymerization.

[0285] In some embodiments, the catalyst is a titanium compound. In some embodiments, the titanium compound is a tetraalkyl titanate and its hydrolyzates. Non-limiting examples include, but are not limited to, tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, tetra-t-butyl titanate, tetraphenyl titanate, tetracyclohexyl titanate, tetrabenzyl titanate, and mixed titanates thereof, and their hydrolyzates.

[0286] In some embodiments, the catalyst includes titanium(oxy)acetylacetonate, titanium tetraacetylacetonate, titanium(diisopropoxide)acetylacetonate, titanium bis(ammonium lactate)dihydroxide, titanium bis(ethylacetoacetate)diisopropoxide, titanium(triethanolaminate)isopropoxide, polyhydroxytitanium stearate, titanium lactate, titanium triethanolaminate, butyl titanate dimer, etc. In some embodiments, the method further includes adding a liquid material obtained by mixing an alcohol, a Group 2 metal compound of the long form of the periodic table (IUPAC Recommendations for Nomenclature of Inorganic Chemistry 2005) (hereinafter sometimes referred to as "Group 2 metal compound of the long form of the periodic table"), a phosphate ester compound, and a titanium compound.

[0287] In some embodiments, the catalyst is selected from tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, titanium (oxy)acetylacetonate, titanium tetraacetylacetonate, titanium bis(ammonium lactate) dihydroxide, polyhydroxytitanium stearate, titanium lactate, or butyl titanate dimer, and a liquid material obtained by mixing an alcohol, a Group 2 metal compound of the long form periodic table, and a phosphate ester compound and adding a titanium compound is added.

[0288] In some embodiments, the catalyst is selected from tetra-n-butyl titanate, titanium (oxy)acetylacetonate, titanium tetraacetylacetonate, polyhydroxytitanium stearate, titanium lactate, or butyl titanate dimer, and a liquid material obtained by mixing an alcohol, a Group 2 metal compound of the long form periodic table, and a phosphate ester compound is added.

[0289] In some embodiments, the catalyst is selected from tetra-n-butyl titanate, polyhydroxy titanium stearate, titanium (oxy)acetylacetonate, titanium tetraacetylacetonate, and a liquid material obtained by mixing an alcohol, a Group 2 metal compound of the long form periodic table, and a phosphate ester compound and adding a titanium compound is added.

[0290] Non-limiting examples of zirconium compounds as catalysts include, but are not limited to, zirconium tetraacetate, zirconium acetate hydroxide, zirconium tris(butoxy)stearate, zirconyl diacetate, zirconium oxalate, zirconyl oxalate, potassium zirconium oxalate, polyhydroxyzirconium stearate, zirconium ethoxide, zirconium tetra-n-propoxide, zirconium tetraisopropoxide, zirconium tetra-n-butoxide, zirconium tetra-t-butoxide, zirconium tributoxyacetylacetonate, and mixtures thereof.

[0291] In some embodiments, the catalyst is selected from zirconyl diacetate, zirconium tris(butoxy)stearate, zirconium tetraacetate, zirconium acetate hydroxide, ammonium zirconium oxalate, potassium zirconium oxalate, polyhydroxyzirconium stearate, zirconium tetra-n-propoxide, zirconium tetraisopropoxide, zirconium tetra-n-butoxide, and zirconium tetra-t-butoxide (preferably zirconium tetra-t-butoxide), zirconyl diacetate, zirconium tetraacetate, zirconium acetate hydroxide, zirconium tris(butoxy)stearate, ammonium zirconium oxalate, zirconium tetra-n-propoxide, and zirconium tetra-n-butoxide. In some embodiments, the catalyst is selected from zirconium tris(butoxy)stearate. In some embodiments, colorless polyesters with a high degree of polymerization are readily obtained using zirconium tris(butoxy)stearate.

[0292] In some embodiments, the catalyst is a germanium compound.Non-limiting examples of germanium compounds include, but are not limited to, inorganic germanium compounds such as germanium oxide and germanium chloride; and organic germanium compounds such as tetraalkoxy germanium.From the viewpoint of cost and availability, germanium oxide, tetraethoxy germanium, tetrabutoxy germanium, etc. are preferred, and germanium oxide is particularly preferred.

[0293] In some embodiments, the catalyst is an inorganic chloride. Non-limiting examples of inorganic chlorides include, but are not limited to, ferric chloride, etc.; inorganic oxides, such as iron oxide; organic iron complexes, such as ferrocene; and the like. In some embodiments, the catalyst is an inorganic oxide.

[0294] In some embodiments, the catalyst is a metal-containing compound.Non-limiting examples of metal-containing compounds include, but are not limited to, scandium compounds such as scandium carbonate, scandium acetate, scandium chloride, and scandium acetylacetonate; yttrium compounds such as yttrium carbonate, yttrium chloride, yttrium acetate, and yttrium acetylacetonate; vanadium compounds such as vanadium chloride, vanadium trichloride oxide, vanadium acetylacetonate, and vanadium oxide acetylacetonate; molybdenum compounds such as molybdenum chloride and molybdenum acetate; tungsten compounds such as tungsten chloride, tungsten acetate, and tungstic acid; lanthanoid compounds such as cerium chloride, samarium chloride, and ytterbium chloride; etc.

[0295] polymerization Aspects of the method include polymerizing the alkanediol monomers and the alkanediol monomers in the dispersion to produce a polymer-polysaccharide nanocomposite resin. Polymerization collectively refers to the process of esterifying a monomer, for example to grow an oligomer or polymer chain, and polycondensing an oligomer to form a higher molecular weight (high MW) polymer. The terms polycondensation and condensation are used interchangeably herein. In some embodiments, polycondensation and condensation refer to a process involving the formation of an ester bond between two components of a composition, for example, two oligomers, an oligomer / polymer with polysaccharide nanocrystals, or an oligomer / polymer with an additive such as an epoxidized oil.

[0296] In some embodiments, the polymerizing comprises esterifying the alkanediol monomers and the alkanedioic acid monomers to form a plurality of oligomers, in some embodiments, the polymerizing further comprises condensing the plurality of oligomers to produce a high MW polymer (e.g., as described herein) in the polymer-polysaccharide nanocomposite resin.

[0297] In some embodiments, the oligomers have an average MW of 500 Da or more, up to 10,000 Da, for example, an average MW of 500 Da to 5000 Da. In some embodiments, the oligomers have an average MW of 1000 to 10000 Da, for example, 5000 to 10000 Da. In some embodiments, the oligomers have an average MW of less than 3 kDa.

[0298] In some embodiments, a high MW polymer has a MW of 10 kDa or more, and in some cases up to 100 kDa.

[0299] In some embodiments, the oligomer has the formula (IIa):

[0300] [ka]

[0301] During the ceremony, n is 1 to 11; m is 1 to 11; p is 1 to 100; each * independently represent H, OH, a copolymer segment, a repeat unit, a comonomer, or a grafted polysaccharide nanoparticle.

[0302] In some embodiments of Formula (IIa), p is 1-50, for example, 5-50, 10-50, 10-40, or 20-40.

[0303] In some embodiments, the oligomer is a PBS or PBF homopolymer. In some embodiments, the oligomer is a PBS or PBF copolymer. In some embodiments, the oligomer is represented by formula (IIIa):

[0304] [ka]

[0305] During the ceremony, p is 0 to 50; q is 0 or 50, and p+q>0; r is 1 to 50; each * independently represent H, OH, copolymer segment, repeat unit, comonomer, or grafted polysaccharide nanoparticle. The oligomer may have a total of up to about 50 repeat units. In some cases, the oligomer has an average MW of 1000-10,000 Da.

[0306] In some embodiments of Formula (IIIa), (p+q)r is < 50. In some embodiments of Formula (IIIa), r is 1-50, e.g., 5-50, 10-50, 10-40, or 20-40.

[0307] In some embodiments, the plurality of oligomers and the high MW polymer each comprises a butylene succinate repeat unit. In some embodiments, the oligomer and the high MW polymer each comprises a plurality of butylene succinate repeat units. In some embodiments, the oligomer and the high MW polymer each comprises a block or segment of polybutylene succinate.

[0308] In some embodiments, the polymer of the polymer-polysaccharide nanocomposite resin is a polybutylene succinate homopolymer or a polybutylene succinate copolymer (eg, polybutylene succinate adipate copolymer).

[0309] In some embodiments, the polymerization further comprises condensing the oligomer or polymer with an epoxidized oil or other epoxidized derivative (e.g., as described herein). In such embodiments, the mixture (e.g., dispersion) comprises an epoxidized oil. In some embodiments, the epoxidized oil or other epoxidized derivative (e.g., as described herein) is covalently bonded to the oligomer or polymer, or is covalently bonded via a transesterification process or a coupling process involving the epoxide group of the epoxidized oil or other epoxidized derivative and a compatible functional group of the polymer or polysaccharide nanocrystal. The epoxidized oil or other epoxidized derivative (e.g., as described herein) may contain multiple epoxide groups that provide crosslinking between two or more components of the resulting nanocomposite resin composition, for example, between two or more oligomers or polymers, or between a polymer and a polysaccharide nanocrystal, or between a polymer and another additive moiety. In some embodiments, the epoxidized oil or other epoxidized derivative (e.g., as described herein) provides desirable non-covalent interactions with other additives or components of the resin composition.

[0310] In some embodiments, the polymerization further comprises condensing the nanocomposite resin with an epoxy derivative (e.g., an epoxidized oil or an epoxidized fatty acid (ester) or an epoxidized triglyceride, or other epoxidized derivative capable of esterification, e.g., coupling between an epoxide and a carboxylic acid group). In some embodiments, the epoxidized oil or epoxy derivative (e.g., as described herein) is added in situ to the nanocomposite resin. In some embodiments, the epoxidized oil or epoxy derivative (e.g., as described herein) is added to the reaction mixture before or during polymerization. In some embodiments, the epoxidized oil or epoxy derivative (e.g., as described herein) is added to the reaction mixture before or during esterification of the monomer. In some embodiments, the epoxidized oil or epoxy derivative (e.g., as described herein) is added to the reaction mixture before or during polycondensation of a plurality of oligomers.

[0311] In some embodiments, the epoxidized oil or epoxy derivative includes, but is not limited to, epoxidized linseed oil, as-epoxidized linseed oil, lard, beef tallow, fish oil, coffee oil, soybean oil, safflower oil, tung oil, tall oil, calendula, rapeseed oil, peanut oil, sesame oil, grapeseed oil, olive oil, jojoba oil, dehydrated castor oil, tallow oil, sunflower oil, cottonseed oil, corn oil, canola oil, orange oil, and mixtures thereof. In some embodiments, the epoxidized oil is linseed oil. In some embodiments, the condensation of the nanocomposite resin with the epoxy is configured to improve one or more of the following: hydrolytic stability of the nanocomposite resin, branching for improved processability during melt spinning for yarn production, increased strength (e.g., toughening) of the nanocomposite resin, reduced coloration of the nanocomposite resin, and reduced COOH end groups of the nanocomposite resin. In some embodiments, the condensation of the nanocomposite with the epoxy is configured to improve the hydrolytic stability of the nanocomposite resin. In some embodiments, the condensation of the nanocomposite with the epoxy is configured to provide branching to improve processability during melt spinning of the nanocomposite resin during yarn production. In some embodiments, the condensation of the nanocomposite with the epoxy is configured to increase the strength of the nanocomposite resin. In some embodiments, the condensation of the nanocomposite with the epoxy is configured to reduce coloration of the nanocomposite resin. In some embodiments, the condensation of the nanocomposite with the epoxy is configured to reduce COOH end groups of the nanocomposite resin.

[0312] The present disclosure includes nanocomposite synthetic precursor compositions that include a mixture of a plurality of oligomers (e.g., as described herein), cellulose nanocrystals, and, optionally, one or more reagents or solvents (e.g., as described herein) suitable for polycondensation.

[0313] Esterification Aspects of the method include esterifying alkanediol monomers and alkanedioic acid agent monomers to form a plurality of oligomers or polymers.

[0314] The end groups of the oligomers or polymers of the present disclosure can be capped with various groups. In some examples, the capping group can be epoxidized oil. Esterification of epoxidized oil or epoxy derivatives into polybutylene succinate nanocomposites can increase durability, increase melt viscosity, and reduce the concentration of acid end groups in the polybutylene succinate nanocomposite, making it easier to process and stable against thermal and hydrolytic effects. The resulting polybutylene succinate nanocomposite is biodegradable and consists mainly of ester bonds, with a few ether bonds introduced with one of the reactants.

[0315] In some embodiments, the polycondensing further comprises esterifying the epoxidized oil or epoxy derivative (e.g., the epoxidized oil or epoxy derivative as an additional component).

[0316] In some embodiments, the one or more additional monomers include epoxidized oil, epoxy derivative, or fatty acid. In some embodiments, the epoxidized oil, epoxy derivative, or fatty acid can be esterified. In some embodiments, the epoxy derivative or epoxidized oil is added at the end of the esterification process just before the catalyst is added and polycondensation is performed. In some examples, the catalyst is added after the epoxy derivative or epoxidized oil is allowed to react for 5 minutes. The high shear disperser method follows the same process as the ultrasonication method in terms of time and power consumption, but instead uses the equipment described in https: / / www(dot)mixers(dot)com / products / high-speed-dispersers / .

[0317] In some embodiments, one or more additional monomers are epoxidized oils.In some embodiments, one or more additional monomers are epoxidized derivatives.In some embodiments, epoxidized oils or epoxy derivatives include, but are not limited to, epoxidized linseed oil, linseed oil as epoxidized, lard, beef tallow, fish oil, coffee oil, soybean oil, safflower oil, tung oil, tall oil, calendula, rapeseed oil, peanut oil, sesame oil, grapeseed oil, olive oil, jojoba oil, dehydrated castor oil, tallow oil, sunflower oil, cottonseed oil, corn oil, canola oil, orange oil, and mixtures thereof.

[0318] In some embodiments, the esterification is carried out under vacuum or inert gas conditions. For example, the esterification reaction can be carried out in a reaction vessel with nitrogen gas. The esterification can be carried out at about ambient pressure or slightly higher pressure with any inert gas. The slurry can be heated to a temperature of about 100° C. or higher, about 105° C. or higher, about 110° C. or higher, about 120° C. or higher, about 130° C. or higher, about 140° C. or higher, or about 150° C. or higher to initiate the reaction.

[0319] In some embodiments, the esterification may be carried out in the gas phase.

[0320] In some embodiments, the esterification involves heating the dispersion to an initial temperature of 100° C. to 140° C. (e.g., the esterification is initiated at 110° C.±10° C., 110° C.±5° C., or about 110° C.). In some embodiments, the esterification involves heating the dispersion to an initial temperature of about 100° C. or higher, about 105° C. or higher, about 110° C. or higher, about 120° C. or higher, about 130° C. or higher, about 140° C. or higher, or about 150° C. or higher.

[0321] In some embodiments, the esterification further comprises heating the dispersion to a second temperature of 200° C. to 250° C. (e.g., 225° C.±15° C., or about 225° C.) after the reaction temperature exceeds 140° C. In some embodiments, the esterification further comprises heating the dispersion to a second temperature of 200° C. or higher, 225° C. or higher, 230° C. or higher, 235° C. or higher, 240° C. or higher, 245° C. or higher, or 250° C. or higher after the reaction temperature exceeds 140° C. In some embodiments, the esterification further comprises heating the dispersion to a second temperature of 200° C.±15° C., 215° C.±15° C., 230° C.±15° C., 245° C.±15° C., or 250° C.±15° C. after the reaction temperature exceeds 140° C.

[0322] catalyst In some embodiments, the polymerizing is carried out in the presence of a catalyst. In some embodiments, the rate of the reaction (e.g., esterification, and / or polycondensation and / or transesterification) can be further increased by the addition of a catalyst. In some embodiments, the method further comprises adding a catalyst to the mixture (e.g., dispersion) before or during polymerization. In some embodiments, the catalyst is added during the first step of esterification of the monomers. In some embodiments, the catalyst is added during the second step of polycondensation of multiple oligomers, for example, to facilitate the formation of higher MW polymers.

[0323] Regarding the amount of catalyst added when using a metal compound as such an esterification catalyst, in terms of the amount of metal relative to the polyester formed, the lower limit is generally 0.1 mass ppm or more, preferably 0.5 mass ppm or more, more preferably 1 mass ppm or more, and the upper limit is generally 3,000 mass ppm or less, preferably 2,000 mass ppm or less, more preferably 1,000 mass ppm or less, particularly preferably 500 mass ppm or less. If the amount of catalyst used is too large, it is economically disadvantageous. In addition, the terminal carboxyl group concentration of the polyester may become high. Therefore, there is a concern that the thermal stability and hydrolysis resistance of the polyester will decrease due to the increase in the terminal carboxyl group concentration and the residual catalyst concentration. Conversely, if the amount of catalyst used is too small, the polymerization activity will decrease, which will subsequently induce thermal decomposition of the polyester during the production of the polyester. As a result, the yield of polyesters that exhibit practically useful physical properties is low.

[0324] The timing of adding the catalyst to the reaction system is not particularly limited. In some embodiments, the catalyst is added before the esterification reaction step. In some embodiments, the catalyst may be added at the time of charging the raw material. In some embodiments, the catalyst is added after the esterification reaction step.

[0325] Non-limiting exemplary catalysts include titanium or zirconium compounds, such as, but not limited to, titanium lactate or zirconium butoxide. Generally, compounds containing at least one member of the metal elements belonging to Groups 1 to 14 of the periodic table can be used as esterification reaction catalysts. Specifically, examples of metal elements include scandium, yttrium, samarium, titanium, zirconium, vanadium, chromium, molybdenum, tungsten, tin, antimony, cerium, germanium, zinc, cobalt, manganese, iron, aluminum, magnesium, calcium, strontium, sodium, potassium, and the like. Among these, scandium, yttrium, titanium, zirconium, vanadium, molybdenum, tungsten, zinc, iron, and germanium are preferred, and titanium, zirconium, tungsten, iron, and germanium are particularly preferred. In addition, in order to reduce the concentration of polyester ends that affect the thermal stability of polyesters, metal elements belonging to Groups 3 to 6 of the periodic table and exhibiting Lewis acidity are particularly preferred among the above-mentioned metals. Specific examples of such elements include scandium, titanium, zirconium, vanadium, molybdenum, and tungsten. In particular, titanium and zirconium are preferred from the viewpoint of availability, and titanium is more preferred from the viewpoint of reaction activity.

[0326] In some embodiments, the catalyst includes compounds containing organic groups, such as carboxylates, alkoxy salts, organic sulfonates, or β-diketonate salts, each of which contains such a metal element; as well as inorganic compounds such as oxides, halides, and the like of the above metals, as well as mixtures thereof.

[0327] In some embodiments, the method includes a compound that is liquid or soluble in the ester oligomer or polyester during polymerization. In some embodiments, a compound that is liquid or soluble in the ester oligomer or polyester is added because the polymerization rate is higher when the catalyst is in a molten or dissolved state during polymerization.

[0328] In some embodiments, the esterification is carried out in the absence of a solvent. In some embodiments, the esterification is carried out in the presence of a solvent. In some embodiments, a small amount of solvent may be used to dissolve the catalyst. Non-limiting examples of the solvent used to dissolve the catalyst include alcohols such as methanol, ethanol, isopropanol, butanol, and the like; diols such as ethylene glycol, butanediol, pentanediol, and the like; ethers such as diethyl ether, tetrahydrofuran, and the like; nitriles such as acetonitrile, and the like; hydrocarbon compounds such as heptane, toluene, and the like; water; and mixtures thereof. With regard to the amount of use, the solvent is used so that the catalyst concentration is approximately 0.0001% by weight or more and 99% by weight or less.

[0329] In some embodiments, the catalyst is a titanium compound. In some embodiments, the titanium compound is a tetraalkyl titanate and its hydrolyzates. Non-limiting examples include, but are not limited to, tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, tetra-t-butyl titanate, tetraphenyl titanate, tetracyclohexyl titanate, tetrabenzyl titanate, and mixed titanates thereof, and their hydrolyzates.

[0330] In some embodiments, the catalyst includes titanium(oxy)acetylacetonate, titanium tetraacetylacetonate, titanium(diisopropoxide)acetylacetonate, titanium bis(ammonium lactate)dihydroxide, titanium bis(ethylacetoacetate)diisopropoxide, titanium(triethanolaminate)isopropoxide, polyhydroxytitanium stearate, titanium lactate, titanium triethanolaminate, butyl titanate dimer, etc. In some embodiments, the method further includes adding a liquid material obtained by mixing an alcohol, a Group 2 metal compound of the long form of the periodic table (IUPAC Recommendations for Nomenclature of Inorganic Chemistry 2005) (hereinafter sometimes referred to as "Group 2 metal compound of the long form of the periodic table"), a phosphate ester compound, and a titanium compound.

[0331] In some embodiments, the method includes adding a catalyst selected from tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, titanium (oxy)acetylacetonate, titanium tetraacetylacetonate, titanium bis(ammonium lactate) dihydroxide, polyhydroxytitanium stearate, titanium lactate, or butyl titanate dimer, and adding a liquid material obtained by mixing an alcohol, a Group 2 metal compound of the long form periodic table, and a phosphate ester compound, and adding a titanium compound.

[0332] In some embodiments, the method includes adding a catalyst selected from tetra-n-butyl titanate, titanium (oxy)acetylacetonate, titanium tetraacetylacetonate, polyhydroxytitanium stearate, titanium lactate, or butyl titanate dimer, and adding a liquid material obtained by mixing an alcohol, a Group 2 metal compound of the long form periodic table, and a phosphate ester compound, and adding a titanium compound.

[0333] In some embodiments, the method includes adding a catalyst selected from tetra-n-butyl titanate, polyhydroxy titanium stearate, titanium (oxy)acetylacetonate, titanium tetraacetylacetonate, and adding a liquid material obtained by mixing an alcohol, a Group 2 metal compound of the long form periodic table, and a phosphate ester compound, and adding a titanium compound.

[0334] Non-limiting examples of zirconium compounds as catalysts include, but are not limited to, zirconium tetraacetate, zirconium acetate hydroxide, zirconium tris(butoxy)stearate, zirconyl diacetate, zirconium oxalate, zirconyl oxalate, potassium zirconium oxalate, polyhydroxyzirconium stearate, zirconium ethoxide, zirconium tetra-n-propoxide, zirconium tetraisopropoxide, zirconium tetra-n-butoxide, zirconium tetra-t-butoxide, zirconium tributoxyacetylacetonate, and mixtures thereof.

[0335] In some embodiments, the catalyst is selected from zirconyl diacetate, zirconium tris(butoxy)stearate, zirconium tetraacetate, zirconium acetate hydroxide, ammonium zirconium oxalate, potassium zirconium oxalate, polyhydroxyzirconium stearate, zirconium tetra-n-propoxide, zirconium tetraisopropoxide, zirconium tetra-n-butoxide, and zirconium tetra-t-butoxide (preferably zirconium tetra-t-butoxide), zirconyl diacetate, zirconium tetraacetate, zirconium acetate hydroxide, zirconium tris(butoxy)stearate, ammonium zirconium oxalate, zirconium tetra-n-propoxide, and zirconium tetra-n-butoxide. In some embodiments, the catalyst is selected from zirconium tris(butoxy)stearate. In some embodiments, colorless polyesters with high degrees of polymerization are readily obtained using zirconium tris(butoxy)stearate.

[0336] In some embodiments, the catalyst is a germanium compound.Non-limiting examples of germanium compounds include, but are not limited to, inorganic germanium compounds such as germanium oxide and germanium chloride; and organic germanium compounds such as tetraalkoxy germanium.From the viewpoint of cost and availability, germanium oxide, tetraethoxy germanium, tetrabutoxy germanium, etc. are preferred, and germanium oxide is particularly preferred.

[0337] In some embodiments, the catalyst is an inorganic chloride. Non-limiting examples of inorganic chlorides include, but are not limited to, ferric chloride, etc.; inorganic oxides, such as iron oxide; organic iron complexes, such as ferrocene; and the like. In some embodiments, the catalyst is an inorganic oxide.

[0338] In some embodiments, the catalyst is a metal-containing compound.Non-limiting examples of metal-containing compounds include, but are not limited to, scandium compounds such as scandium carbonate, scandium acetate, scandium chloride, and scandium acetylacetonate; yttrium compounds such as yttrium carbonate, yttrium chloride, yttrium acetate, and yttrium acetylacetonate; vanadium compounds such as vanadium chloride, vanadium trichloride oxide, vanadium acetylacetonate, and vanadium oxide acetylacetonate; molybdenum compounds such as molybdenum chloride and molybdenum acetate; tungsten compounds such as tungsten chloride, tungsten acetate, and tungstic acid; lanthanoid compounds such as cerium chloride, samarium chloride, and ytterbium chloride; etc.

[0339] condensation Aspects of the present disclosure include esterifying alkanediol monomers and alkanedioic acid agent monomers to form a plurality of oligomers and condensing the plurality of oligomers to produce a high MW polymer in the polymer-polysaccharide nanocomposite resin.

[0340] In some embodiments, condensing the plurality of oligomers is performed in a reaction vessel under reduced pressure. In some embodiments, the pressure of the vessel may be reduced during condensation. In some embodiments, the condensing is performed at a pressure of about 500 mTorr. In some embodiments, the condensing is performed at a pressure of about 400 mTorr. In some embodiments, the condensing is performed at a pressure of about 300 mTorr. In some embodiments, the pressure may be reduced from an initial pressure of about 700 Torr (i.e., atmospheric pressure) to a final pressure of about 500 mTorr. In some embodiments, the pressure may be reduced from an initial pressure of about 710 Torr (i.e., atmospheric pressure) to a final pressure of about 500 mTorr. In some embodiments, the pressure may be reduced from an initial pressure of about 720 Torr (i.e., atmospheric pressure) to a final pressure of about 500 mTorr. In some embodiments, the pressure may be reduced from an initial pressure of about 730 Torr (i.e., atmospheric pressure) to a final pressure of about 500 mTorr. In some embodiments, the pressure may be reduced from an initial pressure of about 740 Torr (i.e., atmospheric pressure) to a final pressure of about 500 mTorr. In some embodiments, the pressure may be reduced from an initial pressure of about 750 Torr (i.e., atmospheric pressure) to a final pressure of about 500 mTorr. In some embodiments, the pressure may be reduced from an initial pressure of about 760 Torr (i.e., atmospheric pressure) to a final pressure of about 500 mTorr. In some embodiments, the pressure may be reduced from an initial pressure of about 770 Torr (i.e., atmospheric pressure) to a final pressure of about 500 mTorr.

[0341] In some embodiments, the method includes pressurizing the reaction vessel at an initial pressure, heating the reaction vessel, and subsequently reducing the initial pressure to a lower pressure.

[0342] In some embodiments, the pressure may be reduced from an initial pressure of about 780 Torr (i.e., atmospheric pressure) to a final pressure of about 500 mTorr. In some embodiments, the pressure may be reduced from an initial pressure of about 790 Torr (i.e., atmospheric pressure) to a final pressure of about 500 mTorr. In some embodiments, the pressure may be reduced from an initial pressure of about 800 Torr (i.e., atmospheric pressure) to a final pressure of about 500 mTorr.

[0343] After esterification, the reaction vessel can be heated to about 225° C. to condense multiple oligomers to produce high MW polymers in the polymer-polysaccharide nanocomposite resin.

[0344] In some embodiments, the presence of a high MW polymer in a resin composition can be determined by evaluating or measuring the viscosity of the resin, e.g., intrinsic viscosity (dL / g). In some embodiments, the polymer-polysaccharide nanocomposite resin comprises a high MW polymer and provides an intrinsic viscosity of about 0.8 to about 1.5 dL / g, about 0.9 to about 1.5 dL / g, measured at 20° C. using a capillary-based automated dilution viscometer as described herein.

[0345] In some embodiments, the temperature of the vessel may be gradually increased as the reaction proceeds, hi some embodiments, the temperature may be increased to about 200° C. or more, 210° C. or more, 220° C. or more, 230° C. or more, 240° C. or more, or 250° C. or more.

[0346] In some embodiments, the method includes adding an epoxy derivative or epoxidized oil at the end of the reaction. For example, in some embodiments, the epoxy derivative or epoxidized oil can be added after repressurizing the vessel just prior to cooling and discharging the polymer. In some embodiments, the method includes adding one or more additional components after polymerization of the nanocomposite.

[0347] Use of polymer-polysaccharide nanocomposite resins in yarn / fiber fabrication Aspects of the present disclosure include articles comprising the nanocomposite resins produced by the methods described herein.

[0348] In some embodiments, an article is manufactured from the nanocomposite resin using any known method, non-limiting examples of which include, but are not limited to, injection molding, blow molding, compression molding, extrusion, and melt spinning. In some embodiments, the article is a molded article molded from the nanocomposite resin of the present disclosure.

[0349] In some embodiments, the article is a yarn or fiber.

[0350] In some embodiments, the polysaccharide-polymer nanocomposite resin (e.g., polybutylene succinate nanocomposite) produced by the present method can then be formed into an article of manufacture. For example, in some embodiments, the process can include thermoforming, extruding, injection molding, or blow molding the composition in molten form.

[0351] The nanocomposite resins of the present disclosure provide a variety of desirable properties and are used in articles where such properties are critical. In certain embodiments, the in situ addition of polysaccharide nanocrystals is configured to increase the tensile strength and Young's modulus of the nanocomposite resin. In certain embodiments, the in situ addition of polysaccharide nanocrystals increases the biodegradability of articles produced from the nanocomposite resin. In certain embodiments, the in situ addition of polysaccharide nanocrystals reduces gas and / or moisture permeation through articles produced from the nanocomposite resin manufacturing. In some embodiments, the polysaccharide nanocrystals are nucleating agents. In certain embodiments, the polysaccharide nanocrystals function as cationic dyeability sites in articles produced from the nanocomposite resin manufacturing. In certain embodiments, the polysaccharide nanocrystals are compatibilizers for melt processing / spinning of nanocomposites during yarn or fiber manufacturing.

[0352] In some embodiments, the polysaccharide nanocrystals in the nanocomposite resin derived from chitosan provide improved properties to articles made from the nanocomposite resin. In some embodiments, the improved properties to the article include one or more of the article's flame retardancy, increased antimicrobial properties, and improved biodegradability. In some embodiments, the article is a yarn or fiber.

[0353] In some embodiments, an injection molding process includes any molding process in which a polymer melt or a monomer or oligomer solution is forced under pressure, for example with a ram injector or reciprocating screw, into a mold where it is shaped and cured. A blow molding process can include any method in which an extrudable polymer composition can be shaped with a fluid and then cured to form a product. Blow molding processes can include extrusion blow molding, injection blow molding, and injection stretch blow molding, as appropriate. Non-limiting examples of extrusion molding methods include methods in which an extrudable polymer composition is extruded through a die under pressure and cured to form a final product, for example, a film or fiber.

[0354] In some embodiments, a single or twin screw extruder can be used, the selection of which and the amount of each component varies depending on the extruder and is within the skill of the art. Other forming methods can include gas foaming, bead foaming, T-dye film forming, stretch blow molding, blown film forming, and sheet forming.

[0355] In some embodiments, the resulting molded article is a container. As used herein, the term "container" includes, but is not limited to, any article, receptacle, or container that is utilized to store, distribute, package, portion, or transport various types of products or objects, including, but not limited to, food and beverage products. Non-limiting examples of such containers include, but are not limited to, boxes, cups, "clamshells," jars, bottles, plates, bowls, trays, cartons, cases, crates, cereal boxes, frozen food boxes, milk cartons, beverage container carriers, plates, egg cartons, lids, straws, envelopes, stacks, bags, baggies, or other types of holders. Containment products and other products used in combination with the container are also intended to be included within the term "container."

[0356] In some embodiments, the molded article is a containment product that is a closure. As used herein, the term "closure" includes, but is not limited to, any containment product, such as a cap, lid, liner, divider, wrapper, film, cushioning material, and any other product used to package, store, transport, divide, serve, or dispense an object in a container. Non-limiting examples of closures include, but are not limited to, screw caps, snap-on caps, tamper-resistant, tamper-evident, and child-resistant closures or caps.

[0357] Exemplary embodiments As described herein, the text refers to various embodiments of the compounds, compositions, and methods. The various embodiments described are intended to provide various illustrative examples and should not be interpreted as descriptions of alternative species. Rather, it should be noted that the descriptions of the various embodiments provided herein may be of overlapping scope. The embodiments described herein are merely illustrative and are not meant to limit the scope of the technology.

[0358] Regardless of the scope of the claims appended hereto, aspects of the present disclosure are set forth in the following paragraphs.

[0359] Item 1. A method for producing a polymer-polysaccharide nanocomposite resin, comprising: A mixture comprising: an alkanediol monomer; an alkanedioic acid agent monomer; polysaccharide nanocrystals dispersed in the mixture; A catalyst; and one or more optional additives. and polymerizing under conditions sufficient to produce a polymer-polysaccharide nanocomposite resin.

[0360] Item 2. The method according to Item 1, wherein the catalyst is a Lewis acid catalyst.

[0361] Item 3. The method according to Item 2, wherein the catalyst is a metal-based Lewis acid catalyst.

[0362] Item 4. The method according to Item 2 or 3, wherein the metal-based Lewis acid catalyst comprises a transition metal catalyst.

[0363] Item 5. The method according to item 4, wherein the transition metal catalyst comprises a metal selected from aluminum, tin, titanium, zirconium, iron, copper, zinc, hafnium and molybdenum.

[0364] Item 6. The method according to any one of Items 3 to 5, wherein the metallic Lewis acid catalyst comprises an alkali metal catalyst or an alkaline earth metal catalyst.

[0365] Item 7. The method of item 6, wherein the catalyst comprises an alkaline earth metal selected from calcium, magnesium, and strontium.

[0366] Item 8. The method according to item 6 or 7, wherein the metal-based Lewis acid catalyst comprises a transition metal and an alkaline earth metal.

[0367] Item 9. The method according to any one of Items 3 to 8, wherein the metallic Lewis acid catalyst is a mixed metal oxide catalyst.

[0368] Item 10. The method of any one of items 3 to 9, wherein the catalyst comprises one or more components selected from magnesium acetate, zirconium acetate, zirconium butoxide, Na2MoO4, ZnMoO4, and hafnium salts.

[0369] Item 11. The method according to any one of Items 3 to 10, wherein the catalyst further comprises a chelating agent.

[0370] Item 12. The method of item 11, wherein the chelating agent is of biological origin (e.g., a compound or material of biological origin produced by a plant, fungus, or microorganism).

[0371] Item 13. The method according to item 11 or 12, wherein the chelating agent is selected from kojic acid (5-hydroxy-2-(hydroxymethyl)-4-pyrone), furaneol (4-hydroxy-2,5-dimethyl-3-furanone), maltol (3-hydroxy-2-methyl-4H-pyran-4-one), and maple lactone (3-methylcyclopentane-1,2-dione).

[0372] Item 14. The method according to any one of items 1 to 13, wherein the catalyst is added to the mixture as a liquid catalyst composition comprising a mixed metal oxide catalyst and a chelating agent dissolved in a glycol solvent (e.g., an ethylene glycol or propylene glycol solvent).

[0373] Item 15. The method of item 1 or 2, wherein the catalyst is an aluminosilicate mineral (e.g., magnesium aluminum phyllosilicate clay or acti-gel 208).

[0374] Item 16. The method according to item 15, wherein the catalyst is selected from kaolin, kaolinite, zeolite, illite, attapulgite, palygorskite, and bentonite.

[0375] Item 17. The method according to item 1 or 2, wherein the catalyst is an organic catalyst comprising a protic ionic salt.

[0376] Item 18. The method according to item 1 or 2, wherein the catalyst is non-metallic and contains a sulfonic acid group or a salt thereof.

[0377] Item 19. The method of any one of items 1 to 18, wherein the catalyst is added to the reaction mixture as a liquid catalyst composition further comprising dispersed polysaccharide nanocrystals.

[0378] Item 20. The method according to any one of items 1 to 19, wherein the produced polymer-polysaccharide nanocomposite resin exhibits an intrinsic viscosity of about 0.9 to about 1.5 dL / g (for example, when measured at 20°C using a capillary-based viscometer).

[0379] Item 21. The method of any one of items 1 to 19, wherein the polymerization comprises esterifying alkanediol monomers and alkanediacid monomers to produce a plurality of oligomers, and polycondensing the plurality of oligomers in the presence of polysaccharide nanocrystals to produce a high MW polymer in the polymer-polysaccharide nanocomposite resin.

[0380] Item 22. The method according to item 21, wherein the esterification step and the polycondensation step are carried out sequentially (e.g., under different reaction conditions of temperature and pressure).

[0381] Item 23. The method according to item 21 or 22, wherein the esterification step and the condensation step are carried out in the same reaction vessel (for example, under the same reaction conditions of temperature and pressure).

[0382] Clause 24. The method of clause 21, wherein the plurality of oligomers have an average MW of less than 3 kDa and the high MW polymer has an average MW of 10 kDa or more.

[0383] Item 25. The method of any one of items 21 to 24, wherein the esterification comprises heating the mixture at an initial temperature of 100° C. to 140° C.

[0384] Item 26. The method of item 25, wherein the esterification further comprises heating the mixture to a second temperature of 200°C to 250°C after the reaction temperature exceeds 140°C.

[0385] Section 27. The polycondensation of the oligomers is carried out in a reaction vessel under reduced pressure (e.g., a pressure of about 500 mTorr or less); and / or 27. The method according to any one of items 21 to 26, wherein the polycondensation of the multiple oligomers is carried out at a reaction temperature of 200°C to 250°C.

[0386] Item 28. The method according to item 21, wherein the esterification step and the polycondensation step are carried out in a one-pot reaction under a set of reaction conditions sufficient to produce a polymer-polysaccharide nanocomposite resin.

[0387] Item 29. The method according to Item 28, wherein the plurality of polycondensation polymers in the resin have an average MW of 10 kDa or more.

[0388] Item 30. The method of any one of items 1 to 28, further comprising pelletizing the polymer-polysaccharide nanocomposite resin to produce resin pellets, and optionally drying the pellets (e.g., under conditions sufficient to increase the average MW of the polymer in the polymer-polysaccharide nanocomposite resin).

[0389] Item 31. The method according to any one of items 1 to 30, wherein the mixture is precombined and contains a catalyst when the polymerization reaction is initiated.

[0390] Item 32. The method according to any one of items 1 to 30, wherein the catalyst is added to the reaction mixture after the initiation of polymerization.

[0391] Item 33. The method of item 32, wherein a catalyst is added to the mixture to catalyze the esterification of the monomer.

[0392] Item 34. The method of item 32, wherein a catalyst is added to the mixture to catalyze the polycondensation of the plurality of oligomers.

[0393] Item 35. The method according to any one of items 1 to 34, wherein the polymerization is carried out in the presence of an additive that is an epoxidized lipid (e.g., an epoxidized oil, an epoxidized triglyceride, an epoxidized fatty acid ester, or an epoxidized terpene).

[0394] Item 36. The method of item 35, wherein the epoxidized lipid is added to the reaction mixture after the initiation of polymerization.

[0395] Item 37. The method of item 35 or 36, wherein the polymerization further comprises condensing the oligomer or polymer of the reaction mixture with an epoxidized lipid (e.g., an epoxidized oil).

[0396] Item 38. The method according to any one of items 1 to 37, further comprising condensing the polymer-polysaccharide nanocomposite resin with an epoxidized lipid (e.g., an epoxidized oil, an epoxidized triglyceride, an epoxidized fatty acid ester, or an epoxidized terpene).

[0397] Item 39. The method according to any one of items 35 to 38, wherein the epoxidized lipid is an epoxidized oil.

[0398] Item 40. The method according to item 39, wherein the epoxidized oil is derived from one or more fatty acids selected from linolenic acid, oleic acid, linoleic acid, palmitic acid and stearic acid.

[0399] Item 41. The method according to Item 39 or 40, wherein the epoxidized oil is epoxidized linseed oil.

[0400] Item 42. The method according to any one of items 1 to 41, wherein the polysaccharide nanocrystals are derived from cellulose, starch or chitin.

[0401] Item 43. The method according to any one of items 1 to 42, wherein the polysaccharide nanocrystals are cellulose nanocrystals.

[0402] Item 44. The method of item 43, wherein the cellulose nanocrystals are derived from acid hydrolyzed cellulose from sources wood, cotton, bacteria, or algae.

[0403] Item 45. The method according to item 43 or 44, wherein the cellulose nanocrystals have average dimensions of about 3 to about 50 nm in width and about 100 to about 1000 nm in length.

[0404] Item 46. The method according to any one of items 1 to 45, wherein the alkanediol monomer is selected from 1,4-butanediol, 1,3-propanediol, and 1,2-ethanediol.

[0405] Item 47. The method according to item 46, wherein the alkanediol monomer is 1,4-butanediol.

[0406] Item 48. The method according to any one of items 1 to 47, wherein the alkanedioic acid agent monomer is selected from succinic acid, monoalkyl succinates, dialkyl succinates (e.g., dimethyl succinate or diethyl succinate), succinic anhydride, adipic acid, monoalkyl adipates, dialkyl adipates (e.g., dimethyl adipate or diethyl adipate), and adipic anhydride.

[0407] Item 49. The method of item 48, wherein the alkanedioic acid agent monomer is succinic anhydride.

[0408] Item 50. A method for producing a polybutylene succinate-cellulose nanocomposite resin, preparing a mixture comprising dispersed cellulose nanocrystals, 1,4-butanediol monomer, succinic acid monomer, a metal oxide catalyst, a chelating agent, and optional additives; Item 50. The method according to any one of items 1 to 49, comprising polymerizing the 1,4-butanediol monomer and the succinic acid monomer in the dispersed mixture to produce a polybutylene succinate-cellulose nanocomposite resin.

[0409] Item 51. The preparation of the mixture, a cellulose nanocrystal-catalyst dispersion comprising cellulose nanocrystals dispersed in a solution of a metal oxide catalyst and a chelating agent; 50. The method of any one of paragraphs 1 to 49, comprising combining a monomer mixture of 1,4-butanediol monomer, succinic acid monomer, and optional additives.

[0410] Clause 52. The method of clause 50, wherein the cellulose nanocrystals are derived from acid hydrolyzed cellulose from sources such as wood, cotton, bacteria, or algae.

[0411] Item 53. The method of item 51 or 52, wherein the cellulose nanocrystals have average dimensions of about 3 to 50 nm in width and about 100 to 1000 nm in length.

[0412] Item 54. The method of any one of items 51 to 53, wherein the succinic acid agent monomer is selected from succinic acid, monoalkyl succinates, dialkyl succinates (e.g., dimethyl succinate or diethyl succinate), and succinic anhydride.

[0413] Item 55. The method of item 54, wherein the alkanedioic acid agent monomer is succinic anhydride.

[0414] Item 56. The method according to any one of items 1 to 55, wherein the mixture (e.g., the dispersion) further comprises one or more additional monomers and / or an epoxidized lipid.

[0415] Item 57. The method of item 55, wherein the plurality of oligomers and the high MW polymer each comprise butylene succinate repeat units.

[0416] Item 58. The method according to any one of items 1 to 57, wherein the polymer of the polymer-polysaccharide nanocomposite resin is a polybutylene succinate homopolymer or a polybutylene succinate copolymer.

[0417] Item 59. The method according to any one of items 1 to 58, wherein the preparation of the mixture (e.g., dispersion) comprises dispersing cellulose nanocrystals in a monomer solution (e.g., homogeneous solution) containing one or both of an alkanediol monomer and an alkanediol monomer.

[0418] Item 60. The method of item 59, wherein the monomer solution comprises an alkanediol monomer and an alkanedioic acid monomer in a solvent.

[0419] Item 61. The method of item 59 or 60, wherein the monomer solution further comprises a catalyst.

[0420] Item 62. The method according to any one of items 59 to 61, wherein the monomer solution further contains a non-aqueous organic solvent.

[0421] Item 63. The method according to any one of items 59 to 61, wherein the monomer solution further contains water.

[0422] Item 64. Variance is contacting the cellulose nanocrystals with a solution comprising 1,4-butanediol (BDO) and succinic anhydride to produce a cellulose mixture; Item 64. The method according to any one of items 59 to 63, comprising sonicating the cellulose mixture to homogeneously disperse the cellulose nanocrystals in the solution to produce a dispersion.

[0423] Item 65. The method of item 64, wherein the ultrasonic treatment of the cellulose mixture is carried out under conditions sufficient to produce a dispersion in which there is no visible settling.

[0424] Item 66. The method of item 64 or 65, wherein the sonication of the cellulose mixture comprises sonication for a duration of about 5 minutes or more.

[0425] Item 67. The method according to any one of items 1 to 66, wherein the polysaccharide nanocrystals are derived from chitin.

[0426] Item 68. The method according to any one of items 1 to 18, further comprising preparing a dispersion of polysaccharide nanocrystals in a premixed solution.

[0427] Item 69. The method according to item 68, wherein the premixed solution does not contain a catalyst.

[0428] Item 70. The method of item 68, wherein the premixed solution further comprises a catalyst.

[0429] Item 71. The method of item 70, wherein the polysaccharide nanocrystals and catalyst are heated in a premixed solution prior to addition to the reaction mixture.

[0430] Item 72. The method of item 71, wherein the catalyst comprises a transition metal oxide catalyst.

[0431] Item 73. The method of item 71 or 72, wherein the catalyst is a mixed metal oxide catalyst.

[0432] Item 74. The method of any one of items 68 to 73, wherein the dispersed polysaccharide nanocrystals are cellulose nanocrystals.

[0433] Item 75. The method according to any one of items 68 to 74, wherein the premix solution is added to the reaction mixture after the start of polymerization.

[0434] Item 76. The method of item 75, wherein the premix solution is added prior to polycondensation of the oligomers in the reaction mixture.

[0435] Item 77. The method according to any one of items 68 to 76, wherein the polymerization is carried out in the presence of an epoxidized oil additive (e.g., ELO or ESO).

[0436] Item 78. The method of item 77, wherein the epoxidized oil is added to the reaction mixture after the initiation of polymerization and before polycondensation of the oligomers in the reaction mixture.

[0437] Item 79. The method of item 77, wherein an epoxidized oil is added to the reaction mixture prior to the start of polymerization.

[0438] Item 80. A nanocomposite resin produced according to any one of items 1 to 79.

[0439] Item 81. The nanocomposite resin according to item 80, wherein the resin exhibits an intrinsic viscosity of about 0.9 to about 1.5 dL / g (for example, when measured at 20 ° C. using a capillary-based viscometer).

[0440] Item 82. An article comprising the nanocomposite resin according to item 80 or 81.

[0441] Item 83. The article of item 82, wherein the article is manufactured from the nanocomposite resin using a process selected from injection molding, blow molding, compression molding, extrusion, and melt spinning.

[0442] Item 84. The article according to item 82 or 83, wherein the article is a molded article.

[0443] Item 85. The article according to item 82 or 83, wherein the article is a yarn or fiber. EXAMPLES

[0444] The following examples are provided to illustrate the present disclosure and should not be interpreted as limiting the scope of the present technology in any way. Any method that is functionally equivalent is within the scope of the present technology. In addition to those described herein, various modifications of the present technology will be apparent to those skilled in the art from the foregoing description and the accompanying drawings. Such modifications fall within the scope of the appended claims.

[0445] Overall evaluation method The nanocomposite resins of the present disclosure and articles (eg, fibers) made therefrom can be evaluated by a variety of methods.

[0446] intrinsic viscosity Intrinsic viscosity measurements can be performed according to ASTM D445 and D2515 test methods, or the method described by Maron and Reznik ("A new method for determination of intrinsic viscosity." Journal of Polymer Science Part A-2: Polymer Physics, Volume 7, Issue 2, February 1969, Pages 309-32). For example, by using a capillary-based automatic dilution viscometer, the intrinsic viscosity can be measured under the following conditions: capillary constant = 0.003 mm 2 / s 2 , temperature = 20°C, solvent = chloroform, and five concentration levels can be measured.

[0447] Viscosity / Rheology Polymeric materials exhibit viscoelastic behavior that is directly related to differences in molecular structure and formulation. To accurately evaluate molecular structure and viscoelastic behavior, experiments such as rheological measurements can be performed in a region where the observed viscoelastic properties are independent of the imposed stress or strain level, e.g., the linear viscoelastic region. Evaluations can be performed using a parallel plate rheometer following the method of Cox WP, Merz EH (1958) Correlation of dynamic and steady-flow viscosities. J Polym Sci 28:619-622. Exemplary conditions; 25 mm plate, 1 mm gap, polymer resin loaded as pellets. Experiments under nitrogen (4-5 L / min): temperature sweep (140-200 °C), strain amplitude sweep (1-10%), frequency sweep (1-500 / s), time-temperature superposition, Cox-Merz law.

[0448] Tensile strength test of PBS nanocomposite Tensile strength testing can be performed according to ASTM D882-18: Standard Test Method for Tensile Properties of Thin Plastic Sheets. Briefly, the material is placed in a 20,000 lbs hot press at 145°C for 15 minutes. The thickness of the sheet is controlled to about 1 mm by a spacer. The sample is then cut into strips of 50 mm x 10 mm, and a gauge length of about 30 mm is used for testing. The sample is kept at 20°C with a moisture content of about 65% for either 24 or 72 hours. The sample is placed in an Instron mechanical grip and subjected to a crosshead speed of 6 mm / min. The thickness of the sample is measured as the average thickness at five different points along the gauge length.

[0449] Example 1: Pure PBS made from succinic acid + butanediol 113.55 g of 1,4 butanediol (BDO) and 141.71 g of succinic acid (SA) are charged to a 1 L glass reaction vessel. The reactants are stirred at 150 rpm with N2 flow until a homogenous slurry is formed. The temperature is then increased to 225°C over approximately 100 minutes, and the reaction mixture is continuously stirred. During this increase, water and THF are formed and removed from the reactor via a distillation apparatus. When the reaction reaches 225°C, 600 uL of catalyst is added (80 wt% zirconium butoxide (ZBO) in 1-butanol, 470 ppm [Zr] total) and the pressure in the vessel is gradually reduced over approximately 1.5 hours to a final pressure of approximately 500 mTorr. The temperature is increased to 230°C, and the polycondensation reaction is allowed to proceed from this point for 3 hours. The vessel is repressurized and cooled to 110°C before the polymer is removed. The reaction takes about 6 hours in total and produces a beige semi-crystalline polymer.

[0450] Example 2: PBS with 0.1 wt% nanocrystalline cellulose (SA+BDO method) 112.26 g of 1,4 butanediol (BDO) and 140.09 g of succinic acid (SA) are charged to a 1 L glass reaction vessel. The reactants are stirred at 150 rpm with N2 flow until a homogenous slurry is formed. 5.4 mL of a 4.8 wt% nanocrystalline cellulose (NCC) dispersion in DI water is added to the slurry to reach a total NCC concentration of about 0.1 wt%. The temperature is then increased to 225°C over about 2 hours, with the reaction mixture being continuously stirred. During this increase, water and THF are formed and removed from the reactor via a distillation apparatus. When the reaction reaches 225°C, a quantity of catalyst is added (80 wt% zirconium butoxide (ZBO) in 1-butanol, 470 ppm [Zr] total) and the pressure in the vessel is gradually reduced to a final pressure of about 500 mTorr over about 2 hours. The temperature is increased to 230°C and the polycondensation reaction is allowed to proceed for one hour from this point. The vessel is repressurized and cooled to 110°C before the polymer is removed. The reaction takes approximately five hours in total and produces a beige semi-crystalline polymer.

[0451] Example 3: PBS with 0.4 wt% ELO (SA+BDO method) 113.55 g of 1,4 butanediol (BDO) and 141.71 g of succinic acid (SA) are charged to a 1 L glass reaction vessel. The reactants are stirred at 150 rpm with N2 flow until a homogenous slurry is formed. The temperature is then increased to 225°C over approximately 2 hours, with the reaction mixture being continuously stirred. During this increase, water and THF are formed and removed from the reactor via a distillation apparatus. When the reaction reaches 225°C, 600 uL of catalyst is added (80 wt% zirconium butoxide (ZBO) in 1-butanol, 470 ppm [Zr] total) and the pressure in the vessel is gradually reduced over approximately 1.5 hours to a final pressure of approximately 500 mTorr. The temperature is increased to 230°C, and the polycondensation reaction is allowed to proceed for 2 hours from this point. The vessel is repressurized and 1.03 g of epoxidized linseed oil (ELO) is added to the melt and allowed to react for 15 minutes. The vessel is then cooled to 110° C. before the polymer is removed. The reaction takes approximately 7 hours in total and produces a beige semi-crystalline polymer.

[0452] Example 4: PBS with 0.1 wt% NCC + 0.4 wt% ELO (SA + BDO method) 97.79 g of 1,4 butanediol (BDO) and 122.05 g of succinic acid (SA) are charged to a 1 L glass reaction vessel. The reactants are stirred at 150 rpm with N2 flow until a homogenous slurry is formed. 4.7 mL of a 4.8 wt% dispersion of NCC in DI water is added to the slurry to give a total NCC concentration of about 0.1 wt%. The temperature is then increased to 225°C over about 2 hours while the reaction mixture is continuously stirred. During this increase, water and THF are formed and removed from the reactor via a distillation apparatus. When the reaction reaches 225°C, 600 uL of catalyst is added (80 wt% zirconium butoxide (ZBO) in 1-butanol, 470 ppm [Zr] total) and the pressure in the vessel is gradually reduced to a final pressure of about 500 mTorr over about 1 hour. The temperature is increased to 230°C and the polycondensation reaction is allowed to proceed for 1 hour from this point. The vessel is repressurized and 0.89g of ELO is added to the melt and allowed to react for 15 minutes. The vessel is then cooled to 110°C before the polymer is removed. The reaction takes approximately 4.5 hours in total and produces a beige semi-crystalline polymer.

[0453] Example 5: PBS with 1 wt% NCC (SA+BDO method) 97.79 g of 1,4 butanediol (BDO) and 122.05 g of succinic acid (SA) are charged to a 1 L glass reaction vessel. The reactants are stirred at 150 rpm with N2 flow until a homogenous slurry is formed. 46.64 mL of a 4.8 wt% dispersion of NCC in DI water is added to the slurry to give a total NCC concentration of about 1 wt%. The temperature is then increased to 225°C over about 2 hours and the reaction mixture is continuously stirred. During this increase, water and THF are formed and removed from the reactor via a distillation apparatus. The reactants are dark brown in color. When the reaction reaches 225°C, an amount of catalyst is added (80 wt% zirconium butoxide (ZBO) in 1-butanol, 470 ppm [Zr] total) and the pressure in the vessel is gradually reduced to a final pressure of about 500 mTorr over about 2 hours. The temperature is increased to 230°C, at which point the polycondensation reaction is allowed to proceed for approximately 15 minutes, terminating prematurely due to the high viscosity of the polymer. The vessel is repressurized and cooled to 110°C before the polymer is removed. The reaction takes approximately 4.5 hours in total, producing a dark brown brittle polymer.

[0454] Example 6: PBS with 0.1 wt% NCC + 0.4 wt% ELO succinic anhydride + BDO Charge 115.35g BDO and 128.09g succinic anhydride (SAn) to a 1L reaction vessel. The reaction is stirred at 150 rpm with N2 flow until a homogenous slurry is formed. 23.95g of 1 wt% BDO and NCC dispersion is added to the reaction vessel and the reaction temperature is increased to 110°C over 30 minutes. As the reaction reaches 110°C, an endotherm occurs and is measured via a thermocouple probe. Shortly after a large exotherm occurs, the temperature increases to a maximum of about 135°C. The temperature is then increased to 225°C over 1 hour. During this increase, water is formed and removed from the reactor. When the reaction reaches 225°C, 575uL of catalyst is added (80wt% zirconium butoxide (ZBO) in 1-butanol, 470ppm [Zr] total) and the pressure in the vessel is gradually reduced over approximately 1 hour to a final pressure of approximately 500mTorr. The temperature is then increased to 230°C. From this point onwards the reaction proceeds for an hour, but may stop. The vessel is repressurized and 1g of ELO is added to the mixture and allowed to react for approximately 15 minutes. The reaction takes approximately 3.5 hours and produces a very tough material with a high melt viscosity that lends itself to processing.

[0455] Example 7: PBS with 0.1 wt% NCC + 0.4 wt% ELO succinic anhydride + BDO 491.31 g of BDO and 513.36 g of succinic anhydride (SAn) are charged to a 2 L reaction vessel. The reaction is stirred at 190 rpm with N2 flow until a homogenous slurry is formed. 114.11 g of a 1 wt % dispersion of BDO and NCC is added to the reaction vessel and the reaction temperature is increased to 225° C. over 110 minutes. As the reaction reaches 130° C., a mild endotherm occurs and is measured via a thermocouple probe. Shortly after the exotherm occurs, the temperature rises to a maximum of about 155° C., where it stabilizes and continues to rise to 225° C. During this rise, water is formed and removed from the reactor. When the reaction reaches 225°C, 2.45g of catalyst is added (80 wt% zirconium butoxide (ZBO) in 1-butanol, 470 ppm [Zr] total) and the pressure in the vessel is gradually reduced over about 1 hour to a final pressure of about 500 mTorr. The temperature is then increased to 230°C. From this point on, the stirring speed is gradually slowed to 50 rpm for 30 minutes as the reaction proceeds and the viscosity of the melt increases. The vessel is repressurized and 4g of ELO is added to the mixture and allowed to react for about 15 minutes. 0.6g of a 50 wt% solution of phytic acid in DI water is then added as a heat stabilizer and decolorizer. The reaction takes about 4 hours and produces a very tough, high melt viscosity material that is useful for processing.

[0456] Example 8(A): PBS Benchmark Example 9(B): PBS Epoxide Capping Example 10(C): PBS NCC Stretching Example 11(D): PBS NCC stretched, epoxide capped Example 12(E): NCC stretched 10x in PBS, epoxide capped Example 13(F): PBS SAn NCC stretched, epoxide capped Example 14(G): PBS NCC + Epoxide Stretching, Sonication Method Example 15(H): PBS NCC + Epoxide stretching, high shear dispersion method As indicated above, the term "capping" is defined herein as a reactant (in this case ELO) that is added at the end of the reaction. In Examples 9, 11, 12, and 13, this means that ELO is added after repressurizing the vessel just before cooling and discharging the polymer. The term "stretching" is defined as the reactants (NCC, ELO) are added up front with BDO and SA or SAn. In Examples 11, 12, and 13, NCC is added in the form of a dispersion at the beginning of the reaction. In Examples 14 and 15, ELO is added at the end of the esterification process just before the catalyst is added and polycondensation takes place. In these examples, ELO is allowed to react for 5 minutes before the catalyst is added.

[0457] The high shear disperser method follows the same process as the ultrasonication method in terms of time and power consumption, but instead uses the equipment described at https: / / www(dot)mixers(dot)com / products / high-speed-dispersers / .

[0458] Sonication of Cellulose-BDO Mixtures The cellulose-BDO mixture is prepared by either: i) preparing a 1 wt% solution of NCC in 1,4 butanediol in a 40 mL scintillation vial by combining approximately 20 g of reactants, or ii) adding approximately 20 g of a 4.8 wt% dispersion of NCC in DI water (provided by CelluForce) to a 40 mL scintillation vial. The cellulose-BDO mixture is pulse sonicated at 60% amplitude for a total of 5 minutes using a Qsonica Q55 ultrasonic homogenizer (available from Qsonica LLC) with a stainless steel probe tip (55 W). The complete cellulose-BDO dispersion is added to the slurry under mixing and N2.

[0459] Tensile strength test of PBS nanocomposite Tensile strength testing for PBS nanocomposites is performed according to ASTM D882-18: Standard Test Method for Tensile Properties of Thin Plastic Sheets. Briefly, the material is placed in a 20,000 lbs hot press at 145°C for 15 minutes. The thickness of the sheet is controlled to about 1 mm by a spacer. The sample is then cut into strips of 50 mm x 10 mm, and a gauge length of about 30 mm is used for testing. The sample is kept at 20°C with a moisture content of about 65% for either 24 or 72 hours. The sample is placed in an Instron mechanical grip and subjected to a crosshead speed of 6 mm / min. The thickness of the sample is measured as the average thickness at five different points along the gauge length. Table 1 lists the tensile strength of Examples 4-6 based on the samples kept at 20°C with a moisture content of 65%. Table 2 lists the tensile strengths of Examples 8-13 at a strain rate of 50 mm / min based on samples held at 20° C. for 24 hours at 65% moisture content, and Table 3 lists the tensile strengths based on samples held for 72 hours. Table 4 lists the tensile strengths of Examples 11-13 at a strain rate of 6 mm / min and 24 hours of conditioning, and Table 5 lists the tensile strengths based on 72 hours of conditioning. Table 6 lists the tensile strengths of polymer fibers composed of PBS formed in Example 13 at a strain rate of 150 mm / min and 24 hours of conditioning, and Table 7 lists the tensile strengths at a strain rate of 55 mm / min with 24 hours of conditioning.

[0460] [Table 1]

[0461] [Table 2]

[0462] [Table 3]

[0463] [Table 4]

[0464] [Table 5]

[0465] [Table 6]

[0466] [Table 7]

[0467] The tensile strength data illustrates that the PBS nanocomposites synthesized using the methods disclosed herein are comparable to benchmark PBS synthesized using conventional means known in the prior art, and in some instances, the PBS nanocomposites exhibit improved properties over the benchmark PBS.

[0468] Intrinsic Viscosity Test of PBS Nanocomposite Intrinsic viscosity testing was performed according to ASTM D445 and D2515 test methods. Briefly, 4 g of material is dissolved in 100 mL of chloroform in a volumetric flask over a period of 2 days. The polymer solution is then filtered through a glass core funnel and diluted to different concentrations before being placed in a CANNON-FENSKE viscometer (available from Cannon Instrument Company, State College, PA). Before each measurement, the entire viscometer is placed in a water bath at approximately 25°C for 10 minutes. Each polymer solution is placed in the device and the time it takes for the solution to pass between the two red lines is measured. The intrinsic viscosity is calculated as the intersection point between the plots of relative viscosity and specific viscosity at zero concentration.

[0469] Table 8 lists the viscosity values ​​for Examples 1-6, and Table 9 lists the viscosity values ​​for Examples 8-15. Higher viscosity values ​​are associated with higher molecular weight polymers and higher quality materials. Dispersing NCC in BDO prior to esterification leads to higher viscosity of the PBS nanocomposite, as shown in Example 15. Esterification with succinic anhydride also increases the intrinsic viscosity of the PBS nanocomposite compared to esterification with succinic acid (see Examples 6 and 13).

[0470] [Table 8]

[0471] [Table 9]

[0472] Acid value of Example 15 The acid value of Example 15 is determined according to ASTM D7409 standard. Briefly, about 0.6g of sample is dissolved in chloroform / methanol solution. Phenolphthalein is added to the solution and titrated with 0.1N KOH in ethanol using a Metrohm photometric titrator. The acid value of Example 15 is about 0.9mg KOH / g, which corresponds to about 16 carboxylic acid end group equivalents per metric ton.

[0473] Dynamic Viscosity Dynamic viscosity values ​​are determined by using a Brookfield HAHB viscometer. Figure 1 provides a plot illustrating the relationship between viscosity and temperature for Example 15. Dynamic viscosity values ​​are determined by using a Brookfield AMETEK rotational viscometer equipped with a 27 spindle and a thermostat. A small amount of polymer is placed in a sample container and the temperature is increased to 230°C to induce melting. Viscosity measurements are recorded stepwise as the sample temperature decreases with time. Data collection is stopped when the temperature approaches the melting temperature of the polymer.

[0474] Differential Scanning Calorimetry (DSC) The sample is placed in a TA Instruments Q2000 equilibrated at 30° C. for 1 min under nitrogen gas flow. In the first cycle, the calorimeter is ramped to 140° C. at 10° C. / min. The sample is then held isothermally for 3 min. In the second cycle, the calorimeter is ramped to −60° C. at 20° C. / min. The second cycle is completed with an isothermal hold for 2 min. A final cycle is performed, ramping the calorimeter to 380° C. at 10° C. / min.

[0475] Thermogravimetric analysis (TGA) The samples are equilibrated at 30° C. for 1 min under a stream of nitrogen gas. The oven is heated to 600° C. at 10° C. / min.

[0476] [Table 10]

[0477] Thermal analysis of Examples 8 to 15 Table 10 provides a comparison of a number of thermal properties of each PBS nanocomposite: 1) Glass transition temperature (T g ), 2) Crystal melting temperature (T m ), 3) Low temperature crystallization temperature (T c ), 4) decomposition temperature at 5% mass loss (T 5% ), and 5) percent crystallinity (X c ). Most of the properties are essentially comparable among the various PBS nanocomposites. The cold crystallization temperature is increased for the PBS nanocomposites that are NCC stretched and esterified with epoxidized linseed oil. The polymer produced from Example 13 was subjected to a basic melt spinning procedure using a twin screw extruder, fed into a spinneret block with 19 circular holes. The barrel temperature and spinneret were both set at 190°C, and the barrel pressure was maintained at 500 psi. The fibers were collected on a rotating drum under non-isothermal conditions, without any drawing procedure. At this temperature, the polymer starts to nucleate and grow crystalline domains. In some cases, a higher T c This aids in the dimensional stability of the polymer.

[0478] 1 H-NMR The polymers and compositions are 1 It can be characterized by H NMR.

[0479] [Table 11]

[0480] The number average molecular weights of Examples 8-13 are provided in Table 11. The addition of succinic anhydride resulted in a higher M n is provided.

[0481] Particle size analysis The polymer fibers produced from Example 13 are dissolved in chloroform at a concentration of 100 ppm. The solution is homogenized and then subjected to particle size analysis using a Malvern Nano ZS Zetasizer. The extinction coefficient of the fibers is set to zero and the refractive index of the specimen is set to 1.49 (the value of PBS). The experiment is carried out five times.

[0482] [Table 12]

[0483] The particle size distribution of the dissolved polymer fibers is shown in Table 12 and Figure 2. The majority of the polymer fiber particles have an average diameter of about 10-30 nm.

[0484] Particle size analysis of NCC dispersed using ultrasonic treatment Nanocrystalline cellulose is slowly added to 1,4 butanediol at 1:10 (w / w) while stirring. The solution is continuously stirred and mixed to obtain a viscous white liquid without the presence of lumps. Samples are dispersed at different amplitudes (60%, 80%, and 100%) at a frequency of 1 Hz. For each amplitude, samples are collected for 1, 3, and 5 minutes of sonication. Each sample is diluted using 5% (w / v) distilled water. Particle size analysis of the samples is performed using a Malvern Nano ZS Zetasizer. The extinction coefficient of NCC is set to 0.001 and the refractive index is set to 1.58. The extinction coefficient of water is set to zero and the refractive index is set to 1.33. The experiment is repeated five times for every nine runs to check the reproducibility and improve the precision and polydispersity of the gel size.

[0485] [Table 13]

[0486] Figures 3A-3C and Table 13 compare particle size distribution data across different sonication time points and amplitudes. Particle size correlates with the degree of dispersion of NCC in BDO, with smaller particle size indicating better dispersion of NCC. Increasing sonication amplitude generally results in better levels of NCC dispersion (as indicated by a larger distribution of small particle sizes), especially for shorter sonication times. The difference in sonication values ​​decreases as duration increases. Similarly, longer sonication durations result in greater dispersion of NCC.

[0487] Particle size analysis of NCC dispersed using homogenization Nanocrystalline cellulose is slowly added to 1,4 butanediol at 1:10 (w / w) with stirring. The solution is continuously stirred and mixed to obtain a viscous white liquid with no lumps present. Samples are dispersed at three different homogenizer speeds ranging from 10,000 rpm to 16,667 rpm. Samples are collected at 1 minute, 3 minutes, and 5 minutes of homogenization at each speed setting. Each sample is diluted using 5% (w / v) distilled water. Particle size analysis of the samples is performed using a Malvern Nano ZS Zetasizer. Set the extinction coefficient of Ncc to 0.001 and the refractive index to 1.58. Set the extinction coefficient of water to zero and the refractive index to 1.33. Repeat the experiment five times for every nine runs to check reproducibility and improve the precision and polydispersity of the gel size.

[0488] [Table 14]

[0489] Figures 4A-4C and Table 14 compare particle size distribution data across different homogenization times and speeds. Higher speeds correspond to higher shear levels, and particle size correlates with the degree of dispersion of NCC in BDO, indicating that smaller particle size improves NCC dispersion. As seen in Table 14, high homogenization speeds are required to effectively disperse NCC. Speeds of 13,330 and 10,000 rpm result in a higher distribution of medium and large particle sizes.

[0490] Example 16: PBS NCC + Epoxide Stretching, Sonication Method Example 16 is similar in method to Example 14, except that ELO is added at the beginning of the process with the monomers. Example 15 demonstrates that ELO can be used as a chain extender and / or branching agent when added between the esterification and polycondensation steps of certain methods of the present disclosure. Examples 13, 12, 11, 9, 7, 6, 4, and 3 demonstrate the use of ELO used as a capping agent.

[0491] Example 17: ELO Used as Both a Bulking Agent and a Capping Agent Example 16 is similar in method to Example 14, except that half of the ELO is added after esterification and the other half is added at the end of the polymerization reaction.

[0492] Example 18: Addition of Phytic Acid (PA) Example 18 is a process similar to Example 7, except that the phytic acid solution is added before the esterification step.

[0493] Example 19: PA Addition During Esterification / Polycondensation Example 19 is a process similar to Example 7, except that the phytic acid solution is added after the esterification step and before the addition of the catalyst.

[0494] Example 20: PA Addition During Esterification / Polycondensation Example 20 is similar in process to Example 15, except that the phytic acid solution is added after the esterification step, before the addition of ELO. PA addition at the end of the reaction is shown in Example 7.

[0495] Example 21: Addition of NCC during the esterification / polycondensation step Example 21 is similar in process to Example 15, except that the NCC dispersion is added to the monomer-containing reaction mixture after the esterification step and before the addition of the ELO.

[0496] Example 22: Addition of chitin nanofibers Example 22 is the same method as Example 15, except that chitin nanofibers (CNF) are utilized instead of NCC.

[0497] Example 23: Mixture of chitin nanofibers and NCC Example 23 is the same method as Example 15, except chitin nanofibers (CNF) are utilized as a 50 / 50 wt% mixture with NCC.

[0498] Example 24: PBS with 0.1 wt% NCC + 0.4 wt% ELO using an esterification catalyst (no polycondensation) BDO and SA are charged to a 2 L reaction vessel. The reactants are stirred at 190 rpm with N2 flow until a homogenous slurry is formed. A dispersion of BDO and NCC is added to the reaction vessel to give a BDO:SA molar ratio of 1.05:1 and an NCC content of approximately 0.1 wt%. After addition of the esterification catalyst (hafnium tert-butoxide (HtBO), 100-500 ppm [Hf] total), the reaction temperature is increased to 225°C over 110 minutes. During this increase, water is formed and removed from the reactor. Once at 225°C, the reactants are allowed to stir until a threshold viscosity / end group concentration is reached, then ELO is added (0.4 wt%). The temperature is then increased to 230°C. From this point on, the stirring speed is gradually reduced to 50 rpm for 30 minutes as the reaction proceeds and the viscosity of the melt increases. The vessel is repressurized and a 50 wt% solution of phytic acid in DI water is added as a heat stabilizer and decolorizer (0.4 wt% PA solids). As a final step before pelletization, a transesterification catalyst (80 wt% zirconium butoxide (ZBO) in 1-butanol, 100-500 ppm [Zr] total) is added. A medium molecular weight polymer is formed, which can be subjected to solid state polymerization (SSP) to increase the molecular weight to the desired value during the pellet drying stage before melt spinning, or subsequently after melt spinning in thread form.

[0499] Example 25. Preparation of mixed metal oxide catalyst solutions Catalyst 1 (solution C1): Solution A: Zirconium acetate (Zr) in H2O (Sigma) with a Zr content of 16.5 wt%.

[0500] Solution B: A stock solution of magnesium acetate in H2O was prepared with a Mg content of 4.12 wt%.

[0501] Solution C: A stock solution of kojic acid (KA) in HO was prepared with a KA content of 3.7 wt %.

[0502] Method: Solution A and an amount of deionized (DI) water are heated to 50°C and solution B is added dropwise with stirring. After 1 hour a viscous white sol-gel develops. The solution has a blue / pink hue indicating the formation of colloids. The metal colloid solution is then added dropwise to solution C with stirring at room temperature. The final solution is a viscous white / yellow precipitate.

[0503] A certain amount of glycol is added to the solution and the remaining water and acetic acid are evaporated by gentle distillation. During the distillation process, the solution becomes clear. The final solution is a completely clear yellow liquid with a final Zr content of about 4.92 wt%.

[0504] By adapting the above method, a variety of catalysts can be prepared.

[0505] Preparation of dispersions of cellulose nanocrystals (NCC) NCC Pre-Dispersion NCC powder (NanoCrystalline Cellulose, sodium salt of cellulose sulfate, CAS number 9005-22-5) is added through a sieve to a vortex of liquid water, 1,4-butanediol (BDO), or a water / BDO combination to make up to a 4 wt% NCC solution. For pure aqueous solutions, it is most preferable to make an NCC solution in the range of 0.05-1.5 wt%.

[0506] NCC dispersion The above NCC pre-dispersion may be further processed according to one or more of the following procedures.

[0507] The pre-dispersion can be heated to 30-40° C. with stirring for up to 1 hour and filtered through a sieve to remove undesirable contaminants / gels.

[0508] The pre-dispersion can be sonicated using a probe-tip sonicator operating at 60-80% amplitude and delivering 2500-8000 Joules per gram of NCC. Filter the resulting solution through a sieve to remove any remaining contaminating material / gel.

[0509] In some cases, the pre-dispersion can be further dispersed using a high shear disperser such as a rotor stator mixer or high shear blade. Typically, the solution is stirred for 1-2 minutes at 50-80% of the disperser's rated power. The resulting solution is filtered through a sieve to remove any remaining contaminants / gels.

[0510] NCC functionalization options – none, catalyzed, and non-catalyzed Depending on the desired resin and resin properties, the dispersed NCC solution can be incorporated into the reaction mixture for polymerization reaction by different procedures. The NCC dispersion can be used as is without further functionalization, can be added to the slurry mixture before esterification, or can be added to the oligomer mixture before polycondensation. Various convenient methods can be used to add the NCC dispersion to the oligomer mixture before polycondensation to achieve the desired NCC and solvent concentration in the reaction mixture.

[0511] Activated NCC dispersed catalyst solution The NCC dispersion can be added to an aqueous solution containing zirconium acetate, zirconium acetate hydroxide, zirconyl chloride octahydrate, zirconium propionate, magnesium acetate tetrahydrate, magnesium chloride hexahydrate, or a combination of these products to create a catalytically active solution. The order of addition of these solutions can be changed. For example, when utilizing a mixed metal oxide catalyst, the NCC dispersion can be added to a zirconium-containing solution, followed by a magnesium-containing solution. Alternatively, the NCC dispersion can be added to a solution containing a mixed metal ion catalyst, such as a solution containing zirconium and magnesium.

[0512] The temperature of the mixed NCC dispersion and catalyst solution can be varied. For example, the solutions can be mixed at room temperature (25° C.) and then raised to a temperature range of 50-80° C. Generally, the NCC dispersion catalyst solution is stirred at 50-80° C. for at least 1 hour prior to addition to the reaction mixture.

[0513] It is understood that the amounts and ratios of the components of the NCC dispersion and the metal-based catalyst solution can vary depending on the particular resin and resin properties desired.

[0514] The catalytic metal solutions are typically made in deionized water at a concentration of 2-20% by weight, more preferably 3-12% by weight.

[0515] The ratio of magnesium ions to zirconium ions may be 1-3 mol / mol in the final dispersion. The ratio of NCC to metal ions may be 1-20 wt / wt. The most preferred ratio is 5-15 wt / wt in the final dispersion.

[0516] Non-catalyzed NCC dispersion The NCC dispersion can be added to an aqueous solution of aluminum acetate, aluminum diacetate, aluminum triacetate, or a combination thereof to make a non-catalytic solution. The temperature of the solution can be varied. For example, the metal solution can be added at room temperature, raised to a temperature range of 50-80°C, and then the final solution can be stirred at a temperature range of 50-80°C for at least 1 hour.

[0517] Metal solutions are typically made in deionized water at a concentration of 2-20 wt. %. More preferred are solutions at a concentration of 3-12 wt. %. The ratio of NCC to aluminum ions can be 1-20 wt / w in the final dispersion. A preferred ratio is 5-15 wt / w.

[0518] NCC dispersion characterization The quality of the dispersion can be assessed visually by looking for the presence of NCC pockets or large clumps of NCC gel, or other unsuspended material.

[0519] NCC dispersions can be diluted (e.g., below 2% by weight) and observed between polarizing filters. This approach is useful for identifying non-suspended material in suspension that is otherwise invisible. At high concentrations, placing an NCC suspension against a black surface and pressing it creates a thin NCC gel, which is useful for visualizing non-suspended material.

[0520] NCC dispersions can be characterized using a particle size analyzer such as a Malvern Zetasizer Nano ZS instrument. Tests can be performed after diluting samples to 0.1 wt% and removing contaminants with a syringe filter. Typically, NCC particles dispersed in solution have a size range of 75-125 nm. Metal-functionalized NCCs (such as those described above) may have slightly larger sizes and size ranges.

[0521] Characterization of NCC dispersions can be performed using a variety of methods, including those described by Shafiei-Sabet et al., "Rheology of Nanocrystalline Cellulose Aqueous Suspensions." Langmuir 2012, 28, 17124-17133.

[0522] Epoxidized triglycerides (ELO, ESO) Epoxidized triglycerides such as epoxidized linseed oil (ELO) or epoxidized soybean oil (ESO) can be used in the polymerization reaction. The ELO or ESO is added as a liquid before the addition of the catalyst solution and before the polycondensation step of the reaction. If the polymerization is a single step process, the ELO or ESO is added to the initial reaction mixture.

[0523] Generally, the added ELO or ESO acts as an acid scavenger in the mixture and can improve the color and thermal stability of the resulting resin.

[0524] The added ELO or ESO can also extend the polymer chain length and improve the melt strength and intrinsic viscosity of the final polymer.

[0525] The addition of ELO or ESO to the polymerization reaction mixture can also improve the process. The epoxide groups can react with residual BDO or water solvent present in the prepolymer mixture to improve processing rates. This property can be important when using moisture sensitive catalysts such as Zr butoxide and when using polymerization methods that include a pre-polycondensation step.

[0526] Preparation of polybutylene succinate (PBS) copolymer The catalyst solution is used in the synthesis of polybutylene succinate copolymer nanocomposite resin compositions by adapting any one of the polymerization methods described in Examples 2-7 and Examples 8-15.

[0527] Composition 1 Conditions: Mixed metal oxide catalyst solution C1 was used to prepare PBS nanocomposite resin (130 ppm Zr + 17 ppmg) according to the methods described herein.

[0528] The addition of epoxidized linseed oil (ELO) before polycondensation eliminated the need for a pre-polycondensation step, which is generally important for moisture sensitive catalysts.

[0529] The use of ELO as an additive helps achieve higher MW polymer compositions and creates polymer branch points that enhance the melt strength of the resulting resin composition.

[0530] Polycondensation was carried out at 2.5 mbar vacuum for approximately 1.5 hours, and the polymer was discharged when a torque strength of 22 Newton cm (Ncm) was reached. Generally, there is a linear correlation between the torque increase observed in the polymer reaction mixture and the degree of polymerization of the PBS nanocomposite resin. The torque can be used to monitor the molecular weight in situ during the polymerization. The final resin product (300 g) is a tough, soft plastic with low coloration.

[0531] Composition 2 Conditions: PBS nanocomposite resin (862 ppm Ti) was prepared following a similar method using titanium catalyst. Polycondensation took 2.33 hours at less than 1 mbar vacuum to produce 900 g of resin with less desirable color.

[0532] Composition 3 Conditions: PBS nanocomposite resin (442 ppm Zr) was prepared following a similar method using a zirconium catalyst. Polycondensation was carried out at less than 1 mbar vacuum for 6 hours to produce 8 kg of resin with acceptable color.

[0533] Evaluation of PBS nanocomposite resin The resin compositions produced are evaluated for color / colorless appearance, inherent viscosity and spinnability.

[0534] PBS Polymer Composition 1-0.82 dL / g Intrinsic Viscosity.

[0535] PBS Polymer Composition 2-0.83 dL / g Intrinsic Viscosity.

[0536] PBS Polymer Composition 3-0.88 dL / g Intrinsic Viscosity.

[0537] Melt spinning of PBS nanocomposite resin The resin compositions produced are used to prepare fibers using a melt spinning process. The fibers produced are evaluated for various properties such as hydrolytic stability, fiber diameter, linear density, and tensile strength (e.g., modulus, tenacity, and strain at break).

[0538] FIG. 5 is a plot showing the expected relationship between intrinsic viscosity and maximum fiber length for PBS polymer resins.

[0539] The diameter, tensile strength, hydrolytic stability, and other properties of fibers produced from the PBS nanocomposite resins of the present disclosure under various melt spinning conditions (e.g., increasing draw ratio (DR) from 1 to 10) are evaluated using conventional methods.

[0540] The PBS nanocomposite resins of the present disclosure have been demonstrated to be processable into fibers using commercial melt-spinning processes, and the fibers produced have been demonstrated to have desirable properties, such as colorless or desirably low color, hydrolytic stability over time, stability to dyeing procedures (e.g., dyeability), and desirable tensile strength.

[0541] While the present approach has been illustrated and described herein with reference to preferred embodiments and specific examples thereof, it will be readily apparent to those skilled in the art that other embodiments and examples may perform a similar function and / or achieve similar results, and all such equivalent embodiments and examples are within the spirit and scope of the present approach.

Claims

1. A method for producing a polymer-polysaccharide nanocomposite resin, comprising: The method comprises: a) preparing a mixture comprising diacid monomers and diol monomers and heating at a first temperature to esterify the diacid monomers and diol monomers; b) contacting the heated mixture of step a) with a nanocellulose crystalline (NCC) dispersion after esterification of the monomers to produce an NCC oligomer composition; c) heating a second mixture containing the NCC oligomer composition with a catalyst at a second temperature and under a reduced pressure of 500 mTorr or less to polycondense the NCC oligomer composition to produce a polymer-cellulose nanocomposite resin.

2. The method of claim 1, wherein the diol monomer is based on the formula HO-L 2 -OH, where L 2 is a linking group.

3. The diol monomer is selected from 1,4-butanediol, 1,3-propanediol, and 1,2-ethanediol, 3. The method of claim 2, wherein the diacid agent monomer is selected from succinic acid, monoalkyl succinates, dialkyl succinates, dimethyl succinate, diethyl succinate, succinic anhydride, adipic acid, monoalkyl adipates, dialkyl adipates, dimethyl adipate, diethyl adipate, fumaric acid, maleic acid, and adipic anhydride.

4. The method of claim 2, wherein the diol monomer is 1,4-butanediol (BDO).

5. The method of claim 1, wherein the mixture of step a) further comprises one or more additional components selected from epoxidized oils, epoxy derivatives, and fatty acids capable of being esterified.

6. The method of claim 1, wherein the NCC dispersion comprises at least one of a diacid monomer and a diol monomer.

7. The method of claim 6, wherein the NCC dispersion comprises 1,4-butanediol.

8. The method of claim 1, wherein the NCC dispersion comprises a 1,4-butanediol (BDO) or glycol solution.

9. The method of claim 1, wherein the NCC dispersion does not contain water.

10. The method of claim 1, wherein the first temperature is 150°C or greater.

11. The method of claim 1, wherein the NCC oligomer composition comprises oligomers having an average MW of 500 Da or greater.

12. The method of claim 1, wherein step a) comprises removing volatiles formed in the esterification step via a distillation apparatus.

13. The method of claim 10, wherein the second temperature is higher than the first temperature, and the second temperature is greater than or equal to 210°C.

14. The polymer-polysaccharide nanocomposite resin is a polybutylene succinate-cellulose nanocomposite resin, the NCC dispersion includes 1,4-butanediol monomer and is contacted with succinic acid agent monomer prior to heating the mixture at a first temperature of 150-200° C. and volatiles are removed via distillation; and The method of claim 1, wherein the second temperature is between 200°C and 250°C.

15. The method of claim 14, wherein the succinic acid agent monomer is selected from succinic acid, monoalkyl succinates, dialkyl succinates, dimethyl succinate, diethyl succinate, and succinic anhydride.

16. The method of claim 15, wherein the NCC oligomer composition comprises repeating units of butylene succinate and has an average MW of 1000 to 10,000 Da.

17. The method of claim 16, wherein the second mixture of step c) further comprises an epoxidized oil.

18. The method of claim 1, wherein the catalyst is added during step a) or step b).

19. The method of claim 1, wherein the catalyst is a mixed metal oxide catalyst.

20. The method of claim 19, wherein the catalyst comprises zirconium.

21. An article comprising the nanocomposite resin of claim 1, the article being a yarn or fiber produced from the nanocomposite resin using melt spinning.

22. The method of claim 20, wherein the catalyst comprises zirconium in an amount of 100 to 500 ppm.

23. The method of claim 22, wherein the catalyst comprises zirconium in an amount of 470 ppm.